2015年「澳門講場」輿情: 公民參與個案研究 - Lei, Ming (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

3D Printing Objects As Installation Art: Standing Humanity: 3D Yan Character - Estadieu, Gérald; Martins de Abreu, F.; Barbosa, Álvaro (ACM, 2017)

A Alma e o Lugar de uma Comunidade Singular - Simoes, José Manuel (O Macaense - Identidade, Cultura e Quotidiano, 2019)

A Biblioteca Escolar como promotora de hábitos de leitura: estudo de caso no primeiro ciclo do ensino básico - Gonçalves, Rosa Maria de Fátima Dias da Silva (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A business concept study for Macau's historic centre revitalization (The renovation of the central hotel as as example) - Cruz Vaz Pimentel, Mariana (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A business plan for a part-time job creation social enterprise aimed at helping the elderly - So, Hom Cheung (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A business plan for super baby restaurant - Chao, Pek Chu (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A business valuation of Ford company - Zhang, An Qi (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A case study: an analysis of the parental involvement in a Macau secondary school with primary focus on new immigrant parents from Mainland China and Macau local parents - Cheong, Ka Wai (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A comparative analysis of smartphone brands in Macau: Apple and Samsung - Cheong, Ka Man (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A comparative study on the attitudes of Macanese teachers towards inclusive education (IE) from an IE secondary school and a non-IE secondary school - Chan, Chi Seng (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A conductor's guide to selected choral works by Tien-Hao Jan - Chu, Chun Wai (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Choral Conducting (MCC); University of Saint Joseph

A Confucian Perspective on Tertiary Education for the Common Good - Eh, Edmond (The Journal of the Macau Ricci Institute, 2018)
Confucian education is best captured by the programme described in the Great Learning. Education is presented first as the process of self-cultivation for the sake of developing virtuous character. Self-cultivation then ...

A content analysis of views of disability within Portuguese language newspapers in Macau - Amaral, Ana Helena (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A cultura nas abordagens comunicativas: análise de materiais didáticos em manuais de Português como língua estrangeira - Morais, David (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A defesa noticiosa do status quo - Simões, José Manuel (E-Revista de Estudos Interculturais, 2018)

A Diocese de Macau no alvorecer da Diocese de Dili - Soares, Domingos da Silva (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Religious Studies (MRS); University of Saint Joseph

A discussion on the group psychotherapy treatment for depressed individuals - Chan, Ka Chon (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A dois passos do paraíso - Simões, José Manuel (Aspectus. Revista de Arte & Ciência, 2019)

A experiência de Macau e Hong Kong – Ensino de Arquitectura entre o Local e o Global - Soares, Nuno (VI Congresso Internacional do Conhecimento Científico ISECENSA, 2018)

A feasibility study for Sino-Angolan business consulting: the case of anginvest co. ltd - Faria, Liliana Sofia da Silva (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Evaluation of Fluor Corporation - Cabaça, Anacleto de Jesus da Silva (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial evaluation of MGM Resort International - Lei, Pou I. (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial evaluation of MGM Resorts International - Lei, Cheng I. (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial evaluation of Yum! Brands, Inc - Chan, Hou Kit (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Comcast Corp - Vasu, Kadali (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of GOOGLE INC - Faria, João David Benazra (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Hewlett-Packard company - Lei, Weng Lon (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Lenovo group limited - Sin, Si Weng (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of melco crown entertainment - Lam, O. Fu (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Melco Crown Entertainment Limited - Cheong, Man (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Ralph Lauren Corporation - Tse, Yin Man (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Seagate technology plc - Kam, Tao Choy (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of SJM Holdings Limited - Ng, Lin Kei (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Starbucks corporation - Ho, Chon In (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Starbucks Corporation - Kusnadi, Figo (University of Saint Joseph, 2017)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Tencent Holdings Limited - Leong, Weng Hong (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Tencent Holdings Limited - Tam, Wai Hou (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of the adobe systems incorporated - Law, Kwun Kau (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of the Coca Cola Company - Chan, Weng Chun (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of the Coca Cola company - Kuan, U. Ian (University of Saint Joseph, 2017)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of the Hewlett-Packard company - Un, Cheng Leong (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of the news corporation - Kwan, Wai Sam (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of the xerox corporation - Lam, Kam Long (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of unilever n.v - Bembom, Willem (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Wynn Resorts Limited - Li, Iok I. (University of Saint Joseph, 2016)
Keywords: Financial institutions Valuation; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Wynn Resorts Limited

A financial valuation of Yahoo! Inc - Hong, Nga Man (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation Study of AT&T, Inc - U, Weng Kei (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of BMW AG - Heyerman, Bjoern (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of Dell, Inc - Fong, Pui Wa (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation: study of ecolab,inc - Io, Hei Lam (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of Nu Skin Enterprises, Inc - Kuok, Man Lei (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of oracle corportion - dissertation - Zhao, Wen Yuan (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of target corporation - Vong, Karen (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valucation study of Target Corporation - Vong, Kuan Vai (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Glimpse into the Cultural Situatedness of Computer Science: Some Insights from a Pilot Study - Berglund, Anders; Thota, Neena (2014 International Conference on Teaching and Learning in Computing and Engineering, 2014)
To what extent is students' understanding of computer science culturally situated? This, possibly philosophical question, has come to the surface at Uppsala University, Uppsala, Sweden, where many Chinese students study computer science together with the local students. We did an exploratory study using email interviews to see if our intuitions could be relied on. We collected data from Chinese students studying in master programs and analysed the data using a phenomenographic perspective. A complex intertwined relationship between the content of their learning (the WHAT), the ways in which they went about studying (the HOW), the aims of their studies (the WHY), and the competencies developed from the intercultural context they studied in (the WHERE) was observed. In this paper we offer some insights from the results of the pilot study and discuss how they have shaped our on-going study in the field.
Keywords: Computer science; Context; Cultural differences; Educational institutions; Global communication; Interviews; computer science education; cultural context

A guide to teaching practice - Cohen, Louis; Manion, Lawrence; Morrison, Keith; Wyse, Dominic (Routledge, 2010)
Keywords: Great Britain; Student teaching; Teachers; Training of

A Heart Rate Variability-based Smart Approach to Analyze Frailty in Older Adults - Paulo do Vale Madeiro, João; César Cortez, Arnaldo Aires Peixoto Júnior, Paulo; Alexandre Lôbo Marques, João; Alisson Pessoa Guimarães, Antônio; Hebert da Silva Felix, John (The Smart Computing Review, 2015)
This paper presents an algorithm that applies metrics derived from automatic QRS detection and segmentation in electrocardiogram signals for analyzing Heart Rate Variability to study the evolution of metrics in the frequency domain of a clinical procedure. The analysis was performed on three sets of elderly people, who are categorized according to frailty phenotype. The first set was comprised of frail elderly, the second pre-frail elderly, and the third robust elderly. Investigators from many disciplines have been encouraged to contribute to the understanding of molecular and physiological changes in multiple systems that may increase the vulnerability of frail elderly. In this work, the frailty phenotype can be characterized by unintentional weight loss, as self-reported, fatigue assessed by self-report, grip strength (measured directly), physical activity level assessed by self-report and gait speed (measured). The results obtained demonstrate the existence of significant differences between Heart Rate Variability metrics for the three groups, especially considering a higher preponderance for sympathetic nervous system for the group of robust patients in response to postural maneuver.

A Macau school-based inquiry into shcool :industry links in science - Gull, Nausheen (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A new talent management strategy for the Macau labour bureau-labour inspection department - Conceição, Beatriz Seabra Da (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A origem e evolução dos magmas graníticos de Macao à luz de dados de geoquímica elementar e isotópica / Source and evolution of Macao granitic magmas: insights from wholerock geochemistry and isotopic signatures. - Dias, Ágata; Quelhas, P; Mata, J; Lou, U T; Ribeiro, M L; Borges, R (XIV Congresso de Geoquímica dos Países de Língua Portuguesa e XIX Semana de Geoquímica (XIV CGPLP/XIX SG, international conference, 2018)

A proposal for a revitalization plan for camoes area in Macao and its surrounding community through a humanistic approach - Lei, Mei Kei (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

A proposed young persons community center for prevention and intervention program for vulnerable young persons - Olivena, Qlinto (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A prospective analysis about eEmployee retention strategies for Macao hotel industry - Chong, Ka Yee (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A rainforest experience and its impact on Chinese students' oro-environmental identity and behavior: a phenomenological case study in undergraduate design education in Macau - Tam, Nga Ian (University of Saint Joseph, 2017)
This study covers the limited research on how experiences with nature can foster Chinese students’ pro-environmental identity and behavior. The relevant literature outlines five areas – identity, human behavior, experiences, nature and transformation – in understanding how the Chinese culture of ‘face’ (lain/mian) shapes Chinese students’ identity and behavior today and why experience with nature can help to transform Chinese students’ values, beliefs and norms, and shapes someone who manifests an environmentally sensitive behavior. Past research studies environmental behavior in various dimensions, including the correlation between environmental knowledge and positive environmental attitudes and behavior. Yet surveys of how students’ experience with nature fosters a pro-environmental identity and behavior, especially amongst Chinese students, are rare. The qualitative case study in this thesis seeks to find out whether senior students in the Design Department of IPM’s School of Arts who experienced nature in Southern Thailand show a stronger pro-environmental identity and behavior compared to those not in the experiential learning program. A survey which includes the Environmental Identity Survey (Clayton, 2003) and the Environmentally Responsible Behaviors Index (Smith-Sebasto & D’Acosta, 1995) was administered to all senior students, and an in-depth interview with students who had experience with nature in Southern Thailand was conducted. The findings suggest that a rainforest experience not merely fosters pro-environmental identity and behavior, but student all rounded development especially as a step towards internationalization. The findings also indicate to what extent the programmatic factors of the experience were important in changing Chinese students’ values, beliefs and norms in thinking and behaving environmentally, as well as in student personal development. Keywords: nature, experiential learning, pro-environmental identity, pro-environmental behavior
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

A receção da figura de Melquisedeque na literatura cristã latina - Eleutério, JM (Didaskalia, 2015)
A interpretação da Escritura e das suas diferentes personagens enriquece a Tradição cristã, mas este processo de receção é muitas vezes marcado por debates e polémica …

A review of the Colloquium «Narrative, Media and Cognition» — a cartography of the borders of narrative - Castro, Maria Guilhermina; Caires, Carlos Sena; Ribas, Daniel; Palinhos, Jorge (Journal of Science and Technology of the Arts, 2015)
We present an overview and discussion of the Colloquium «Narrative, Media and Cognition», which took place at Porto's Centre of Catholic University of Portugal in July of 2015, under the organization of the Research Centre for Science and Technology of the Arts (CITAR). Several scholars of different areas presented research about the uses and advances in narrative study and practice in a broad range of areas, giving some important insights about the latest developments in Narrative Studies, Ontology of Narrative and the uses of Narrative in Art, Cinema, Performance, Journalism, Marketing and Literature, among other fields. After briefly describing the main points of each presentation in the Colloquium we try to draw some conclusions and possibilities raised by the Colloquium and take a glimpse of future paths that the use of Narrative can end up taking.

A Review of the Macau's Judiciary Police: Opportunities and Challenges in the Wake of the 21st Century - Che, Ion Fong (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

A school-based investigation of school disipline in Macau - Lei, Chi Hang (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Soundscape Assessment Tool Based On A Massive Multichannel Loudspeaker Setup - Cordeiro, Joao; Barbosa, Alvaro; Santos, A. (2013)

A strategic business development report for jewellery retail industry - Sam, Wai Heng (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A strategic report to help increase the company's growth in the it industry - Ng, Fong Chi (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A study of brand awareness for Mongolian Cashmere in Macau - Batsukh, Selenge (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A study of choral music activities in Singapore schools - Foong, Hak Luen (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Choral Conducting (MCC); University of Saint Joseph

A study of cultural impact on successful entrepreneurship - Ezeonwuneme, Uzoh John (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A study of German management and its management style changes - Ng, Chi Lan (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A study of the factors affecting th retention of secondary English teachers in Macao private schools - Tai, Lai Kan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A study of the risk of burnout in final year nursing students in clinical practicum - Cheong, Chan Long (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A study of Tissot Group's marketing strategy in Macau - Mou, Hio Fong (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A study on customer loyalty and Japanese Ramen specialty restaurant - Leong, Tek Kei (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A study on optimizing the heritage interpretation system in Macao S.A.R - Wong, Cheng Man (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

A study on the Anti-Money Laundering Systems in the banking sector in Macao: a case study of the practice of HSBC Macao - Chan, Ka Ian (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A study on the consumer market for dietary supplements in Macau - De La Cruz Y Lin, Lisa (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A study on the service quality and student satisfaction in student dormitory service at the University of Macau - Lao, Cheok Hin (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A survey of independent art galleries in Macao: analysing organisational,curatorial and promotional strategies under service design framework - Dias, Ana Cristina Ferreira (University of Saint Joseph, 2016)
Keywords: Art galleries, Commercial; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A symbologia Chinesa nos contos de antonio torrado: uma breve abordagem a recepcao da literatura infanto-juvenil em Macau e na China - Fong, Mei Ian (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Lusophone Studies in Linguistics and Literature (MLLS); University of Saint Joseph

A training plan develop reort for call center industry - Vong, Keng Chi (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A valuation of 3M Company - Gilbert, Maria Cristina (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A valuation of McDonald's Corporation - Wong, Wai I. (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A valuation of the Walt Disney corporation - Lei, Man Chon (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A valuation of Thomson Reuters - Leong, Kam Wa (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A valuation study of Marriott international, Inc - Lio, Ka Wai (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A vignette: study do casual explanation and continuum beliefs affect Macau college students' attitudes towards mental disorders? - Wong, Ka In (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A work report on administrative and government policies of the civic and municipal affairs bureau - Lei, Pui San (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

A work report on Macao trade and investment promotion institute - Chan, Ka Un (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Abfaelle sind kostbar!" Konsumethische Perspektiven in Papst Franziskus' Enzyklika Laudaut Si - Gassner, Franz (Eine Wirtschaft, die Leben fördert wirtschafts- und unternehmensethische Reflexionen im Anschluss an Papst Franziskus, 2017)

Academic disengagement in learning science among Macau secondary school students: looking at the taxonomy of science learning amotivation - Lam, Sok I. (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Academic emotions and achievement goals as predictors of academic achievement - Kong, Hou I. (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Academic emotions as mediators between achievement goals and academic: achievement - Kot, Sok Kuan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Academic self-concept and non academic self concept on test anxiety the mediating role of academic emotion - Wong, Nga Na (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Academic self-concept and non-academic self-concept on test anxiety: the mediating role of academic emotions - Tam, Chi Kuan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Academic support and belongingness and academic achievement mediated by academic motivation - Lao, Wai I. (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Accounting in Macau: A Historical Perspective from 1970s until 2008 - Lam, Ching Chi (University of Saint Joseph, 2011)
The current research study embraced the objectives to investigate the transformation of accounting in Macau from the first set of accounting legislations in 1970s, through the first set of accounting standards in 1983, until a year after the first application of international accounting standards, by 2008. From the transformation, the role taken by accounting in the economy and the factors that have influenced the transformation were intended to identify. Through the historical picture, findings have supported and expanded the theoretical concepts that accounting was taking both active and passive roles in the economy. Furthermore, they also supported the theoretical concepts that culture, economic environment, political environment and education influenced the transformation of accounting. The objectives have been structured through three research issues identified from the analysis of past literatures. Five qualitative and quantitative research studies have been carried out, using primary and secondary data from both primary and secondary sources. In-depth interviews on 13 representative respondents of the government, the profession, the industry and the academia, directly or in-directly related with accounting have been done. A case study on a company doing business in Macau since 1970s was included to enrich, supplement and evaluate the findings on the accounting practice of Macau. Based on the findings, a model has been constructed that represented the interaction between accounting and the different factors of the economy. Contributions from the research findings have enriched the research literatures on the area of accounting history. Implications from the findings have generated better insights for the business and economic histories of Macau
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; Thesis and Dissertations PhD in Business Administration (D-BA); University of Saint Joseph

Accuracy of ITU-R BS.1770 Algorithm in Evaluating Multi-track Material - Barbosa, Alvaro; Pestana, Pedro; Reiss, Josh (Audio Engineerg Soceity, 2012)

Achievement goals, academic motivation and academic emotions - Sun, Sok U. Rosa Maria (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Achievement goals on school engagement: looking at the mediating role of academic emotions in Chinese secondary school students - Leong, Sin U. (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Achieving acceptable air quality in Macao through sustainable transportation - Ezeka, Franklin A.N; Chan, Sek Kiu (International symposium on the progrees of technology in environmental impact assessment, 2010 Macao international environmental co-operation forum & exhibition, 2010)

Acoustic communication in marine shallow waters: testing the acoustic adaptive hypothesis in sand gobies - Amorim, Maria Clara P.; Vasconcelos, Raquel O.; Bolgan, Marta; Pedroso, Silvia S.; Fonseca, Paulo J. (Journal of Experimental Biology, 2018)
Skip to Next Section Acoustic communication is an important part of social behaviour of fish species that live or breed in shallow noisy waters. Previous studies have shown that some fish species exploit a quiet window in the background noise for communication. However, it remains to be examined whether hearing abilities and sound production of fish are adapted to marine habitats presenting high hydrodynamism. Here, we investigated whether the communication system of the painted (Pomatoschistus pictus) and the marbled (Pomatoschistus marmoratus) gobies is adapted to enhance sound transmission and reception in Atlantic shallow water environments. We recorded and measured the sound pressure levels of social vocalisations of both species, as well as snapshots of ambient noise of habitats characterised by different hydrodynamics. Hearing thresholds (in terms of both sound pressure and particle acceleration) and responses to conspecific signals were determined using the auditory evoked potential recording technique. We found that the peak frequency range (100–300 Hz) of acoustic signals matched the best hearing sensitivity in both species and appeared well adapted for short-range communication in Atlantic habitats. Sandy/rocky exposed beaches presented a quiet window, observable even during the breaking of moderate waves, coincident with the main sound frequencies and best hearing sensitivities of both species. Our data demonstrate that the hearing abilities of these gobies are well suited to detect conspecific sounds within typical interacting distances (a few body lengths) in Atlantic shallow waters. These findings lend support to the acoustic adaptive hypothesis, under the sensory drive framework, proposing that signals and perception systems coevolve to be effective within local environment constraints.

Acquired hearing loss in the zebrafish model: investigating the mechanisms underlying aging and noise effects on the vertebrate auditory system (University of Saint Joseph, 2019)

Adaptive music composition for ballet fundamental training barre and center practice - Lam, Man Yin (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Adaptive Reuse of Iec Long Firecracker Factory - Lao, Ka Man (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Adolescent pathways to hikikomori in Macau - Hon, Leng Ian (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

"Adolescents' psychological well-being from diversed family types and functioning in Macao" - Tou, Ka Man (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Adoption of Best Practices for Municipal Solid Waste Recycling Management in Macao - Li, Man Ho (University of Saint Joseph, 2017)
Municipal Solid Waste (MSW) is associated with industrialization, urbanization, and a modern economic development, covering several origins such as households and similar waste streams from commerce and trade. Inappropriate waste management impacts human health and the environment negatively, but also the economy and society in general. Waste is today also seen more and more as resource itself. The world trend is to move from mere waste management to a consistent form of resource management within a circular economy, e.g. in form of an Integrated Waste Management System (IMWS). Concerning Macao, MSW is being transported to the Macao Refuse Incineration Plant for thermal treatment with energy recovery. For 2014 and 2015, the amount of waste transferred to the Macao Refuse Incineration Plant for treatment shows a strong yearly increase (11.3 %) being expected to reach or even exceed the maximum allowable waste handling capacity in near future. Alternative methods for waste treatment and valorization are necessary for an effective and sustainable waste management system in Macao. In this research, three case-studies were carried out to analysis real case scenarios that are considered examples of well-functioning MSW management. They were: 1) LIPOR (Portugal); 2) Resinorte (Portugal) and 3) Hong Kong. A questionnaire was prepared and distributed to Macao residents in order to understand their perceptions and views on the existing solid waste recycling in Macao. According to the results of the case-studies and questionnaire, based on the “Polluter Pays Principle” and “Producer Responsibility Scheme”, the main objective of this research is to suggest best practices for waste recycling and management in Macao for the Government, Company, Recycling Trade Participator and the Individual Level
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Adoption of cloud computing by SMES in Macau - Lee, Vai Ieng (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Aesthetic experiences with young children in Hong Kong - Ho, C.K.L. (Meaning making in early childhood research: Pedagogies and the personal, 2018)

African Female Nascent Entrepreneurship In The Macao S.A.R. - Morais, Isabel (Urban Anthropology and Studies of Cultural Systems and World Economic Development, 2014)
African women from different countries and social classes, from those seeking refugee status to diplomats and peasants' daughters, have been arriving in increasing numbers on Chinese shores since the 1980s. The amazing stories of some of these "invisible" but dynamic women have been ignored, yet they reveal great diversity and deserve scholarly attention, as they provide rich material for studies on the African diaspora in China. This article focuses on African migration to Macao, a former Portuguese colony and primary migration destination in the Pearl Delta River Region, which currently hosts the densest African population in China. It explores both the more recent and the relatively longer-term migration of African women and university students to Macao, and examines the intersection of these communities resulting from the overlap between the ongoing global movements of African diasporas and new African migratory trends to China. The article draws on the life stories as well as the educational and entrepreneurial experiences of African women in Macao, and investigates the relevance of ethnic networks of trust and reciprocity for their communities' survival. This article places specific emphais on the experiences of African women, recognizing their achievements in the face of multiple intersections of racism and sexism on the part of both state and society, and reveals how the women employ a resistance strategy by reinforcing ethnic migrant networks.

Aid and poverty reduction: comparing China and France's aid policies and projects in Guinea - Diakité, Ansoumane Douty (University of Saint Joseph, 2016)
The purpose of this research is to analyse the nexus between foreign aid and poverty reduction. In this research, aid provided by traditional and (re)emerging donors, China and France, was compared to understand their strategies toward poverty reduction and the impact of their aid in improving the conditions of their beneficiaries. Guinea, a Least Developed Country, was used as unit of comparison and assessment. Qualitative research methodology was used to collect data about the two aid donors, China and France. Among other research tools used, there are documents’ analysis (official documents from donors and recipients, declarations, scholarly works, media articles, etc.), interviews with various stakeholders, site visits and observation. As for main findings, this research found similarities and differences between China and France’s aid strategies in general and in Guinea in particular. There are similarities in the ways they integrate poverty reduction into their aid policies, motives and partly in their geographical and sectoral allocation systems. In terms of differences, they use different instruments and conditions to deliver their aid for poverty reduction. Regarding the impact of their aid, both donors have to some extent contributed to improving the access of the poor population in Guinea to basic services such as education, health, water and sanitation, etc. Finally, contrary to those who have denied the importance of foreign aid as a financial tool to reduce poverty, this research posits that aid is still a relevant tool to address poverty. However, more work needs to be done at donor, recipient and direct beneficiaries’ levels to ensure its effectiveness. On the other hand, it posits that the divide between traditional and (re)-emerging donors is becoming blurred as their strategies to address poverty are becoming increasingly alike
Keywords: Thesis and Dissertations PhD in Government Studies (D-GS); University of Saint Joseph

Aid to Infrastructure Development in Sub Saharan Africa: An Assessment of China Financing Approaches - Diakité, A.D. (China-Africa: New Types of Exchange, Cultural Identity and Emerging Relations in a Globalized World, 2010)

Airlines Perceptions of Airport Services - Alves, J (University of Saint Joseph, 2017)

Alternative pathway history in a fish with plastic reproductive tactic - Gonçalves, David (Functional Ecology, 2014)

Ambivalence, relationality, complexity and integration grassroots artistic landscape of Macao S.A.R in the post-retrocession era - Mendes, Carla de Utra (University of Saint Joseph, 2017)
This research intends to analyze how the social, political, economical and cultural transformations of the retrocession of Macao S.A.R. to China influenced the contemporary grassroots artistic production, namely their response to the issue of One Country, Two Systems policy. This transitional state of these places in-between creates a somehow ambivalent situation where some of the core values of identity and heritage are fading away due to the forces of the current development. In this sense, it urges to consider the ways in which artists in the post-retrocession era in their lived experiences, form their own sense of community and consciousness of place, time and belonging and, by doing so, can contribute to the preservation of some of the local and specific characteristics, enhancing the cultural vitality of the region. The growing interest by the artists in the issues of preservation and engagement with the locality, trough memory and history, manifested in ‘alternative’ modes of production, is providing a different model of ‘place making’ and a narrative that contrasts and complements some of the top-down cultural policies. Since the focus of development in these territories has been on the idea of creative industries, entertainment and tourism as possible realities for the pressing economical diversification, these grassroots models, functioning as the ‘second system’ open up complexity, providing different questions and answers to the future of artistic production. Finally, departing from these examples, we analyze the possibility of a new image for these kinds of artistic practices, through their incorporation into the possibility of relational aesthetics ‘with Chinese characteristics’, within the perspective of integration, and as emergent features in the field of contemporary art
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

Amotivation in learning mathematics: the taxonomy of why secondary school students in Macau are not motivated to learn mathematics - Iam, Man Cheng (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

An analysis of teacher questions and student responses in a primary school in Macau: a case study - Lee, Soo Mi (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An eco-structuralism approach in soundscape (data) composition - Gomes, J.A.; Barbosa, A.; Penha, R. (ACM International Conference Proceeding Series, 2014)

An Educological Analysis of Multisensory Instruction for Teaching Chinese: A Case Study Of Macao - Found, Andrew; Hwee, Chia Kok (University of Saint Joseph, 2015)
Keywords: China Macau (Special Administrative Region); Chinese language; Study and teaching

An exploratory investigation into success factors of e-commerce in Macau - Hoi, Ka Leng (University of Saint Joseph, 2016)
Keywords: Electronic commerce; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An exploratory study into understanding the marketing mix strategy of green fast-moving consumer goods - Pangan, Maria Rebeca Aquino (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An exploratory study of Chinese rituals in street shops in Macau - Moreira, Irene Mitsiko Sadoyama (University of Saint Joseph, 2016)
Keywords: Business ethics; China; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An exploratory study of consumer attitude and intention to redeem mobile coupons - Wong, Hang Wa (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An exploratory study of management transition in United Kingdom - Ao, I. Tak (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An exploratory study of the training and development needs in the Macau hotel industry - Tou, Cheng I. (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An exploratory study on effective retention of human resources in the Macau gaming industry - U, Chin Hong (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An exploratory study on management style changes in Vietnam - Chan, Im Fan (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An insight on University of Saint Joseph strategic management as part of Macao lifelong learning education system - Lam, Pui Ieng (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

An interpretative study of three aspects of teacher retention, turnover, and attrition in Macau - Cheong, Ngai Hong (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An investigation into students' views of the backwash effects of the English section of the joint admission examination for Macau four higher education institutions (languages and mathematics) - Bramley, Corinna Elaine (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Análise multimodal de estratégias discursivas: debate sobre o “bailout” entre Hillary Clinton e Bernie Sanders - Rocha, Nuno (ElingUP : Revista eletrónica de Linguística dos Estudantes da Universidade do Porto, 2019)
Este trabalho consiste numa análise multimodal das estratégias discursivas de Bernie Sanders e Hillary Clinton num excerto de um debate sobre as benesses dadas pela senadora norte americana aos bancos no pós-crise económica global de 2008. Bernie Sanders e Hillary Clinton evidenciaram uma linguagem corporal diferente, tanto na posição de locutor como na de interlocutor. No entanto, mesmo utilizando estratégias de comunicação verbal e física diferentes, os gestos utilizados enquadram-se no campo dos gestos recorrentemente observados em figuras políticas em estudos feitos por outros autores. Reforça-se assim a ideia de que os gestos em questão são regularmente utilizados por figuras políticas.

Analysing Sands China Limited HR practices, discovering the challenges, issues and possible solutions - Im, Hoi Tek (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Analysis of Business Clusters in Macau - Alves, Jose; Trimarchi, Michael (University of Saint Joseph, 2016)

Analysis of customer in-store experience at the atrium Macau - Leong, Ka Wai (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Analysis of employee turnover for Chinese family business: a case study of Chun Heng Company - Chan, Nga Ieng (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Analysis of employee turnover intention within Macau gaming industry: a case study of Starworld casino - Tou, Weng I. (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Analysis of Fuhong Society's marketing strategies to achieve self-sustainability - Karki, Sanjib (University of Saint Joseph, 2013)
Keywords: Fuhong Society; Marketing Management; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Analysis of job performance & its related causes: a study of Macao Polytechnic Institute - Sio, Man Kei (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Animal welfare in Macau: a feasibility study for a nonprofit organization - Vong, Sok I. (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Anti-corruption policy and sunshine law coping with globalization: the declaration of assets and interests in the CCAC - Kuong, Cheok Man (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Anti-money laundering in the Greater Bay Area: effectiveness, strategies and compliance - Hoi, Kuan Io (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Aprendizagem cooperativa na matemática: uma abordagem de ação-investigação - Alves, Sara Policarpo (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

ARCASIA Roundtable on Architectural Education in Asia - Future Chalenges and Visions - Jay Ho (Architecture Macau Magazine, 2016)

Are Luminous Devices Helping Musicians to Produce Better Aural Results, or Just Helping Audiences Not To Get Bored - Joaquim-Fernandes, Vitor; Barbosa, Alvaro (2013)

Are the devotions of the Passion of Jesus in Macao still a "Dangerous memory"? - Eleutério, João Marques (Asian Conference on Ethics, Religion & Philosophy, 2015)
Among the multiple images used to promote Macao as a touristic destination, we can find some related with the Christian traditions, in particular with the Catholic devotions to the Passion of Christ and the cult of the Virgin Mary. Discussing the concept of “dangerous memory” as proposed by Johann Baptist Metz and analyzing the rituals associated with the devotions around the Passion of Jesus, this paper aims to look at, and present, the different perceptions of a message of subversion of unbalanced relations of power and domination, such as the image of the suffering Jesus in the contemporary society of Macau. The method followed in this paper is ethnographic and structured around some major contributions in the field of Ritual Studies. The implications of this research are related with the different perceptions and usages of a religious image and the drift of its power.

ARQUITECTOS ANÓNIMOS: a Sample of a Generation [Keynote Speak] - Afonso, Filipe (Public Lecture of Faculty of Creative Industries, University of Saint Joseph, 2019)

ARTECH2017: Proceedings of the 8th International Conference on Digital Arts - Caires, Carlos; Cardoso, Jorge Carlos; Lipovka, Aleksei; Bidarra, José; Pimentel, Lúcia (Association for Computing Machinery, 2017)

Artificial intelligence and forensic computing - Lobo-Marques, J. Al (Forensic Computing, 2018)

Artificial selection for male winners in the Siamese fighting fish Betta splendens correlates with high female aggression - Ramos, A.; Gonçalves, D. (Frontiers in Zoology, 2019)
In Southeast Asia, males of the Siamese fighting fish Betta splendens have been selected across centuries for paired-staged fights. During the selection process, matched for size males fight in a small tank until the contest is resolved. Breeders discard losing batches and reproduce winner batches with the aim of increasing fight performance. We assessed the results of this long-term selection process by comparing under standard laboratory conditions male and female aggressive behaviour of one strain selected for staged fights (“fighters”) and one strain of wild-types. The aggressive response of adult fish was tested against their mirror image or a size-matched conspecific. Fighter males were more aggressive than wild-type males for all measured behaviours. Differences were not only quantitative but the pattern of fight display was also divergent. Fighter males had an overall higher swimming activity, performing frequent fast strikes in the direction of the intruder and displaying from a distance. Wild-type males were less active and exhibited aggressive displays mostly in close proximity to the stimuli. Females of the fighter strain, which are not used for fights, were also more aggressive than wild-type females. Aggressive behaviours were correlated across male and female fighter siblings, suggesting common genetic and physiological mechanisms to male and female aggression in this species. The study further shows that results were largely independent of the stimulus type, with the mirror test inducing similar and less variable responses than the live conspecific presentation. These results suggest that selection for male winners co-selected for high-frequency and metabolic demanding aggressive display in males and also enhanced female aggression, opening a wide range of testable hypothesis about the ultimate and proximate mechanisms of male and female aggression in B. splendens.
Keywords: Aggression; Artificial selection; Domestication; Mirror test; Sexual conflict

As fronteiras do sentido num projeto educacional europeu:uma grounded theory - Lopes, Carlos Manuel de Brito Mariano de Vasconcelos (University of Saint Joseph, 2015)
Esta dissertação reporta uma investigação realizada com o objectivo de se compreender a persistente dificuldade de integração sentida no patamar transnacional de um projeto educacional europeu Comenius, de parceria entre escolas. A Grounded Theory foi a metodologia selecionada para orientar a recolha e análise de dados. Os dados empíricos primários foram extraídos de entrevistas abertas, não estruturadas, realizadas aos professores europeus envolvidos nas atividades do projeto. Identificou-se, como principal fator obstrutivo da unidade operacional a esse nível no projeto, a existência de significativas barreiras à comunicação entre os diferentes parceiros europeus, latentes, pouco compreensíveis, mas extraordinariamente operativas. Implicações do estudo e sugestões para esforços subsequentes visando evitar ou, pelo menos, contornar o mesmo tipo de problema, ou problemas similares, estão incluídas
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

As tic na aprendizagem da língua Portuguesa - Simões, Joana Rodrigues (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Asia-Europe Comparative Studies Research Project(AECSRP) - Leandro, F. J (University of Saint Joseph, 2016)

ASIA URBAN LAB – Comparative Studio - Soares, Nuno (DATUM: EDU International Education Conference 2018, 2018)

Asian business: a study of Indian business management styles - Un, Man Long (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Assessing driving behavior in Macau public transportation through mobile crowd sensing - Ma, Fei Chun (University of Saint Joseph, 2018)
This thesis introduces, implements and evaluates an innovative concept for assessing driving behavior in public transportation through Mobile Crowd Sensing (MCS), under the field of Advanced Public Transportation System (APTS) - a sub-group of Intelligent Transportation Systems (ITS). Aggressive driving behavior is known to be a cause of avoidable accidents and to increase fuel consumption. In public transportations, it is also a case for costumers’ dissatisfaction. Monitoring the quality of driving behavior is a key element to overcome this issue and to improve road safety and customer satisfaction. In this research project, a software application (app) for mobile devices was developed as an experimental tool / proof-of-concept, to monitor aggressive driving behavior in bus drivers, collecting data coming from mobile device’s accelerometer and passengers’ qualitative evaluation. The experimental procedure took place in public transportation in Macau (bus only) and consisted of data collection of drivers’ aggressive driving behavior using the developed application. The analysis of collected data suggests that MCS is a viable way to assess drivers’ behavior in public transportation, thus contributing to the improvement of the service and increase of road safety. Although the methodology has been tailor-made for Macau public transportation, it is believed that the same concept can be applied to other cities, leading them towards the goal of becoming smarter cities. Keywords: driving behavior; mobile crowd sensing; crowdsourcing; smart city; advanced public transportation system; intelligent transportation system; road safety; mobile device accelerometer
Keywords: Thesis and Dissertations PhD in Information System (D-IS); University of Saint Joseph

Assessing Driving Behavior in Public Transportation through Mobile Crowd Sensing: A Concept Proposal for Macau Public Transportation System - Ma, Fa Chun; Tóng, Sok Hán; Cordeiro, João (2016 10th International Conference on Innovative Mobile and Internet Services in Ubiquitous Computing (IMIS), 2016)
This paper introduces a concept proposal for accessing driving behavior in public transportation through Mobile Crowd Sensing (MCS), as part of a long-term research project on Advanced Public Transportation System (APTS). The proposed concept makes use of mobile device's accelerometer and passengers' qualitative evaluation to identify aggressive driving behavior, which is believed to be a major factor for unnecessary accidents and fuel consumption. A survey and comparison of IT services (mobile applications and websites) provided by Macau Government and private bus companies in Macau, regarding bus-related information, such as fares, routes and route diversions is also provided.

Assessment of Ambient Particulate Matter Concentration in Schools of Macau - Leong, Seng Nam (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Attachment styles and adjustment as predictors of academic emotions among Macau college students - Cheong, Cheng Ian (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Attitude and perception towards green products in Macao: An exploratory study - Lampo, Alessandro; Leong, Sin U (13th Society for Global Business & Economic Development (SGBED 2014), 2014)

Attitudes and self-beliefs of ability towards mathematics and science and their effects on career choices A case study with Macao-chinese girls - Correia, Ana; Fernandes, Clara; Maia, Joao (Third International Conference on Advances In Economics, Social Science and Human Behaviour Study - ESSHBS 2015, 2015)
This study explores girls’ attitudes and selfassessment of abilities towards mathematics and science and its effects on career preferences. Results from Pi

Attitudes and self-beliefs of ability towards mathematics and science and their effects on career choices: A case study with Macao-Chinese girls - Correia, Ana; Fernandes, Clara; Maia, João (Beyong mirrors: Research pathways (CeiDE 2013-2017), 2018)

Attitudes to mental illness: the effects of labels and symptoms - Found, Andrew; Duarte, Carlos (East Asian Archives of Psychiatry: Official Journal of the Hong Kong College of Psychiatrists = Dong Ya Jing Shen Ke Xue Zhi: Xianggang Jing Shen Ke Yi Xue Yuan Qi Kan, 2011)
OBJECTIVES: To investigate the effects of different Chinese terms for mental illness and related symptoms on the attitudes of adolescents towards sufferers of a mental illness. METHODS: A survey of 578 secondary school students attending 4 schools in Macao was conducted. Each student read a short passage about a new student with a mental illness joining their class. Different versions used different labels to refer to the illness of the new student. The symptoms describing the new student also varied: either describing positive symptoms of schizophrenia or mild negative symptoms only. The attitudes of participants to the new student described were measured. RESULTS: There were significantly more negative attitudes towards the sufferer of a mental illness referred to with a psychiatric label, compared with a general label 'illness'. Participants also expressed significantly more negative attitudes when positive symptoms of schizophrenia were used to describe the new student. The results are discussed in terms of the influence of labels and symptoms on attitudes towards mental illness. CONCLUSIONS: These results supported the existence of 2 additive costs in terms of negative attitudes towards sufferers of mental illness, one associated with the label and the other associated with the symptoms.
Keywords: Adolescent; Adolescent Behavior; Asian People; Attitude to Health; Female; Humans; Male; Mental Disorders; Stereotyping; Students; Surveys and Questionnaires; Young Adult

Attitudes towards counseling between iran and Macau universities students - Rashinia, Jafar (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Attractiveness of Macau International Airport to AirAsia - Au, Hoi Yee (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Audience Participation in Interactive Art Systems: Is Instructional Signage a Necessary Evil? - Cordeiro, João; Martins de Abreu, F.; Estadieu, Gerald (ARTECH2017: Eighth International Conference on Digital Arts, 2017)

Automatic Cardiotocography Diagnostic System Based on Hilbert Transform and Adaptive Threshold Technique - Marques, J. A. Lobo; Cortez, P. C.; Madeiro, J. P. D. V.; Fong, S. J.; Schlindwein, F. S.; Albuquerque, V. H. C. D. (IEEE Access, 2019)
The visual analysis of cardiotocographic examinations is a very subjective process. The accurate detection and segmentation of the fetal heart rate (FHR) features and their correlation with the uterine contractions in time allow a better diagnostic and the possibility of anticipation of many problems related to fetal distress. This paper presents a computerized diagnostic aid system based on digital signal processing techniques to detect and segment changes in the FHR and the uterine tone signals automatically. After a pre-processing phase, the FHR baseline detection is calculated. An auxiliary signal called detection line is proposed to support the detection and segmentation processes. Then, the Hilbert transform is used with an adaptive threshold for identifying fiducial points on the fetal and maternal signals. For an antepartum (before labor) database, the positive predictivity value (PPV) is 96.80% for the FHR decelerations, and 96.18% for the FHR accelerations. For an intrapartum (during labor) database, the PPV found was 91.31% for the uterine contractions, 94.01% for the FHR decelerations, and 100% for the FHR accelerations. For the whole set of exams, PPV and SE were both 100% for the identification of FHR DIP II and prolonged decelerations.
Keywords: Acceleration; Biomedical monitoring; Cardiography; Cardiotocography (CTG); Databases; FHR DIP II; FHR accelerations; FHR baseline detection; FHR decelerations; Fetal heart rate; Hilbert transform; Hilbert transforms; Monitoring; PPV; Transforms; accurate fetal heart rate feature detection; accurate fetal heart rate feature segmentation; adaptive threshold technique; antepartum database; automatic cardiotocography diagnostic system; auxiliary signal; cardiotocographic examinations; computerized diagnostic aid system; digital signal processing techniques; fetal distress; fetal heart rate (FHR); fetal signals; maternal signals; medical signal detection; medical signal processing; obstetrics; patient monitoring; positive predictivity value; preprocessing phase; segmentation processes; uterine contractions; uterine contractions (UC); uterine tone signals; visual analysis

"Balm Balm" the U.K's leading 100% organic skincare company-market opportunity in Macao - Chan, Weng Ian (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Banking efficiency and competition: an empirical research on Macau's banking industry - Lei, Hoi Kin (University of Saint Joseph, 2019)
This research examines the relationship between banking competition and efficiency using relevant data of Macau banking industry from 1999 to 2016. The key finding of this research is to demonstrate a clear causality between competition and efficiency in Macau’s banking industry throughout the study period. The interaction between two vital factors of the banking industry provides a solid empirical evidence for the practitioners and policymakers to make sound decisions accordingly. The most recent data show that there is a wide variation of key operational indicators of different banks in 2016. However, this study finds no evidence that the size of operations in terms of total bank loans would impact banks’ efficiency. Economies of scale or market share doesn’t necessarily bring cost efficiency in Macau’s banking industry
Keywords: Doctorate of Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph

Baptism as Christian Initiation in the New Testament - MONERA, A. (Orientis Aura, 2016)

Barometer of Business Relations between China and Portuguese Speaking Countries: An Economic, Commerical and Cultural Approach - Rato, Ricardo (University of Saint Joseph, 2015)

Barriers to financial inclusion: a study of the economic Community of west African states - Té, Adjombi (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Behavioral plasticity meets neuroplasticity: brain neurogenesis in the polymorphic fish Salaria pavo - Gonçalves, David Manuel Flores (University of Saint Joseph, 2016)

Belgagem: smart suitcase designed for business travelers of 2015 - Rosario, Isabel Maria do (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Beyond product and into the 21st century: exploring mathematics education in Macau - Marques, Tânia Maria Lemos de Sales (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Beyong Mirrors: Research Pathways (CeiDE 2013-2017) (Attitudes and self-beliefs of ability towards mathematics and science and their effects on career choices: A case study with Macao-Chinese girls., 2018)

Biased performance prediction and estimate: concurrent examination of the optimistic bias and miscalibration of performace judgment - Ngan, Henrique Fátima Boyol (University of Saint Joseph, 2016)
Kruger and Dunning (1992) found that unskilled people were typically unaware of their own performance and ability. In this context, unskilled performers were shown to overestimate their performance and ability, whereas skilled performers often accurately predicted their own performance and ability. Such miscalibration in self-assessment is usually attributed to a lack of so-called metacognitive skills necessary for performance evaluation. However, it remains unknown to what extent the miscalibration of performance judgment and optimistic bias is observed in the Chinese culture. This thesis examines patterns of miscalibration of performance judgment and specific optimistic bias. This thesis also builds on a range of previous studies of performance judgment and optimistic bias. In order to investigate the performance judgment and optimistic bias in this context, two studies were conducted as part of the research aspect of this thesis. In the first study, participants were given a reasoning task on which they had to predict their performance before completing the task and estimate their performance upon completion of the task. The second study followed similar methodology, with two additional tasks – Institute For Tourism Studies (IFT) module and the respective midterm examination. Results from both studies indicate that biases in performance judgment occur in the Chinese culture, and may yield negative consequences to those persons who exhibit such judgments. Although metacognitive ability provides some explanation for the miscalibration of performance judgment, the results of the current study indicate that task optimistic bias provides another, equally viable explanation for the miscalibration of performance judgment. The findings presented in this thesis suggest that inaccurate judgments of performance occur within various domains (general and specific iii performance contexts) and that there are a range of implications associated with these biases. Keywords: Miscalibration of performance judgment, optimistic bias, absolute optimistic bias, comparative optimistic bias, overestimation, overplacement, underestimation, underplacement
Keywords: Thesis and Dissertations PhD in Psychology (D-PSY); University of Saint Joseph

Bibliotherapy with the Chinese oracle using the i ching to promote insight - Davis, Adrian John (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Binding Ties of Miscegenation and Identity: The Narratives of Henrique Senna Fernandes (Macao) and Rex Shelley (Singapore) - Morais, Isabel Maria Da Costa (Portuguese and Luso-Asian Legacies in Southeast Asia, 1511–2011, vol. 1: The Making of the Luso-Asian World: Intricacies of Engagement, 2011)
Vários “pequenos” portugueses fizeram sentir a sua presença na “imensa Asia”, uns quase como reis, alguns como escravos, o maior número simplesmente como portugueses capazes de amar mulheres orientais e ser por elas amados. Capazes de fecundar mulheres de cor e fazer sair dos seus ventres portugueses também de cor.(Several “small” Portuguese made felt their presence in the “enormous Asia”, some as almost kings, others as slaves, the great majority just as Portuguese [who were] able to love oriental women and be loved by them. [They were] able to inseminate women of colour and to make their wombs produce other Portuguese also of colour.)Gilberto Freyre, Aventura e RotinaDespite the dynamics of globalization and rapid economic and political development, it is still noticeable nowadays that several Portuguese creolized communities in postcolonial societies have resisted cultural homogenization, particularly those scattered throughout the detached, peripheral regions of East and Southeast Asia that were under the Estado da Índia's sovereignty and influence (Goa, Daman, Diu, Sri Lanka, Malacca, Macao and Timor) and that the Portuguese created alongside the local political authorities (Indonesia and today's Singapore).By the beginning of the seventeenth century, the official population in the colonies of several territories in Asia that proudly claimed Portuguese ancestry had reached nearly one-and-a-half million individuals, as a legacy of colonial (dis)encounters. Centuries later, the Portuguese descendants of this “shadow empire” forged through trading, matrimonial alliances and cultural networks — notwithstanding a pragmatic adaptation to times of unprecedented political, economic and cultural upheaval — persist in a quest for identity and cultural reaffirmation of “Portuguese” cultural differentiation, which continues to be faithfully perpetuated and transmitted, centuries after the earlier Portuguese contacts ceased. These communities show distinctive aspects of what could be called a certain “Luso-Eurasianness”, exhibited in oral literature, religious practices, family surnames, ceremonies, cuisine, public structures, ways of speaking and, above all, in identity-making religious and cultural reinterpretation of lived and shared commonalities.This study argues that, even if relatively scant attention has been paid to the literary production of the communities considered here, in particular in Anglophone postcolonial studies, they have influenced and continue to exercise seminal influence on most postcolonial imaginaries, either in their respective societies or in the contemporary fiction of the Luso diaspora.

Birth date predicts alternative life‐history pathways in a fish with sequential reproductive tactics - Fagundes, Teresa; Simões, Mariana G.; Saraiva, João L.; Ros, Albert F. H.; Gonçalves, David; Oliveira, Rui F. (Functional Ecology, 2015)

Book Review: ‘The Catholic Invasion of China: Remaking Chinese Christianity’, by D. E. Mungello (Lanham, MD: Rowman & Littlefield, 2015) - Law, Cyril Jerome (Heythrop Journal, 2018)

Bowler plus: bowling ball feedback device - Leong, Chou Kin (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Information Technology (MIT); University of Saint Joseph

Breakthrough of self-containment: a work report of the Macao meteorological and geophysical bureau - Lee, In Tai (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Bringing Life Science to Primary and Secondary School Students in Macao: From Genes to Environment - Tagulao, Karen (University of Saint Joseph, 2015)

Building essential life skills through visual arts in the early years education - Goitia, Isabel Maria Marçal da Silva (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Building Sustainability: the Cork House - Afonso, Filipe; Arquitectos Anonimos® project (NATURE AND ENVIRONMENTGLOBAL ISSUES, 2019)
Sustainability takes priority with architect Matthew Barnett Howland. His house in England is made entirely of cork: 100 percent natural, 100 percent recyclable, with almost zero carbon emissions.

Bullying, victim and pro-social behaviors as predictors of mental health among primary students - Vong, Maria (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Business analysis and development of a tutorial center in Macau - Lai, Kai Neng (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Business expansion consultancy report for mac Macau - Xin, He (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Business operations improvement at the Kin Fu Chinese restaurant - Fong, Seng Lok (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Business plan for a cultural - Fashion retailer - Pereira, Alexandre Eduardo (University of Saint Joseph, 2013)
Keywords: Fashion; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Business plan for a Franchised Kumon Center - Loi, Pou Lin (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Business plan for a nursery education school - Wong, Weng Ian (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Business plan for Just Café - Pang, Ka Wai (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Business plan of waffle crepe delight - Leong, Weng Man (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Business plan: pure prawn - Chong, Mao Lou (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Can the application of neuroscience improve processes for ongoing improvement in organizations? - Alves, José (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Can the junket model be applied successfully to the slots business in Macau? - Lei, Pa Kei (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Capture and transformation of urban soundscape data for artistic creation - Gomes, Jose Alberto; Pinho, Nuno Peixoto De; Lopes, Filipe; Costa, Gustavo; Dias, Rui; Tudela, Diogo; Barbosa, Álvaro (Journal of Science and Technology of the Arts, 2014)

Career aspirations of generation y: the case of event management graduates in macau - Alves, José (University of Saint Joseph, 2016)
Keywords: China Macau; Marketing; Organizational effectiveness; Planning; Special events; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Catholic Orders as Efficient Institutions - Rothlin, Stephan; Frey, B. S (Lumen: A Journal of Catholic Studies, 2015)

Catholic schools and inclusive education in Macao: a journey of a thousand miles - Correia, Ana; Teixeira, Vitor (EDUCA - International Catholic Journal of Education, 2017)

Catholic social teaching and environmental responsibility - Rothlin, Stephan; McCann, Dennis (A planetary and global ethics for climate change and sustainable energy, 2016)

Challenges and pitfalls of vocational education in Macao: the teachers' voices - Au, Chi Kwun (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Challenges in bridging creative education and creative industry - Chan, Kai Pang (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Challenges of collborataive blend learning in undergraduate students - Monteiro, Elisa; Morrison, Keith (Education Research and Evaluation, 2014)

Changing minds: an analysis of the impact of the discovery learning methodologies on the student's attitude towards learning - Churchill, Geoffrey Raymond Alan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Characterization of the Natural Soundscape of Zebrafish and Comparison with the Captive Noise Conditions - Lara, Rafael A.; Vasconcelos, Raquel O. (Zebrafish, 2019)
Zebrafish is a well-established model organism in hearing research. Although the acoustic environment is known to shape the structure and sensitivity of auditory systems, there is no information on the natural soundscape of this species. Moreover, zebrafish are typically reared in large-scale housing systems (HS), although their acoustic properties and potential effects on hearing remain unknown. We characterized the soundscape of both zebrafish natural habitats and laboratory captive conditions, and discussed possible impact on auditory sensitivity. Sound recordings were conducted in five distinct zebrafish habitats (Southwest India), from quieter stagnant environments with diverse biological/abiotic sounds to louder watercourses characterized by current and moving substrate sounds. Sound pressure level (SPL) varied between 98 and 126 dB re 1 μPa. Sound spectra presented most energy below 3000 Hz and quieter noise windows were found in the noisiest habitats matching the species best hearing range. Contrastingly, recordings from three zebrafish HS revealed higher SPL (122-143 dB) and most energy below 1000 Hz with more spectral peaks, which might cause significant auditory masking. This study establishes an important ground for future research on the adaptation of zebrafish auditory system to the natural soundscapes, and highlights the importance of controlling noise conditions in captivity.
Keywords: Animals; Animals, Laboratory; Auditory Threshold; Batrachoidiformes; Ecosystem; Environment; Female; Hair Cells, Auditory; Hearing; Housing, Animal; India; Male; Neuronal Plasticity; Noise; Saccule and Utricle; Seasons; Sexual Behavior, Animal; Sound; Species Specificity; Vocalization, Animal; Zebrafish; ambient noise; hearing sensitivity; natural habitat; sound pressure level; soundscape

Charter UIA/UNESCO for Architectural Education - Mohamed, E.; Soares, Nuno; Revedin, J. (International Union of Architects, 2017)

Chew Store: a business plan - Ieong, Hio Na (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Child protection during emergencies in Fiji and Tonga: enabling, constraining or controlling children's agency and participation - Stuebing, Dennis L. (University of Saint Joseph, 2017)
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

China-Africa: emerging relations - Sousa, Ivo Carneiro de; Diakite, Ansoumane Douty; Iwaloye, Ojo Olukayode (Saint Joseph Academic Press, 2011)
Keywords: Africa China Congresses; China Africa Congresses; Relations

Chinese Religious Syncretism in Macau | Orientis Aura: Macau Perspectives in Religious Studies - Eh, Edmond (2017)
In this paper, I address the phenomenon of syncretism with respect to Chinese religions. An analysis of the syncretism that takes place between the three major Chinese religious traditions is first done in its personal and social dimensions. The social structure of Chinese religion is then used as a framework to understand how Buddhism and Daoism were made compatible with Confucianism. All this will serve as a background for the case study of Macau, where Chinese religious syncretism is very much alive. Three popular religious festivals are celebrated annually and simultaneously on the eighth day of the fourth lunar month, namely, zuilongjie (醉龍節) Feast of the Drunken Dragon, tangongdan (譚公誕) Tam Kung Festival and fodanjie (佛誕節) Feast of the Buddha.

Chinese values and perception of professional counselling service: a study among senior high school students in Macau - Chan, Pan Kei (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Chromosome-level reference genome of the Siamese fighting fish Betta splendens, a model species for the study of aggression - Fan, Guangyi; Chan, Judy; Ma, Kailong; Yang, Binrui; Zhang, He; Yang, Xianwei; Shi, Chengcheng; Law, Henry; Ren, Zhitao; Xu, Qiwu; Liu, Qun; Wang, Jiahao; et al. (GigaScience, 2018)

Church in the Making: An Apophatic Ecclesiology of Consubstantiality - Eleutério, João Marques (Theological Studies, 2017)

Citizens' satisfaction with the services delivered by IACM-HAWKER Management Services - Hong, Mei On (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

City guide publications shift towards digital platform a case study in Macau - U, Sou Mui (University of Saint Joseph, 2016)
Keywords: City planning; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Classroom management into learning: using phenomenography to analyse student teachers’ conceptions of classroom management - Correia, Ana Maria (Revista Portuguesa de Investigação Educacional, 2019)
Classroom management is a critical area in the curriculum of teacher education programs. Student teachers’ conceptions of the role of the teacher as a class leader are frequently backed by their intuition and experience as students and socio-cultural context rather than evidence-based. This paper examines the conceptions of classroom management held by a multicultural group of forty-four student teachers attending a teacher education program at a higher education institute in Macao. The study aims at understanding the patterns of variation expressed by student teachers regarding the purpose and relevance of the object of learning. It compares a) the patterns of variation in students’ views of classroom management, and b) the students’ learning progress based on the pre-and post-test. The phenomenographic approach was adopted as the conceptual framework. Participants handwritten transcripts from student teachers at the first and last sessions of the course are the primary type of data collection. The findings show that changes in student teachers’ understanding of the conceptions of classroom management occurred during the course. The initial preferences for disciplinary approaches to classroom leadership have given way to conceptions of promoting the integration of classroom management into learning. The participants expressed increasing adherence to classroom management systems targeting and providing behavioural and academic supports and interventions to children and adolescents with and without special needs.

Classroom management strategies for children with emotional challenges: voices of special education teachers (University of Saint Joseph, 2019)

College Students’ Attitudes Toward Counseling for Mental Health Issues in Two Developing Asian Countries - Kuok, A. C. H; Rashidnia, J (Spritual Psychology and Counseling, 2019)

Communication between Chinese and Portuguese communities: case study of Macau - Lai, Chi Kei (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Community attitudes on disability: an analysis of disability discourse in Macao newspapers - Leong, Weng Ka (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Community health specialist nurses and primary health care in Macao: Linking core competencies with curriculum development - Lam, Oi Ching Bernice Nogueira (University of Saint Joseph, 2012)
This study focuses on curriculum development for competency-based training of advanced practice nursing and smoking cessation in Macao. The aims of this thesis are: (a) to link the core competencies of Advanced Practice Nursing (APN) to curriculum development; (b) to make recommendations for improved specialist nurse training to address current problems of nursing; and (c) to gather data to indicate the scope and the severity of the issues related to nurse training in Macao. The thesis presents a comprehensive literature review of theoretical frameworks of competency-based nursing curricula, curriculum development and design, quality assurance, best practice in competency based models of nursing education, theories of change and innovation, needs analysis and stakeholder satisfaction. The thesis develops and implements a needs analysis and situational analysis of nursing education in Macao, using a „mixed methods‟ approach that integrates quantitative and qualitative data to identify the needs for, and perception of, core competencies in Community Health APNs by the health professionals and clients of the community. This includes an empirical survey of stakeholders, semi-structured interviews with professionals in the field of nursing and nurse training, structured questionnaires from clients, observational data on training and implementation of competency-based curricula, and evaluation of a piece of curriculum implementation of an APN training program on smoking cessation. Through action research cycles, the thesis synthesizes a range of literature and empirical data, and, from these, gains feedback for improvement and refinement of the new curriculum to be implemented. As well as conducting client satisfaction surveys of the primary health care provision and services in Macau and how these could be improved, the thesis provides the framework for a competency-based curriculum for nursing education in Macau. The thesis argues that, in order to keep abreast with current developments in nurse training and practice worldwide, it is essential for APN education and training to adopt a competency-based approach and for curricula to be framed in terms of competencies and outcomes. It indicates that these are currently under-developed in Macao, and that there is an urgent need for them to be addressed, in terms of general, core and specific competencies (e.g. smoking cessation). The thesis argues that, for such developments to iii happen, fundamental changes will be required to curricula and to APN nursing practice, as, even though there may be changes to curricula, the opportunity to put general and specific competencies into practice by APNs is currently severely restricted because of a range of constraints in Macao. The thesis argues that there is an urgent need for APNs to receive competency-based training and practice for smoking cessation, and the opportunity to put this training into practice. It indicates that even short workshops and training programs can be effective. The thesis argues that current obstacles to such practice can be identified, but that overcoming them presents serious challenges to the current system, and will require action on many fronts, including revisions to local legislation, nurse credentialing, facilitation by senior managers of the health service, and an increase in the supply of nurses. The thesis indicates that there is a strong and united will for changes to be made to bring about competency-based training, curricula and practice in Macao, but that there are many practical barriers to be overcome in order to bring about these changes
Keywords: Macao; PhD in Education (D-SE); Practice Nursing; School of Education. Education; Smoking Cessation; Thesis and Dissertations; University of Saint Joseph

Comparing student's learning satisfaction in lower secondary and upper secondary school education - Kong, Weng Mei (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Comparing Urban Rules for Urbanizing Villages in Hong Kong, Macau, and Shenzhen - Tieben, H.; Chu, J.; Soares, Nuno (ISUF 21st International Seminar of Urban, 2014)

Comparision of modern cultural tourism in Hong Kong and Macao - Mui, Ho Yan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Complexities of Languages and Multilingualism - Baragül, Fernando (Educational Challenges in Multilingual Societies, ed. Zubeida Desai et al., 2010)
Complexities of Languages and Multilingualism

Complexity Theory, School Leadership and Management: Questions for Theory and Practice - Morrison, Keith (Educational Management Administration & Leadership, 2010)
Complexity theory (CT) has had a meteoric rise in management literature and the social sciences. Its fledgling importation into school leadership and management raises several questions and concerns. This article takes one view of CT and argues that, though its key elements have much to offer school leadership and management, caution has to be exercised in accepting CT too readily, as it: (1) is unclear on its own novelty, nature and status; (2) can be regarded as disguised ideology in conflating description and prescription; (3) confuses explanation with prediction; (4) is relativist, undermining its own status; (5) contains problems in its advocacy of self-organization; (6) neglects the ethical and emotional dimensions of leadership and management; and (7) risks exonerating school leaders and managers from reasonable expectations of accountability and responsibility. The article concludes that there are questions to CT at the levels of theory, ontology, deontology and ethics, but that it offers useful challenges for school leadership and management.

Composing with Soundscapes: an Approach Based on Raw Data Reinterpretation. - Gomes, Jose; Pinho, N.; Lopes, F.; Costa, G.; Dias, R.; Barbosa, Alvaro (2014)

Computer Literacy Teaching Using Peer Learning and Under the Confucian Heritage Cultural Settings of Macao, China - Wong, Kelvin; Neves, Ana; Negreiros, João (2017)
University students in Macao are required to attend computer literacy courses to raise their basic skills levels and knowledge as part of their literacy foundation. Still, teachers frequently complain about the weak IT skills of many students, suggesting that most of them may not be benefiting sufficiently from their computer literacy courses. This research proposes an enhanced framework based on constructivist principles by using peer-tutoring to increase cost effectiveness and to improve student outcomes. Essential to this proposed model is the training of former course graduates as peer-instructors to achieve high quality learning results. At Instituto de Formação Turistica (IFT), a case study was used to evaluate its effectiveness using a qualitative analysis. In Macao, most students have a Confucian Heritage Cultural (CHC) background and the current findings demonstrate that students share more easily their learning difficulties within their group as their interpersonal relationships improve. It is suggested that since CHC cooperative learning is primarily based on bonds, students involved in this 'relationship-first, learning-second' type shared a larger amount of knowledge and social skills, a dual positive outcome. Moreover, English language is a major barrier for the understanding of the teacher’s message to Chinese students. Meanwhile, the negative Western concept of plagiarism is replaced, under the CHC, as the ‘face giving’ and it is directly based on the relationship intensity to 'help friends'. At last, peer-tutors play a key role in the student increase internal motivation regarding the joy of the learning process.

Computer Literacy Teaching Using Peer Learning and under the Confucian Heritage Cultural Settings of Macao, China - Wong, Kelvin; Neves, Ana; Negreiros, Joao (International Association for the Development of the Information Society, 2017)
University students in Macao are required to attend computer literacy courses to raise their basic skills levels and knowledge as part of their literacy foundation. Still, teachers frequently complain about the weak IT skills of many students, suggesting that most of them may not be benefiting sufficiently from their computer literacy courses. This research proposes an enhanced framework based on constructivist principles by using peer-tutoring to increase cost effectiveness and to improve student outcomes. Essential to this proposed model is the training of former course graduates as peer-instructors to achieve high quality learning results. At Instituto de Formação Turistica (IFT), a case study was used to evaluate its effectiveness using a qualitative analysis. In Macao, most students have a Confucian Heritage Cultural (CHC) background and the current findings demonstrate that students share more easily their learning difficulties within their group as their interpersonal relationships improve. It is suggested that since CHC cooperative learning is primarily based on bonds, students involved in this "relationship-first, learning-second" type shared a larger amount of knowledge and social skills, a dual positive outcome. Moreover, English language is a major barrier for the understanding of the teacher's message to Chinese students. Meanwhile, the negative Western concept of plagiarism is replaced, under the CHC, as the "face giving" and it is directly based on the relationship intensity to "help friends". At last, peer-tutors play a key role in the student increase internal motivation regarding the joy of the learning process. [For the complete proceedings, see ED579282.]
Keywords: Action Research; Asian Culture; Case Studies; College Students; Computer Literacy; Confucianism; Cooperative Learning; Cost Effectiveness; Cultural Influences; English (Second Language); Foreign Countries; Grades (Scholastic); Language of Instruction; Models; Participant Observation; Peer Relationship; Peer Teaching; Program Effectiveness; Qualitative Research; Questionnaires; Semi Structured Interviews; Student Attitudes; Student Journals; Student Surveys; Teaching Methods

Computer science at school/CS teacher education: Koli working-group report on CS at school - Schulte, Carsten; Hornung, Malte; Sentance, Sue; Dagiene, Valentina; Jevsikova, Tatjana; Thota, Neena; Eckerdal, Anna; Peters, Anne-Kathrin (Association for Computing Machinery, 2012)
In an international study, experts reflected on their national state of computer science education in school, and the associated situation and education of computer science teachers. While these situations are shaped by local circumstances, they are also shaped by changes in the discipline. The results of the study showed a number of recurrent themes and patterns such as curriculum difficulties, training and support for teachers, as well as the understanding (e.g. computer science vs. information technology) and relevance of computer science. The study also draws attention to initiatives that are being undertaken at the local and international levels to solve these problems. Finally, the study points out trends which are -- according to the experts asked -- likely to occur within the next few years.
Keywords: CS at school; CS ed research; CS teacher education; curriculum; goals; international comparison; pedagogy; study; topics

Computer Science Students' Perception of Computer Network Security - Cambazoglu, Volkan; Thota, Neena (2013 Learning and Teaching in Computing and Engineering, 2013)
In the last decade, the progress of internet technologies has led to a significant increase in security and privacy issues for users. This study aims to investigate how computer science students perceive computer network security. Thirty three students participated in the study in which we gathered data through a questionnaire. In this paper, we present an analysis that is inspired by the phenomenographic approach. Our conclusion is that the students have different levels of understanding of computer network security depending on their usage of the concepts they have learned, their theoretical or practical orientation to the subject, and their interest in the field.
Keywords: Computer Network Security; Computer Science Education Research; Computer security; Educational institutions; Protocols; Training; Wireless networks

Conception of a southern Portuguese wine: a fesibility analysis - Santos, João (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Conceptions of giftedness in Macau - Leong, Nga Ut (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Conceptual frameworks of big data generation for Macao - Sousa, Ana Paula Soares Batalha da Silva de (University of Saint Joseph, 2015)
Keywords: Big data; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Conceptualizing the Second Education Circuit for China’s Doctoral Students in Asia - Ge, Yun; Ho, Kong Chong (International Journal of Chinese Education, 2019)
The quest to become research universities of international repute has led flagship universities in East and Southeast Asia to develop a new focus on attracting international doctoral students. This paper aims to understand Chinese doctoral students’ mobility in the immediate region and their education to work perceptions. The study draws from a sample of 301 doctoral students from China who were studying at five universities in Japan, South Korea, and Singapore. Analysis on students’ decision making and after-study pathways highlights the regional exchange in related areas. We argue that this regional mobility of doctoral students, characterized as the second education circuit, is facilitated by a higher education migration infrastructure with three interactively weaved dimensions: commercial, social, and regulatory. The research findings suggest the growing importance of Asia as a regional second circuit of doctoral training for students from China.

Concordância verbal - Baxter, A. N.; Lopes, N. (Tânia Lobo (ed.) O português escrito por afro-brasileiros no século XIX: atas de reuniões da Sociedade Protetora dos Desvalidos, 2018)

Conflict between affective versus continuance commitment among casino dealers - Kuok, A. C. H; Taormina, Robert J. (Evidence-based HRM: a Global Forum for Empirical Scholarship, 2015)
Purpose – The purpose of this paper is to empirically investigate the extent of the reported low affective commitment compared to continuance commitment of Chinese casino dealers, to discern if there is a significant difference between the two types of commitment, and to identify factors that could explain the difference between them. Design/methodology/approach – Questionnaire data were obtained from 247 Chinese casino dealers working for the three major casino groups in Macau. Correlations and regressions were used to analyze the data. Findings – Dealers’ affective commitment was significantly lower than their continuance commitment, suggesting dealers do not like their jobs but do not leave them, which indicates they have cognitive dissonance about their jobs. Organizational socialization, organizational support, and supervisor integrity were positively correlated with affective commitment; while value of money, pay satisfaction, and neuroticism, were positively correlated with continuance commitment. Organizational support was the strongest predictor of affective commitment, while the value they place on money was the strongest predictor of continuance commitment. Practical implications – Casino managers could improve dealers’ affective commitment by facilitating their organizational socialization, especially training and rewards for their work, providing greater organizational support, and fair and supportive treatment from their supervisors. Originality/value – This is the first study to provide evidence of the difference between affective and continuance commitment in Chinese society, and identifies factors that influence each type of commitment, and may help resolve the employees’ dilemma about their jobs, which is an important concern for Chinese managers.

Conflict resolution among adolescents in Macao - Fong, Kit Leng (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Connectivism and the Use of Technology/Media in Collaborative Teaching and Learning - Thota, Neena (New Directions for Teaching and Learning, 2015)
This chapter explores the ways in which a relational understanding of the education process and the use of collaborative technologies in the connectivist tradition might inform and transform university teaching.

Consultants report: develop a questionnaire to test intention to participate in sweepstakes: to enable a local FMCG company to test the mass market in Macau - Chan, Yee Yee (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Contemplation on Today’s Digital Education - Negreiros, João; de Fatima Oliveira, Maria (Springer International Publishing, 2015)
This paper starts to address the affect and side-effects of social media on people’s live in a pure contemplation perspective. Social networks are revised and some issues regarding its impact on education was not forgotten such as the teacher role in the digital classroom, formal versus informal learning or Web 2.0 tools use. Since Moodle is the first Learning Management System whilst Facebook is the first social network in the world, a survey was accomplished with two independent classes of e-business students at University of Saint Joseph, Macao, China, on their attitudes toward both online services in a learning framework. In general, the results confirms to a certain extent others previous studies on the question of whether using Facebook as an educational tool is more effective than Moodle.
Keywords: Education; Facebook; Macao; Moodle; Social Networks

Content and language integrated learning in higher education: a case study - Santos, Pedro Paulo Pereira Dos (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Contributions to the Macao's Social Security Fund: the Arbitrary System - Un, Ka Man (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Coping with Merging and Advanced Market Risks - Xia, Harry (International Journal of Economics and Social Science, 2015)

Corporate social responsibility at Foxconn with particular regard to employee issues - Kuok, Sin Teng (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Corporate social responsibility in Macau gaming industry - Madureira, Óscar Alberto Correia da Costa (University of Saint Joseph, 2015)
Keywords: Gambling; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Correlation of emotional intelligence, sports emotions, and coping strategies among Chinese adolescents in Macau - Yuen, Po Shan (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Corruption in Macao causes, consequences and challenges ahead - Tong, Ka Ieng (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Corruption in timor-leste: causes, consequences, and reform - Borges, Almério Saldanha (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Cosultant's report for improving on-time delivery performance and inventory control of commercial business unit (CBU) in semiconductor industry - Chong, Lai Ha (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Cote D'ivoire: On the Way to Become an Economic Hub in Western Africa - Sedia, Gounto Jean-Claude (University of Saint Joseph, 2017)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Creating multiculturalism amidst ethnic, linguistic and religious diversity: a Filipino perspective. - Monera, Arnold (Multiculturalism in Asia – Peace and Harmony, 2018)

Creative Engagement: Multimodal digital games in children's learning environment in Macau S.A.R. - Martins de Abreu, F.; Barbosa, Álvaro (Association for Computing Machinery, 2017)
One of the biggest challenges that we have encountered, when trying to encourage digital games in schools, is trying to explain what its benefits are in teaching and learning environments. In this pilot experimental study we explore how multimodal audio and visual games can be used in learning environments for children, specifically by fostering creative behaviors through User-Centered design approaches. To achieve this objective, a framework is being developed with multimodal experiences based on flexible design patterns that exploits basic visual and audio elements, allowing children from three to six years of age to play and learn through fun and subsequently trigger creative behaviors. These studies are making use of tangible objects, digital games and mobile platforms. We are making use of commercial digital games to understand and discuss the affordances of these games in an educational environment and how they support creativity in learning. (Fig.1)
Keywords: Children; Creative Learning; Devices; Digital Games; Mobile; Multimodal; Tangible Technologies; User-Centered Design

Crisis in motivation: exploring the factor structure of academic amotivation among school student in Macau - Chao, Josefina (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Critical development of green marketing in the hotel industry: Macao case study - Lampo, Alessandro; Gregori, Gian Luca; Cardinali, Silvio; Temperini, Valerio (SGBED Research Symposiums：Doing Well by Doing Good: New Perspectives on Corporate Social Responsibility, Sustainability, and Inclusive Capitalism, 2012)
This study analyzes the green marketing strategies with specific reference to the hotel industry. The concept of green marketing in this sector is crucial due to the growing expected importance of tourism in the future of global economy and its potential impact on social and economic development; this is true particularly in areas with relevant volumes of tourist arrivals. In this sense, we carried out an exploratory research in the hotel industry of the Special Administrative Region (SAR) of Macao in order to: highlight the primary motivations that underlie interventions geared towards the eco-sustainability of hotels, the services they offer and point out the problems, issues, and future prospects in the development of green marketing, as well as explore the role of eco-sustainable values in hotels’ online communication policies. In order to reach these aims a qualitative research was carried out with a semi-structured questionnaire (face-to-face interviews) to a group of hotels. The research was finished by an analysis of their websites, in order to verify possible references to the steps taken to protect the environment.

Cross-Adaptive Polarity Switching Strategies for Optimization of Audio Mixes - Pestana, Pedro; Reiss, Josh; Barbosa, Alvaro (2015)

Cultural tourism in Macau: positioning through identification of consumer segments and enhancing the product offering - Chiang, Ka Pek (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Culturally Responsive Teaching: Attitude and Practice among Teachers in Macau (University of Saint Joseph, 2019)

Current practices of successful Hong Kong middle school choral directors in working with voice-changing boys - Lam, Hoi Yan (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Choral Conducting (MCC); University of Saint Joseph

Curriculum development of MICE in tertiary education in Macao - Chan, Kam Lun (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Curriculum leadership and management - San, Pek Leng (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Cyber - bullying in Macau schools: an exploratory study - Afshar-Tongga, Mona (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Cyberculture and Multimodal Digital Games in Learning Environments: Fostering Creativity in Macau’s Educational System - Martins de Abreu, F.; Barbosa, Alvaro (LISBON CONSORTIUM - VIII Lisbon Summer School for the Study of Culture “Cyber+Cipher+Culture", 2018)

Da aptidão à aspiração: um caminho por percorrer - Correia, Ana (CECS - Publicações / eBooks, 2015)

Darwinism, Freemasonry and print culture: The construction of identity of the Macanese colonial elites in the late nineteenth century - Morais, Isabel (Macao - The Formation of a Global City, 2013)
In his most quoted study Imagined Communities, Benedict Anderson argues that the invention of the printing press and the rise of print media contributed to a textual representation of the concept of the nation and nationalism. He states that ‘popular’ print culture was also crucial in its contribution to a global exchange that would have reinforced the idea of an ‘imagined community’.1 Anderson further explains that before the eighteenth century, the concept of nation was extensive, as Latin was the language of a broad, vast, imagined community called ‘Christendom’, but as there were changes in the religious communities, such a concept began to be replaced by French and English as vernacular languages of administrative centralization.2 Thus, print capitalism allied to the book market supported by the improvement of communications and the emergence of new and diverse forms of national languages, originated the creation of clusters of small creole ‘imagined political communities’ that were eager to promote new forms of national and cultural consciousness, aimed at widespread literacy through liens of kinship, ethnicity, fraternity, and power loyalties.3 This chapter posits that Anderson's arguments regarding creole nationalism in the new world, fit the particular case of the emergence of the printing, publishing and book-selling culture among a Euro-creole bourgeoisie from Macao with solid kinship, ethnic, commercial and social connections in Hong Kong, Canton, Shanghai and other littoral spaces in the treaty ports in East Asia, and takes these developments as a necessary point of departure. I argue that they used the widespread nature of print media to empower themselves and other community members with the progressive eighteenth-century Enlightenment ideas on rational scientific knowledge. They embraced atheism and anti-clericalism as important elements of enlightenment, thus promoting scientific culture, constitutional monarchy or republican forms of government, social mobility for ethnic minorities, and religious and intellectual tolerance that to a certain extent challenged the Catholic Church and conservative circles.

De Portugal a Macau: Filosofia e Literatura no Diálogo das Culturas - Natário, Maria Celeste; Espadinha, Maria Antónia (Universidade do Porto, Faculdade de Letras, 2017)

Dealing with a changing society: a work report on further development of the government infnormation bureau - Loi, I. Man (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Depiction of the freedom of the press and access to sources of information for working journalists in Macau - Rato, Frederico; Simões, José Manuel; Flores, Rui (Macau Portuguese and English Press Association, 2017)

Desafios à unidade geopolítica da lusofonia - Leandro, Francisco da Silva (IDNBrief, 2017)
info:eu-repo/semantics/publishedVersion

Descobrimentos marítimos: miscigenação e preconceito em Senna Fernandes - Conde, Margarida (De Portugal a Macau. Filosofia e literatura no diálogo das culturas, 2017)

Design Thinking and Entrepreneurship: In Macanese Corporate Environment - Caldeira, Wilson (University of Saint Joseph, 2016)
Keywords: Entrepreneurship Religious aspects; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Design Thinking associated with R&D: Process Management and Knowledge Transfer for the Creative Industries - Cerejo, Joana; Barbosa, Álvaro (LAP LAMBERT Academic Publishing, 2014)
The difficult task of innovation is a key facet of Research & Development (R&D) institutions. To Design, innovation is to make the project technically feasible, economically viable, merchandising interesting and emotionally engaging. Design Thinking integrated with R&D organizations can foster the relationship between Universities and new markets. By addressing these topics, this book researches new emerging design methods and provide an overview of Design Thinking tools that can be applied in an early stage of the R&D research process to produce meaningful results. It is taken into account that design, through Design Thinking, extends to the experience that costumers/users have with products/services or even multidimensional experiences, which is a relevant input for R&D innovation development. In fact, the establishment of coherent guidelines for the Design Thinking process is a very complex task, due to its interdisciplinary requirements, that convey many diverse mindsets. The main focus of this book is creating an analysis toolkit that enables non-specialist and specialist users to perform high-quality design solutions.

Determinants of social media shopping intention in Macao - Ng, Iok Mui (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Developing a community-based science curriculum for primary school students in Macau - Ng, Shuk Yan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Developing a customer call-center in Macau for a beverage company - Gunawan, Albert (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Developing a Holistic Approach to Learning and Teaching Introductory Object-Oriented Programming - Thota, Neena Jawaharlal (University of Saint Joseph, 2010)
This thesis articulates the development of a holistic approach to enhance learning and teaching in an object-oriented programming course. Starting with the premise that it is not possible to improve teaching without understanding how students learn programming, this thesis embodies the processes and reflections experienced while applying knowledge of how students learn programming, to design a learning environment that enhances learning outcomes. First, a theoretically based framework for the teaching of the course is developed. A holistic approach using a plurality of pedagogic theories, taxonomies, and instructional designs is employed to bridge the gaps between the bodies of knowledge relating to the ways that students approach programming and the application of this knowledge to design the course. Second, in two cycles of action research, the course is implemented and the analysis of its outcome is conducted using mixed methods data collection techniques. The evaluation is integrative and seeks multiple forms of evidence for student engagement and improved learning. The original contributions from this research in the form of new initiatives, perceptions, and understandings, as well as implications for theory and practice are described. A claim to knowledge is established by explaining the significance of the research to student learning, personal practice and beliefs, institutional influence, and potential for influence on computing education research. Quality criteria are applied to assess the validity and rigor of the action research project, and the research is appraised as a scholarly enquiry and a transformative process that led to innovative forms of thinking and acting
Keywords: Thesis and Dissertations PhD in Information System (D-IS); University of Saint Joseph

Developing an employer brand for the judiciary police: a consultants' report - Chan, Hao Man (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Developing an understanding of Yoox Net-A-Porter Group's business model - Brito, Clara Susana Pereira Soeiro de (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Developing Teledifusao de Macau (TDM) Issues and Prospects - Siew, Pek Leng (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Development of management style in Taiwan - Jung, Iok Fan (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Development of management styles in India - Chau, Sou Cheng (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Development of SMES in Angola - Carvalho, Ahod Vazeriva Cardoso De (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Development of Structure and Sensitivity of the Fish Inner Ear - Vasconcelos, Raquel O.; Alderks, Peter W.; Sisneros, Joseph A. (Fish Hearing and Bioacoustics: An Anthology in Honor of Arthur N. Popper and Richard R. Fay, 2016)
Fish represent the largest group of vertebrates and display the greatest diversity of auditory structures. However, studies addressing how the form and function of the auditory system change during development to enhance perception of the acoustic environment are rather sparse in this taxon compared to other vertebrate groups. An ontogenetic perspective of the auditory system in fishes provides a readily testable framework for understanding structure–function relationships. Additionally, studying ancestral models such as fish can convey valuable comparable information across vertebrates, as early developmental events are often evolutionary conserved. This chapter reviews the literature on the morphological development of the fish auditory system, with particular focus on the inner ear structures that evolve from an otic placode during early embryonic development and then continue to undergo differentiation and maturation in the postembryonic phase. Moreover, the chapter provides a systematic overview of how auditory sensitivity develops during ontogeny. Although most studies indicate a developmental improvement in auditory sensitivity, there is considerably species-specific variation. Lastly, the paucity of information and literature concerning the development of auditory capabilities for social communication in fishes is also discussed. Further investigation on the development of structure and function of the fish auditory system is recommended in order to obtain a deeper understanding of how ontogenetic morphological changes in the auditory pathway relate to modifications in acoustic reception, auditory processing, and the capacity to communicate acoustically.
Keywords: Auditory development; Auditory physiology; Ear morphology; Fish ontogeny

Diferenças étnico-culturais e expectativas académicas entre dolescentes Macaenses, Portugueses Europeus, Africanos e Chineses ultramarinos: estudo de caso em contexto escolar - Street, Maria Cristina Munhoz (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

DISRUPT - Environmental Endocrine disruptors: Current situation in Macao, neurobehavioral effects and bioremediation strategies - Gonçalves, David (University of Saint Joseph, 2018)

Distribution of Meiji baby milk powder in Macao - Leong, Chi Cheong (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Diving into the unknown: robotics as tools to study the deep-sea. Informed Scientific Sampling in Large-scale Outdoor Environments - Dias, Ágata (International Conference on Intelligent Robots and Systems IROS, 2019)

Domestic Violence in Macao: Its Socio-Cultural, Psychological and Economic Perspectives to Public Policy Making - Munoz-Agcaoili, Suzette (University of Saint Joseph, 2015)

Drug abuse among adolescents in Macau: its psycho-socio-cultural perspectives - Song, Yi Xuan (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Drug abuse and trafficking in Macao: a perspective on the challenges for the law enforcement - Ho, Cheng I. (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Dutch Disease In Macau: Theoretical Modeling, Empirical Diagnosis And Treatments - Mieiro, Susana Margarida Baptista (University of Saint Joseph, 2013)
Keywords: Dutch Disease; Macau

E-waste recycle plant in Macau: a feasibility study - Chan, Kuai Son (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

E2S Enso entertainment strategies a business plan - Steinen, Jesko von den (University of Saint Joseph, 2016)
Keywords: Business planning; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Ear traning and the improvement intonation for the choir - Lam, Iok Teng (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Choral Conducting (MCC); University of Saint Joseph

Early career promotions in hospitality - Phinn, Kan Yean (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Early Notices Regarding Creole Portuguese in Former Portuguese Timor - Baxter, Alan N.; Cardoso, Hugo C. (Journal of Language Contact, 2017)

Ecological modulation of reproductive behaviour in the peacock blenny: a mini-review - Saraiva, J. L.; Gonçalves, David; Oliveira, R. F. (Fish Physiology and Biochemistry, 2013)

Editorial - Castro, Maria Guilhermina; Palinhos, Jorge; Ribas, Daniel; Caires, Carlos Sena (Journal of Science and Technology of the Arts, 2017)

Education and human capital management in a world city: the case of Singapore - Ho, K. C.; Ge, Yun (Asia Pacific Journal of Education, 2011)
There is considerable evidence to suggest that the human capital needs of the world city differ from what Robinson calls “ordinary cities” or what Markusen and associates term as “second tier cities”. This path is blazed most notably in the field of world cities and the flow of skilled labour, in the work by Sassen and with case examples (finance, law, accountancy) provided in the work by Beaverstock and his associates. This focuses on producer services and migration flows needs to be matched by an accompanying look at city-based strategies. This paper represents an attempt to provide this by providing a case history analysis of Singapore in three stages of growth – as port city, industrial city and as world city – in order to show how the evolving infrastructure associated with human capital (education, immigration and labour policies) allows human capital to be developed, attracted, harnessed, deployed, released and retained.
Keywords: Singapore; human capital; migration

Education for justice-oriented and participatory citizenship in a politicized era in Hong Kong. (Handbook of Research on Education for Participative Citizenship and Global Prosperity, 2018)

Education in Religious Freedom - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2016)
The author emphasizes the crucial relevance of religious liberty and freedom of expression for a harmonious and peaceful development of modern societies. He follows the prophetic Declaration of Religious Freedom of Second Vatican Council (1965) with its constitutional limitation of governmental powers in matters of religion. The high value of religious freedom is judged as bulwark of all human rights and true capstone of sound human and societal developments, which have to be guarded against any form of infringements. In this regard, a reasonable education in religious freedom and liberty is indispensable for young people of the twenty-first century. Education in religious freedom in the context of moral and religious formation is based on the dignity of every human person and promotes a deeper mutual and cultural understanding by respecting the conscience of every human person. It thus carries the potential to diminish conflicts and clashes in a sustainable way. Educational reforms in countries have to include the high value of religious liberty and freedom as a main element and condition for human dignity and a peaceful global development.

Education in Religious Freedom: Path to Peace and Stability - Gassner, Franz (Orientis Aura, 2016)

Educational leadership practices in East Timor Catholic schools: a case study - Gusmão, Domingos (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Educational technology and the learning of history in a middle school in Macao - Lai, Su Kei (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Effectiveness of mind over old-age depression (mood) programme for older persons in Macau - Lam, Chao Ut (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Effects of family closeness and conflict on young adults' peer relationships - Chan, Mei Kei (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Effects of parenting styles, parent expectations, and academic results on Macau adolescent's self-esteem - Mak, Chi Kwan (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Effects of students' perception of intelligence on English language learning: a case study in Macau - Dvorska, Jana (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Efficient isolation of polymorphic microsatellites from high-throughput sequence data based on number of repeats - Cardoso, Sara D.; Gonçalves, David; Robalo, Joana I.; Almada, Vitor C.; Canário, Adelino V.M.; Oliveira, Rui F. (Marine Genomics, 2013)

Emotional expressoins In Palestrina's Motets - Tsoi, Yuen Yan (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Choral Conducting (MCC); University of Saint Joseph

Employee climate survey of Zhuhai Zhongfu Enterprise Ltd. Co - Liu, Yan Mei (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Employee engagement at the BMW Concessionaires (Macau) Ltd - Gabriel, Eurico (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Employee turnover after company merger: A case in Macao - Cheong, Lien Hon (University of Saint Joseph, 2013)
Keywords: Employees; Theses and Dissertations Master of Business Administration (MBA); Turnover; University of Saint Joseph

Employee turnover and retention in hospitality industry: an exploratory study in Macau - Nantes, Belinda Fatima (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Employees’ Dissonance in non-gaming industries A Casino Dominant Econom - Kuok, A.C.H. (2016 Global Conference of Education and Psychology, 2016)

Endogenous fragmented technology and optimal offshoring in large civil aircraft production - Lei, Weng Chi (The 9th Annual Conference of the Asia-Pacific Economic Association, 2013)
This paper is motivated by two observations in the large civil aircraft (LCA) industry. (1) Boeing and Airbus are significantly different in the degree of offshoring. (2) The degree of offshoring also changes among different aircraft models. To offer an explanation, this paper focuses on issues related to fragmentation. Existing literature has established the tie between fragmented technology and offshoring. However, it is assumed that production can be fragmented readily and at no cost; and only exogenous global economic factors have impact on the degree of fragmentation. This model distinguishes itself from others by incorporating endogeneity in fragmentation. A final-good firm can spend on R&D specifically for its own fragmented technology. As a result, the final-good firm can optimally choose the portion of components to be offshored. A strategic trade policy model is used to show that the degree of offshoring depends on the firm's own cost of production, the host country's cost of production, the global state of technology as well as the government trade policies. In particular, export subsidy and subsidy on R&D of fragmented technology are shown to be policy substitutes. Keywords: Fragmentation; Offshoring; Outsourcing; Aircraft; Export subsidy; R&D subsidy; Boeing; Airbus JEL classification: F12; F13; F23; L13

Engaging: Creative Placemaking in Macau and Hong Kong - Mendes, Carla de Utra; Simões, José Manuel (Individual, Community & Society: Conflict, Resolution & Synergy, 2014)
Nowadays, contemporary art practices have been expanding into fields outside their own borders. According to Claire Bishop (2012), this expanded field of post-studio practices currently goes under a variety of names: socially engaged art, community-based art, experimental communities, dialogic art, littoral art, interventionist art, participatory art, collaborative art, contextual art and (most recently) social practice. By engaging, artists nurture the sense of belonging and search for an identity of the place they inhabit. In Hong Kong and Macao, as well as in the Pearl River Delta and China in general, the speed of urban transformation is forcing artists to reconsider their participation in the city in order to develop a creative place making process that is according to the new identity of the place. By doing so, they are also included in what has been defined as “creative industries” that tries to build a new image of the urban fabric. Linked with this sort of collective attitude, there is also an attempt to find a sense of local identity that has been disappearing in the face of these major developments. Engaging with the city and the communities may constitute, therefore, a challenge for the young generation, especially in hybrid places such as Hong Kong and Macao, where artists find themselves in an effort to understand the core values of their fragmented identity. In this paper we will analyze some projects that artists are doing in both SAR´s, in order to create a sense of place in this state of transition.

Engaging School Students with Tangible Devices: Pilot Project with .NET Gadgeteer - Thota, Neena; Estadieu, Gerald; Ferrao, Antonio; Meng, Wong Kai (2015 International Conference on Learning and Teaching in Computing and Engineering (LaTiCE), 2015)

English as a foreign language: a comprehensive study on teacher's self-efficacy and its antecedents in Macao - Lam, Man Ieng; Malungu, Laurie Baker; Negreiros, João Garrott Marques (University of Saint Joseph, 2019)
As societies globalize, mastery of a second or multiple languages has become an important index to enhance interaction in the society. In that English is a is a widely used medium of communication globally for engagement in international business, commerce, science, technology and governance, the benefits of an efficacious English language teaching force to facilitate the English acquisition process of students in classrooms around the world is highly valued. For the purpose of this study, the English language teacher efficacy instrument (ELTEI) was adapted to the local context to measure the professional efficacy of the English as a foreign language (EFL) teacher participants. The objective of the research was to investigate the degree of relationship between antecedent conditions and specific teacher efficacy in Macao. A mixed-method approach in a sequential phase design was adopted to explore the efficacy of English language teachers serving Chinese medium schools in a non-English speaking region in Asia. Phase-one employed a qualitative approach to contextualize the measurement instrument and to ascertain important characteristics of the target population. Phase-two ensured a quantitative approach to yield understanding regarding the influence of key antecedent conditions on the efficacy of English language teachers in Macao. As evidenced through multiple linear regressions and structural equation modeling, openness, neuroticism, and perceived school support were significant predictors for teacher’s self-efficacy in English teaching. Recommendations for the school management to enhance and sustain the efficacy of EFL teachers in Macao were discussed
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

English learning strategies and strategy instruction: a mixed methods study of EFL students in higher education - Chan, Mei Lan (University of Saint Joseph, 2015)
This thesis investigates the Language Learning Strategies (LLS) used by English as a Foreign Language (EFL) nursing students of higher education in Macao and the effectiveness related to students’ learning outcomes by Strategy Instruction (SI). To date there has been no literature in the area of SI among the Macao Chinese EFL higher education students on teaching all LLS groups, and on four main English skills to look at its effects on learning processes and outcomes at the same time, and this study starts to fill the gap. The research uses an embedded mixed methods research design in phase one and an embedded mixed methods quasi-experimental design in phase two. Phase one aimed to identify students’ LLS use. The findings revealed that students’ cognitive, metacognitive and compensatory strategies were used more than affective, memory-related and social strategies, and overall they used a medium to low level of LLS. In phase two, the effects of SI on students’ changes of LLS use, their proficiency and English learning processes were identified. After SI, students used LLS both more widely and frequently in all four main English skills. Most students’ motivation and self-confidence were enhanced. After SI the affective group of strategies in the treatment group statistically significantly improved, with a moderate effect size, from that of the comparison group. It was found that the widely used Strategy Inventory for Language Learning questionnaires by Oxford (1989c) had limited statistical power and some conceptual confusion. Recommendations are made for policy and practice of EFL instruction
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

Enhancing Educational Collaborations between China and SIngapore - Saw, Swee-Hock; Ge, Yun (Advancing Singapore-China Economic Relations, 2014)

Ensino-aprendizagem da matemática: que lugar a mitos? que lugar a Macau? - Oliveira, Maria de Fátima Andrade de (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Entre a tradição e a modernidade, os Potiguara. Estudo etno-histórico, narrativas de memórias e rituais, a revisitação e o turismo - Simões, José Manuel (História, histórias, 2017)
Keywords: transformações

Environmental characterization of 4,4′-dichlorobenzophenone in surface waters from Macao and Hong Kong coastal areas (Pearl River Delta) and its toxicity on two biological models: Artemia salina and Daphnia magna - Ivorra, Lucia; Cardoso, Patricia G.; Chan, Shek Kiu; Tagulao, Karen; Cruzeiro, Catarina (Ecotoxicology and Environmental Safety, 2019)

Environmental Contamination by Microplastics in Macao: Contribution of Personal Care Products - Sam, Pui Wai (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Environmental Legacy of the Genocide: An Exploration into the Contamination Potential of Mass Grave Soils in Post-Genocide Rwanda - Amuno, Solomon; Tran, Emilie (University of Saint Joseph, 2013)
Keywords: Environmental; Genocide; Legacy; Rwanda

Environmental Urban Design and Planning Rules and their Impact on Street Spaces in Hong Kong and Macau - Tieben, Hendrik; Chu, Joanna; Soares, Nuno; Yiu, Edward (8th Conference of the International Forum on Urbanism (IFoU), 2015)

Espaço, história e memória: os potiguara na paraíba - Simoes, José Manuel (Sæculum – Revista de História, 2016)
últimos assumidos remanescentes provavelmente de um território cultural antes bem mais vasto vivem atualmente nos municípios de Baía da Traição, Marcação e Rio Tinto, no litoral setentrional da Paraíba - nem sobre s seus espaços, culturas e gentes. É preciso dobrar a primeira metade do século XX para se encontrar nos títulos gerais de histórias da Paraíba alguma atenção pelos Potiguara e a sua movimentação histórica no processo longo e contraditório de formação da capitania e da instalação portuguesa na região, enfrentando primeiro a concorrência comercial e militar francesa, depois no século XVII a ocupação holandesa e sempre, até quase meados de seiscentos, a oposição muitas vezes feroz e brutal de vários grupos e milícias potiguaras. A arqueologia confirma um processo recente de formação histórica dos espaços atualmente reivindicados como originais e tradicionais pelos Potiguara. Os estudos linguísticos disponíveis sobre os Potiguara também não destacam a memória rigorosa de um espaço cultural arcano e pré-colonial. Os espaços Potiguara de hoje com este sistema de organização agrícola quase binário são tudo menos naturais. Trata-se, antes, de um espaço em recorrentes transformações históricas, demográficas, económicas e sociais que desafia qualquer ideia de um espaço ‘natural’, ‘original’ ou ‘essencial’ dos Potiguara. Seja como for, estas polarizações estruturais são historicamente aquelas que presidiram à exata produção dos espaços que atualmente os Potiguara apresentam como seus, originais, antigos e tradicionais seguindo, afinal, um modelo colonial de ocupação de espaços e especialização das gentes do Brasil.
Keywords: História colonial

Etnografia, lugares da memória e o discurso dos poderes na aldeia dos índios potiguara - Simões, José Manuel (e-hum, 2013)
eoi/doi Deposit-Electronic Object Identifierhttp://eoi.citefactor.org/10.11248/ehum.v6i2.1385RESUMO: A aldeia dos índios Potiguara não é somente um aglomerado de casas e pessoas. Trata-se de um espaço social muito mais complexo, somando ao habitat modelos de parentesco, cruzando práticas culturais e economicas, juntando aos humanos bichos e plantas, rotinas de trabalhos e “libertações” de lazeres. A aldeia Potiguara embora se apresente como singular, ela comunicava e continua a comunicar hoje com redes mais amplas de aldeias rurais e indígenas, gerando transformações culturais e sociais profundas. Embora as alterações marquem as mudanças nos habitos da aldeia Potiguara acredita-se que as práticas culturais que se estendem das festas ao turismo das suas aldeias são tão tradicionais como singulares.PALAVRAS-CHAVES: Aldeia indígena – Espaço social – Práticas culturais – TransformaçõesABSTRACT:The village of Potiguara Indians is not only a cluster of houses and people. This is a social space much more complex, adding to habitat kinship models, crossing cultural and economic practices, joining human animals and plants, work routines and "releases" of leisure.The Potiguara village despite presenting as singular, she communicated and continues to communicate today with wider networks of rural and indigenous villages, generating deep cultural and social transformations. Although the changes mark the changes in the habits of the village Potiguara is believed that cultural practices that extend parties to tourism from their villages are so traditional and unique.KEYWORDS: Indian Village - social area - Cultural practices - TransformationsRecebido: 31/08/2014    Aceito: 01/10/2014
Keywords: Aldeia indígena; Espaço social; Práticas culturais; Transformações

Evaluating a Japanese language teaching strategy that comprises a video component - Pun, Oi Ian (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Evaluating an Enterprise Content Management for the Macao Government Agency - Pong, F.; Whitfield, R.; Negreiros, J. (Springer, 2011)
Information contained within documents is an essential ingredient of any office operation. A content management application (CMA) is an organization plan for the conception, use, retention, disposal and selective preservation of its data. Using an appropriate CMA framework can greatly help Macao Government agencies, for instance, that are increasingly using electronic means to create, exchange and store a major variety of records daily. By definition, a record is information, in whatever form, for government functions, activities, decisions and other important transactions. As expected, as the volume of electronic information increases, so does the complexity of managing electronic records. This project goal was to evaluate the software capabilities of the Alfresco© Enterprise Content Management (ECM) against a set of functional requirements, aimed by the Macao Government agency. Drawing on the results of this evaluation, the present analysis concludes that Alfresco© ECM is capable of supporting an entire agency needs related to the management of its records content.
Keywords: Alfresco©; Enterprise Content Management; Macao Government; Open Source Software

Evaluating Mathematical Models for Morphological Classification of the QRS Complex - Do Vale Madeiro, J.P.; Barreto, D.; Marques, J.A.L.; Salinet, J.L. (Computing in Cardiology, 2019)

Evaluating the comments & complaints from Japanese guests and mainland Chinese guests in hotel Okura Macau - Lau, Fong Peng (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Evaluating the relationship of Filipino domestic helpers and their employers: towards improving inter-cultural community development in Macao - Lok, Weng I. (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Evaluation of Bally Technology Limited - Lao, Sio Mei (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Evaluation of Deterministic Spatial Interpolators with myGeoffice©: The Utah Grasshoppers Case - Negreiros, Joao; Phillips, Jenny O. L. (International Journal of Geology, Agriculture and Environmental Sciences, 2018)
The knowledge of spatial distribution of grasshoppers can be very relevant for agricultural planning purposes. On the other hand, the comparison of spatial interpolators for efficiency and reliability reasons is also a key factor to understand interpolation maps outcomes (versus reality). At last, but not least, the use of open Web geographical tools to disseminate true spatial inferential methods to address spatial issues is still quite limited (if none) in high schools and universities, particularly in Geography subjects. If the latter can be addressed with myGeoffice©, the first issue will use the Utah, USA, dataset (58 samples) to layout the spatial distribution of grasshoppers and understand the counties that are more pro to this kind of agriculture infestation. Inverse Distance Weighted (IDW), Moving Average (MA), Multi-quadratic, Inverse Multi-quadratic and Nearest Neighbor (NN) will produce interpolated surfaces of grasshopper’s properties. Efficiency of spatial interpolators was assessed in this writing based on the prediction error’s statistics derived from the difference between the estimation and the real samples on a cross-validation procedure. Remarkably, results show that NN was the most accurate one when compared with the remaining deterministic approaches at sample’s locations.

Examining the efficacy of outdoor education camp in enhancing middle school students' self-esteem - Chan, Chi Hong (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Examining the Factor Structure of the Victorian Gambling Screen in Chinese Casino Workers. - Mordeno, I.G.; Nalipay, M.J.N.; Coteriano, C.; Leong, S.U. (Current Psychology, 2017)

Explanatory study of management style changes in the Philippines - Lam, Sok Chan (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploration of consumer behavior on luxury goods in Macau - Chan, Chi Cheng (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study of management change in Egypt - Chan, Wai Kei (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study of management style change in France - Ng, Sut Fan (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study of management style change in Laos - Xian, Jia Xing (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study of management transition in South Korea - Chan, Wai Ip (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study of management transition in the United States - Choi, Hoi Lam (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study on inns and guest houses in Macao: propose monitoring system and regulatory policy - Lai, Weng Lou (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Exploratory study on perceptions of young adults about speed dating service in Macao - Kuong, Weng Man (University of Saint Joseph, 2015)
Keywords: Dating services; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Young adults

Exploratory study on the turnover of direct sellers in Macao: the case of NuSkin Macao - Tang, Weng In (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploring attitudes concerning family size in Macau: a qualitative study - Ho, Nga Si (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Exploring fashion trends with internet blogs: an application to Design Esta Studio - Ng, Ian Io (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploring occupational stress and job satisfaction among pharmacists in Macau - Ho, Joel (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Exploring service quality in luxury retail in Macau - Mui, Wing Yan (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploring the Development of Contemporary Hospice Care Orientation in the Light of a Confucian View of Life and Death - Liu, Weifeng (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations PhD in Religious Studies (D-RS); University of Saint Joseph

Exploring the dynamics of students with social anxiety through multiple case studies: a proposed intervention program - Cabral, Olga Tsvirkun De Freitas (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Exploring the quality of life of Macau people with visual impairment - Wong, Ka Meng (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Exploring the role of vocational education in promoting the diversification of Macao's industry: a study of the cultural and creative industries - Ngai, Hio Peng (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Exploring the therapeutic value of dancing among the selected Chinese women in Macau - Rosario, Elzira Jonas Do (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Export performance: management competency in the use of information and strategy development - Nwachukwu, Francis (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Extending social networking into the secondary education sector - Kio, Su Iong (British Journal of Educational Technology, 2016)
Secondary schools do not have the same technical resources and capabilities as universities. They usually need to rely on ready-to-use tools to fulfill their information and communication technology (ICT) structure. Social networking site (SNS) has emerged as a practical solution to this need. However, few have collected empirical data on the application of SNS in a secondary school setting. This paper probes into the current condition of SNS usage among secondary school students using a sample of 851 students in Macau, a Special Administrative Region (SAR) of China. Data in terms of access, profile and activities are collected. The activities on SNSs are analyzed by regression techniques to produce a prediction model relating perceived academic benefit and SNS activities. The model yields a strong positive relationship between that benefit and activities such as raising questions and engaging in study-related discussions. The model also yields a weak dependency on activities such as searching for information and entertainment. The paper also evaluates the actual academic utilization of a Facebook Group for one class of secondary school students for a period of one year. At the end of the year, various opinion parameters are measured, and improvements are observed in most parameters.

Facebook as an Informal Learning Space Channel: The São José, Macao Cases - Kio, Su Long; Negreiros, Joao (2013 Learning and Teaching in Computing and Engineering, 2013)
Broadly, on-line communication platforms are online resources that allow the exchange of information using the Internet. They include Email, Instant Messaging, Online Open Forums, Online Blogging and Social Networking Sites. All these platforms have their own specialties and properties. In education, there are great advantages for high-schools to utilize these online communication platforms, especially Online Open Forums and Social Networking Sites. Communication is the backbone of education. Everything from classroom teaching to school policy making depends on effective communication [1]. With these new communication platforms at hand, schools can develop more adaptable and friendly channels among students, teachers and management (only the first two interveners are covered under this study). Various components of the schools will essentially work together in a more collaborative and regenerative way [2]. This research paper analyses how online communication platforms are changing the internal nature of education. It takes sample populations from two schools in Macao (Pre-University of the University of Saint Joseph, USJ, and Colégio Diocesano de São José, CDSJ) with different backgrounds such as medium of language, level of degree, professor's background and style of teaching. Teachers of these schools are communicated first for their opinion on key elements to improve learning with online communication platforms. These factors are implemented in a platform such as Social Networking Sites. As expected, students are instructed to utilize this platform (Facebook) to enhance their learning practice and experience. The result of this utilization is assessed in terms of student opinions and feedback.
Keywords: Educational institutions; Electronic mail; Facebook; Internet; Macao; Visualization; communication; incidental education; social networking sites

Family constellations: a systematic review and a critical analysis - Kuan, Man Sok (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Fashion design in Macau: the local government's role in the development of culture and creative industries - Lo, Nei Ian (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Fashion education and the fashion industry in Macau linked through an NGO - Chan, Victoria Alexa Kuan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Fast Cluster-learning with Prior Probability from Big Dataset - Li, Tengyue; Fong, Simon; Lobo Marques, Joao Alexandre; Wong, Raymond K. (2018 5th International Conference on Soft Computing & Machine Intelligence (ISCMI), 2018)
Association Rule Mining by Aprior method has been one of the popular data mining techniques for decades, where knowledge in the form of item-association rules is harvested from a dataset. The quality of item-association rules nevertheless depends on the concentration of frequent items from the input dataset. When the dataset becomes large, the items are scattered far apart. It is known from previous literature that clustering helps produce some data groups which are concentrated with frequent items. Among all the data clusters generated by a clustering algorithm, there must be one or more clusters which contain suitable and frequent items. In turn, the association rules that are mined from such clusters would be assured of better qualities in terms of high confidence than those mined from the whole dataset. However, it is not known in advance which cluster is the suitable one until all the clusters are tried by association rule mining. It is time consuming if they were to be tested by brute-force. In this paper, a statistical property called prior probability is investigated with respect to selecting the best out of many clusters by a clustering algorithm as a pre-processing step before association rule mining. Experiment results indicate that there is correlation between prior probability of the best cluster and the relatively high quality of association rules generated from that cluster. The results are significant as it is possible to know which cluster should be best used for association rule mining instead of testing them all out exhaustively.
Keywords: Association Rule Mining; Big Data; Clustering; Clustering algorithms; Data mining; Itemsets; Preprocessing; Prior Probability; Probabilistic logic; Probability distribution

Feasibility Analysis For an Academic Incubator at USJ - Cheong, Ieng (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Feasibility analysis of operating the third wave speciality coffee Business in Macau - Wong, Ka Long (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Feasibility analysis: Upper Floor Store and/or alternative locations for business operation in Macao - U, Hio Tong (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Feasibility study for a movie production setting in Macau - Tam, Pek Kei (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Feasibility study into implementation of automated traffic lights to improve emergency vehicle response time in Macau - Chong, Kirl Cheah (University of Saint Joseph, 2016)
Keywords: Emergency vehicles; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Feasibility study of a digital gourmet marketplace in Hong Kong - Farinha, João Pedro (University of Saint Joseph, 2016)
Keywords: Google; Hong Kong; Marketplaces; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Feasibility study of a living lab in Macau for the creative industries - Tong, Pui Si (University of Saint Joseph, 2016)
Keywords: Creative ability in business; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Fernand Braudel and China - Lau, Nga Lai (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Festas e lugares da memória dos índios Potiguara – a invenção das tradições locais - Simoes, José Manuel (Tokyo University of Foreign Studies, 2015)

FIGHT – Hormonal, pheromonal and genomic regulation of aggression in a fish model - Gonçalves, David (University of Saint Joseph, 2018)

Financial challenges of small medium emterprises in China - Fok, Gerald (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial flows and currency exchange in Mainland China in the foreign investor perspective - Rodrigues, Nuno Miguel Vieira (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of AT&T Inc - Lam, Ut Wa (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of avon products,inc - Kiki, Michael Oluwasegun (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Campbell Soup Company - Wong, Chong Weng (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of FedEx corporation - Olalekan, Adebiyi (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Galaxy Entertainment Group (GEG) - Ieong, Si Wan (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Harley-Davidson, Inc - Sou, Heng Fu (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Hyatt Hotels Corporation - Lam, I. Leng (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Kelloge company - Kuan, Wai Si (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Kraft foods company - Kuan, Man Chon (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Las Vegas Sands Corp - Gomes, Sérgio (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial Valuation of Nike - Cheong, Hio Fong (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Novartis International AG - Pires, Dora Marques (University of Saint Joseph, 2017)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Oracle Corporation - Monteiro, Amilcar Samora Rodrigues Rendall (University of Saint Joseph, 2017)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Pfizer Inc - Pires, Rui Carlos Moreno (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Shun Tak Holdings - Magalhães, João Pinto de (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Tencent - Sou, Fai Wong (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of the Hershery Company - Ho, Weng Kam (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Tiffany & Co - Chu, Choi Peng (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Wabtec Corporation - Pereira, Marcos da Silva (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial Worldwide Crisis: The Anti-Counter Cycle of Australia - Pou, Boey Tang; Trimarchi, Michael; Negreiros, Joao (Journal of the Faculty of Economics and Administrative Sciences, Çankırı Karatekin University, 2013)
If Australia has been subject to major influences by the United States and European countries, why is its economy healthier than their counter partners? What are the economic foundations that underline this anti-counter cycle of financial worldwide crisis from Australia? What are some of the lessons that countries from Europe that have not fared during the current financial worldwide crisis should learn from Australia? The purpose of this paper is to review the present Australian management system. Four changes are identified including embracement of corporate governance, a shift to adopt more R&D activities, a shift to adopt environmental sustainability practices and emerging corporate social responsibility. On the conclusions settings, a recap and recommendation on how Portugal, a member of the PIGS (Portugal, Italy, Greece and Spain) Southern European Countries club forgot to embrace directives that have been applied in Australia, to avoid the actual financial and identity crisis.

Fish Sounds and Mate Choice - Amorim, M. Clara P.; Vasconcelos, Raquel O.; Fonseca, Paulo J. (Sound Communication in Fishes, 2015)
Fish acoustic signals associated with mating behaviour are typically low-frequency sounds produced by males when in close proximity to females. However, some species make sounds that serve the function and follow the design of advertisement calls, well known in insects, anurans, and birds. Close-range courtship acoustic signals may be used by females in mate assessment as they contain information of male quality such as size and condition. For example, sound-dominant frequency, amplitude, and fatigue resistance may signal body size whereas pulse period (i.e. muscle contraction rate) and calling activity are related with body condition in some species. Some signal features, such as sound pulse number, may carry multiple messages including size and condition. Playback experiments on mate choice of a restricted number of species suggest that females prefer vocal to silent males and may use sound frequency, amplitude, and mainly calling rateCalling ratewhen assessing males. The assessment of males by females becomes more challenging when males engage in choruses or when sounds are otherwise masked by anthropogenic noise but almost nothing is known about how these aspects affect mating decisions and fish reproductive success.
Keywords: Acoustic communication; Anthropogenic noise; Calling activity; Chorus; Fish; Mate choice; Reproductive success

Food safety in Macao :a review of the Civic and Municipal Affairs Bureau's Food Safety Centre - Lou, Kai Yin (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Foreign workers in Macau - Wong, Kit Weng (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Francisca Diniz - Morais, Isabel (Feminist Writings from Ancient Times to the Modern World: A Global Sourcebook and History [2 volumes], 2011)
Collecting more than 200 sources in the global history of feminism, this anthology supplies an insightful record of the resistance to patriarchy throughout human history and around the world.From writings by Enheduana in ancient Mesopotamia (2350 BCE) to the present-day manifesto of the Association of Women for Action and Research in Singapore, Feminist Writings from Ancient Times to the Modern World: A Global Sourcebook and History excerpts more than 200 feminist primary source documents from Africa to the Americas to Australia.Serving to depict "feminism" as much broader—and older—than simply the modern struggle for political rights and equality, this two-volume work provides a more comprehensive and varied record of women's resistance cross-culturally and throughout history. The author's goal is to showcase a wide range of writers, thinkers, and organizations in order to document how resistance to patriarchy has been at the center of social, political, and intellectual history since the infancy of human civilization. This work addresses feminist ideas expressed privately through poetry, letters, and autobiographies, as well as the public and political aspects of women's rights movements.More than 200 chronologically arranged entries on feminist writers, thinkers, and organizations across 4,000 years of human historyContributions from more than 100 international scholars, including historians, sociologists, literary, cultural theorists, religious scholars, writers, and activistsBrief bibliographies of further readings, websites, and other relevant resources with each entryLists of entries arranged by region as well as by broad topic, in addition to a comprehensive index
Keywords: Social Science / Ethnic Studies / General; Social Science / Feminism & Feminist Theory

From digital to Facebook divide: social capital benefits for Facebook immigrant - Yung, Chun Sing (University of Saint Joseph, 2018)
Two billion users make Facebook of academic interest. This thesis creates a Facebook Divide Index, the delineated categories of Facebook Native, Facebook Immigrant, and Facebook Isolate, and develops Facebook inequality concepts. Macau has a fast- growing number of Facebook Immigrants who benefit from using the online social network. Data from participation-observation and surveys demonstrate social capital gain by Facebook Immigrants, with older generation Facebook users relatively happier than their younger counterparts. The thesis concludes that society needs to equip and empower the older generation or Facebook Isolates, so that they can benefit from online social network usage
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

Gambling motivation, gambling behaviors, alcohol use and substance abuse among Macau casino workers - Coteriano, Carla (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Gastronomy as a sub-sector of the creative industries: the case study of Macau - De Sousa, Carlos Humberto (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Gender differences in self-reported depression: an examination of gender bias, social desirability and stereotype threat - Ng, Lai Va (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Gender, sibling position and parental expectations: A study of Chinese college students - Found, Andrew; Sam, David (Journal of Family Studies, 2013)
Differences in parental expectations related to cultural background, gender and sibling position were investigated among Chinese college students in Macau. Three-hundred and forty-four Chinese college students completed a questionnaire which included measures of parental expectations and psychological distress, as well as information about their gender, cultural background (Mainland China or Macau) and sibling position. Participants born in mainland China reported significantly higher perceived parental expectations (PPE) compared with students from Macau. Contrary to predictions, there was no evidence of a difference in PPE in relation to gender or being the first-born sibling. These findings are discussed in terms of changes in family values and parental attitudes within Chinese society over the past few decades.
Keywords: Chinese; gender; parenting; siblings; students

General affective dispositions on academic emotions: exploring the general and specific dimensions of emontions as determinants of students' emotional experiences - Oberhauser, Petra (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Geochemistry and stable isotope constraints on high-temperature activity from sediment cores of the Saldanha hydrothermal field - Dias, Ágata; Früh-Green, G.L.; Bernasconi, S.M.; Barriga, F.J.A.S. (Marine Geology, 2011)

Geochemistry of Fe-Si-(Mn) Chimneys from Luso Vent Field, MAR - Dias, Ágata; Costa, P; Marques, A F; Ribeiro, L; Madureira, P; Calado, A; Gonçalves, E; Morato, T (Goldschmidt, 2019)

Geochronological, geochemical and petrographic constraints on incremental pluton growth: the case of Macao granitic suite - Dias, Ágata; Quelhas, P; Mata, J; Wayne, Davis (Goldschmidt, 2019)

German restaurant adoption in Macau - Loi, Sio Mei (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Globalization, Communication, Information and Cohabitation - Simoes, José Manuel (8th Annual Conference of the Chinese Association of Global Communication, 2015)

Going green in Sands Cotai Central Macau - Chao, Wai Chong (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

"Going through the mist": early career transitions of Chinese Millennial returnees - Porschitz, Emily T.; Guo, Chun; Alves, José (Managing the New Workforce, 2012)

Gosto de matemática, mas... prefiro estudar direito: compreender a resistência das estudantes às áreas stem - Fernandes, Clara Isabel Raimundo (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Government policy coping with human resources management in the Venetian Macao Resort Hotel - Che, Man San (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Grade retention in Macau: Teachers' beliefs and attitudes. - Tchiang, Isabel; Monteiro, Elisa; Lopes, Carlos; Found, Andrew (University of Saint Joseph, 2017)

Gratitude interventions: the person-activity fit dimension - Todd, Philip (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

GROKYA: a privacy-friendly framework for ubiquitous computer - Farinha, Daniel Filipe G. (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Information Technology (MIT); University of Saint Joseph

Guangzhou Places: Density Series: Urban Screening - de Lancastre Jedenov, Kirill; Ward, Devon; Afonso, Filipe (Australian Institute of Architects, 2019)
Colloquially, Guangzhou is known as the ‘Factory of China’,and, in many respects, it may be one of the great factories of the world. Located in the Guangdong Province in Southern China, Guangzhou is an exemplar of twenty-first century metropolis. It is home to over 14 million residents and is in a state of extreme growth. Old farmlands encircling the city are incentivised, through government subsidies, to build apartment complexes that can accommodate the rapid growth as the city develops. The city is home to migrant population—from the rural areas of China that is larger than the entire population of Perth. The middle classin Guangzhou is outpacing the growth of middle classes in Australia and the US. Factories, shipping ports, apartment blocks, malls, and urban farms are mixed in a tightly knit tapestry across the city. ‘Guangzhou Places’ is a series of short videos that present viewers with a glimpse of urbanisation that is akin to app development. Guangzhou is a ‘beta city’, an environment
Keywords: Architecture; Density; Guangzhou; Places

Guidelines for an Oriented Organic Waste Valorization Strategy for Macao - Lei, Man Sao (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Hacking: Toward a Creative Methodology for Cultural Institutions - Estadieu, G; Caires, C. S (2018)

Heading for success in government services: a case study on the administrative and human resouces policies of the DSI - Lei, Ming Kei (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Heading for success in government services: a work report on the "Performance Pledge" program and the services of the Macao Immigration Department - Ling, Sio Kuan (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Healthcare governance coping with globalization: a work report on the administrative policy of the CHCSJ Hospital and Macao Health Bureau - Rosario, Anabela Luiza do (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Henrietta Hall Shuck: Engendering Faith, Education, and Culture in Nineteenth-century Macao - Morais, Isabel (Americans and Macao: Trade, Smuggling, and Diplomacy on the South China Coast, 2012)
Chapter 7 Henrietta Hall Shuck Engendering Faith, Education, and Culture in Nineteenth-Century Macao Isabel Morais Introduction Henrietta Hall Shuck (1817–1844) is famous for being the first American female missionary in China. Despite her short period of residence in Macao in the early nineteenth century, her multiple experiences in the Portuguese colony are invaluable. Her pronouncements in her journal entries, correspondences and other writings make clear her perceptions of Christian interaction with the Chinese people. Her writings combine strong religious beliefs with an equally powerful commitment to promote gender equality through education . Excerpts from her journal openly address female child slavery, the mui tsai system (little girls sold as household servants and for prostitution), gender-based class hierarchies, and the exploitation of women and children. Henrietta helped establish the first Chinese girls’ school in Macao and promoted other important factors through her writing such as the “Camões’s Garden and Grotto” and her discussion of The Lusiad. Had Henrietta Hall not come to China, I might not be here today.1 The first four decades of the nineteenth century were critical years in the Pearl River Delta and Macao. Many examples show Chinese tightening political control over Macao and increased opposition to British incursions.2 In Portugal, several reforms aimed at reinforcing state control of the administrative, political, military, and economic colonial organizations were implemented and extended to Macao.3 In 1835, the governor of Macao ordered that Portuguese who were born in Macao or who had lived in Macao for a long time, be 106 Isabel Morais restricted to municipal affairs only and thereby reducing the political autonomy of the local elites.4 Meanwhile, other important legislation was also extended to Macao. A law passed in 1834 called for the dissolution of all religious orders and congregations, and the abolition of slavery in every Portuguese territory in 1836. These initiatives weakened the Catholic Church’s role in the education system since all schools for both Portuguese and Asian converts in Macao were church-affiliated under the Portuguese Padroado (Patronage) system in Asia.5 At the same time, the United States’ maritime expansion and foreign policy in Asia started to assume a more assertive role, promoting American social, political, and liberal ideas. In 1803, the governor of Macao prohibited the consul of the United States from spending the winter in Macao, forcing him to go to Canton.6 Driven by profits from trade, Americans were nonetheless encouraged to continue going to China, and despite restrictions in Macao, they used the city as a base for not only commerce but the promotion of religion as well. This was done despite the opposition of the British East India Company to missionary activity, the Chinese government’s prohibitions of publicly propagating religion and the local Catholic elite’s aversions to non-Catholics in the Portuguese colony.7 According to Reverend John Lewis Shuck, Henrietta’s husband, the Protestant missionaries in Macao were “strictly prohibited by the civil authority any public efforts for the diffusion of the gospel” being limited to personal conversations only.8 The persecution against Protestants in Portugal might have contributed to the intolerance among Roman Catholics in Macao. It is worth mentioning that between 1843 and 1846 around one thousand Jews fled from Portugal to the United States and West Indies (British island of Trinidad). In 1846 more than four hundred Jewish people fled from the Portuguese archipelago of Madeira to Jacksonville and Springfield, in the state of Illinois.9 On the other hand, the immigration of Catholics into the United States, resulted in the so-called “nativist” movement in the 1840s, and the rise of the anti-immigrant Know-Nothing Party of the 1850s.10 For many years Protestant missionaries in China were restricted to Guangzhou (Canton) and Macao. They concentrated on distributing literature among members of the foreign and Chinese merchant class, which gained a few converts. And they laid the foundations for more humanitarian efforts of advancing education in China among the lower classes and providing medical services to the needy. This situation would change after the Opium Wars led to Henrietta Hall Shuck 107 the imposition of treaties, and compelled the Chinese government to allow evangelization and freedom to convert Chinese to Christianity. In the 1830s, North American and British missionaries established bases in Macao to advance their evangelical operations. Amidst the restrictions and constraints of the diplomacy of the Canton system (ca. 1700–1842), which included a ban on foreign women entering China...

High school emergency management in Macao - Marques, David Pinto (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Historical Space in Macao - Pinheiro, Francisco Vizeu (IACM : Jiangnam University, 2016)

Hormones and Sexual Behavior of Teleost Fishes - Gonçalves, David; Oliveira, Rui F. (Hormones and Reproduction of Vertebrates, 2011)

Hotel central, Macau leveraged buyout plan - Real, Sérgio Miguel Anacleto (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Housing (un) affordability in Macau - Tang, Mui Wa (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

How digital transformation could facilitate operational improvements: the case of urban cable car industry - Vodenicarski, Dalibor (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

How older hotels can remain competitive in a booming hotel industry - Chio, Hou Meng (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

How to create and develop a Choir in Chinese christian church of Macau - Chao, Chou (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Choral Conducting (MCC); University of Saint Joseph

Hydrological Risk Assessment at Praia, Cape Verde - Silva, Jose Lino; Negreiros, Joao Garrott Marques (International Journal of Environment, Agriculture and Biotechnology, 2017)
Hydrology modeling became a relevant topic for the Cidade da Praia, Cabo Verde, Africa, due to negative impact risk to local population and its assets. The modeling via Geographical Information Systems (GIS) can help the decision-making process of space occupation and characterization for this type of risk. Under the municipalities of Praia, the phenomenon of flash flood is common, causing soil erosion and landslide. This constitutes a risk for the local habitat, particularly in districts with a lack of strong human infrastructures. To simulate, analyze and generate risk maps using GIS to help this county governance authorities for decision-making, thus, becomes the main aim of this article.

Hydrothermal Fe-Mn deposits from low-temperature systems of the Mid-Atlantic Ridge - Costa, P; Dias, Ágata (InterRidge Workshop on Hydrothermal Ore-forming Processes, 2019)

Illustration of paradigm pluralism in computing education research - Thota, Neena; Berglund, Anders; Clear, Tony (14th Australasian Computing Education Conference, ACE 2012, 2012)
This paper argues for paradigm pluralism in computing education research. The value of mixing paradigms, and the choice of methodological eclecticism and mixed methods is explored using pragmatic knowledge claims. A research study, which focused on the design of an introductory object-oriented programming (OOP) course for undergraduate students, is introduced as an illustration of paradigm pluralism. The study demonstrates methodological eclecticism and use of mixed methods for data collection and analysis. Meaningful outcomes resulting from the choice of the research design are described. A framework that focuses on the research problem and research questions to guide research design is presented as the outcome of the study. Through the discussion and demonstration of paradigm pluralism, this paper contributes to increased awareness of theoretically anchored research in computer science. © 2012, Australian Computer Society, Inc.

Images of Law in Chinese Crime Fiction - Morais, Isabel (2014)
Crime fiction in China emerged in the 1890s in translations of Western works, and evolved from the mere imitation of Western crime fiction to becoming an autonomous literary genre. Despite fluctuations in popularity, the genre of Chinese crime fiction, the plots of which are based on true cases, has retained a reasonably constant presence on the literary scene, and has captured the popular imagination in contemporary China and, more recently, across the world. After the demise of Mao, under whose governance the genre was banned, the government of the early Deng regime began to favor so-called “legal system literature” (fazhi wenxue), and aimed to use it to propagate moral principles and maintain political control in opposition to writers who strived for independence and originality. Since the mid and late 1980s, which were considered the heyday of Chinese crime fiction, and the expansion of the legal system and legal institutions, crime fiction has served to illuminate the role of law and to display new social perceptions. To investigate these attitudes, I focus on works of contemporary Chinese crime fiction by arguing that they are expressions of a confluence of cultural exchange and new trends. Several factors may have contributed to such a change, from the impact of the cinema and television serials in China to the celebrity status of Chinese detectives, lawyers and judges both as crime solvers and writers in the Chinese mainland and amongst the Chinese writing diaspora. An important finding is that besides giving detailed descriptions of legal procedures, all of the works studied have clearly shifted away from the traditional formula of Chinese crime fiction, that is, of the quest of a hero for justice, punishment, and revenge, to focus on the process of solving crime and the rendering of justice through legal processes. It seems that crime fiction is becoming crucial in conveying a new understanding of citizen’s rights in an attempt to fit into ongoing contemporary debates on universalistic notions of justice and the competence of legal institutions to provide justice to increasingly marginalized sectors of contemporary China.

Impact Assessment of the Macao Forum's Seminars (colloquia) on the Economy and Public Policy-Making in Portuguese Speaking Countries - An Illustration of South-South Cooperation - Tran, Émilie (University of Saint Joseph, 2015)

Impact of internet usage, demographic factors, and illusory perched control on pathological gambling, depression, anxiety and stress - Au, Ho Ki (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Impacts of Public Support and Voices Pluralism in Macao Newspapers - Simões, José Manuel; Faustino, Paulo (Journalism and Mass Communication, 2017)

Implement performanace pledge in Macao government departments: a case of Macao IACM - Choi, Kuai Hong (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Implementation of a centralized ERP system for the supply chain department in Melco Crown Entertainment - Fong, Tou Vai (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Implementation of Enterprise Resource Planning for the Supply Chain Management of the Food and Beverage Department at Macao Entertainment Corp - Vai, Fong Tou; Lee, Leanda; Negreiros, Joao (Information Resources Management Journal (IRMJ), 2014)
One of the six gaming concession holders in Macao, Macao Entertainment Corp (MEC)1, undertook to centralize three casino/entertainment properties through utilization of a centralized Enterprise Resource Planning (ERP) in April 2010. The Supply Chain (SC) department was the first to apply the ERP in...

Implementation of item response theory to English grammar assessment to map students' understanding and to foster learning - Ho, U. Kei (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Implementing cross-curricular themes - Morrison, Keith (2018)

Implications of cultural values in retail strategies for the gaming industry: Chinese consumer values in the context of Macau - Barbosa, Hong Seng (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Import and sales of Chinese fabrics in Brazil: a feasibility study - Ribeiro, Lucas Rodrigues Gomes (University of Saint Joseph, 2016)
Keywords: Brazil; China; Textile fabrics; Textile fabrics Markets; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Improvement in English learning by using a systematic learning approach in reading comprehension: a case study in primary school of Macau - Lao, Wai Man (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Improving customer loyalty programs to increase market share - Lei, Sut Na (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Improving social skills of primary school students through a social skill enhancement program - Fok, Ka Ian (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Improving Students' Reading Literacy with the Guided Use of a Digital Reading Platform in a Chinese Primary School - Norte, Patricia Alexandra D. C. (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

In faithfulness to the original inspiration: spirituality of St. Magdalene of Canossa and its implementation in Canosslan education Hong Kong and Macau, 1860-2014 - Leong, Weng Man (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

In search of aesthetic education: Student teachers’ perspective and practice with sensory-based approach in Infant Education (University of Saint Joseph, 2019)

Inclusive education in Macao: Teachers' perceptions and attitudes - Correia, Ana; Teixeira, Vitor; Monteiro, Elisa; Kuok, A. C. H. (University of Saint Joseph, 2017)

Inclusive education in Macau: a dual teacher-parent perspective - Lam, Sao Lan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Influence of Chinese legitimizing discourse on domestic violence in Macau: a preliminary study - Lam, Hang U. (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Influence of management in change readiness maturity of teams in organizations - Reis, Joana Mateus (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Influence of parents and peers on stress and coping in Korean-born adolescents in Macau - Choi, Dong Jin (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Influência da nova estrutura fiscal de impostos de Angola na gestão de escolas privadas do municipio do Lobito - Armando Carlos Hombo Nogueira; Luis Miguel Pacheco; Marcus Antonio Almeida Rodrigues (Revista Gestao em Analise, 2019)

Inquérito aos estudantes da Universidade de São José: o peso da cultura na aprendizagem das línguas - Espadinha, M. A.; Borges, V. (A framework in Portuguese as a Foreign Language for Chinese Native Speakers, 2018)

Inquiry-Based Teaching and Learning as Cross-Cultural Educational Innovation - Pottier, Susan (University of Saint Joseph, 2011)
Inquiry-based Teaching and Learning is fundamental to modern western Science Education. This thesis argues that improving Science Education within a traditional Chinese educational setting can be realized by introducing Inquirybased Learning as a cross-cultural educational innovation - through the agency of a Science Learning Centre (SLC). The thesis evaluates the impact and uptake of the Inquiry-based approach, as seen through SLC activities that foster the professional development of Science teachers, and that build awareness of the approach at the community level. It also examines the process of establishing a SLC, and regional network, in Macau. The conceptual and substantive factors affecting the cross-cultural transfer of an Inquiry-based Teaching and Learning approach and the development of the SLC are explored through the theoretical lenses of Complexity Theory, Innovation and Change Theory; Social Networking Theory; and a range of Curriculum Development Theories. Central to the thesis is the analysis of three Episodes involving Inquiry-based training programmes facilitated by the SLC, and one Account of the development of the SLC itself: a series of Geoscience Inquiry-based learning workshops in Macau and Hong Kong; an invitational international professional development Training Programme provided in York by the National Science Learning Centre in England; an innovative Master’s in Education degree module which involved learning in an unfamiliar context; and finally, the creation of the Macau Science Learning Centre network as an agency for promoting Science Education in Macau. Furthermore, the thesis analyzes the multi-dimensional roles of the writer as participant, co-teacher, co-facilitator, researcher, ethnographer, theorist, and SLC manager. It incorporates aspects of educational innovation and change, teacher professional training, and the development of collaborative social networks. The research makes a unique contribution to the field of Science Education, especially in terms of the transfer and adaptability of an Inquiry-based approach into a traditionally Chinese educational setting through the agency of a SLC
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

Insights for management among non-gaming industries: Employees’ dissonance in a casino dominant economy - Kuok, A.C.H. (Revista de Psicología del Trabajo y de las Organizaciones, 2017)

International Business Ethics: Focus on China - Rothlin, Stephan; McCann, Dennis (Springer-Verlag, 2016)
This book addresses an essential need felt by many who seek to promote best business practices in China and East Asia – namely the need for culturally appropriate instructional materials (basic information, case studies and ethical perspectives) that will allow managers and entrepreneurs to understand and embrace the challenge of moral leadership in business. In an era characterized by globalization and the increasing importance of the economies of China, India, Japan and SE Asia, international business ethics must reflect the concerns of the people living and working in this area, the moral and spiritual traditions that have nurtured them and their specific contributions to sustainable development. This book presents twenty important case studies, taken from newsworthy events of the past few years, in which Asians and others have attempted to respond to this challenge. Each case study has been selected and shaped in order to highlight various aspects of doing business in Asia, starting with basic principles and moving on to the specific responsibilities that businesses have towards their various stakeholders. The authors contend that the best way to appreciate the relevance of Asian moral and spiritual traditions is to determine their specific contribution to virtue ethics, where the ancient traditions of both East and West converge in their focus on the qualities of moral leadership that form the basis of best business practice. Exploring the case studies will enable readers to appreciate the continued relevance of these ethical perspectives in Asian business. Best business practice clearly involves learning to do business and playing the game according to the rules; but the necessity of playing by the rules is not likely to become clear until one takes up the path that leads to a virtuous life in business, developing a moral character chiefly based on integrity.

International Business Ethics. What We Have Learnt by Focusing on China? - Rothlin, Stephan; McCann, Dennis (Eine Wirtschaft, die Leben fördert. Wirtschafts- und unternehmensethische Reflexionen im Anschluss an Papst Franziskus, 2017)

Interpopulational variation of the mating system in the peacock blenny Salaria pavo - Saraiva, João L.; Pignolo, Giulia; Gonçalves, David; Oliveira, Rui F. (acta ethologica, 2012)

Interpreting the causes of depression in Macau elderly - Kwok, Wing Yee (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Interviewing children in uncomfortable settings: 10 lessons for effective practice - Morrison, Keith (Educational Studies, 2013)

Intra-Asia higher education mobilities - Ge, Yun; Ho, Kong Chong (Routledge Handbook of Asian Migrations, 2017)
Intra-Asian higher education mobility is a relatively new phenomenon in Asia and one triggered by the dynamic economic changes occurring in East Asia,

Introducing A Blended Learning Environment to Enhance Student Academic Efficacy - Ho, Io Weng (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Introducing new ventures in Macau traditional retail - Ao, Wan Meng (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Inventory of Portuguese-based Intangible and Tangible Heritage in Larantuka and Sikka (Maumere) in Flores Island (Indonesia): Legacies and Realms of Memory of Portuguese Eurasian Communities in a Muslim Country - Morais, Isabel; Baxter, Alan N. (University of Saint Joseph, 2018)
A study of Portuguese cultural vestiges assimilated into the local cultures of the island of Flores, in Eastern Indonesia, and maintained today. The vestiges include, principally, street theatre (the Bobo tradition) as well as ritual traditions inherited through the Confraternities established by Dominican missionaries in the 16th century.

Investigating the relationship between the human resource management practices and the "intention to stay"of therapists in Macau - Hoi, Mang Hong (University of Saint Joseph, 2017)
Keywords: 2017; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Investigating the urban rulesof the Pearl River Delta: a comparative approach to urban design research and teaching - Tieben, H.; Soares, Nuno; Yiu, E. (IN-TERSECTIONS. Expertise, AcademicResearch and Design from Barcelona, Beirut, Hong Kong, Brisbane, Auckland, Florence, 2018)

Is the Belt and Road Initiative in Africa Sustainable? - Nwachukwu, Francis C. (The Journal of the Macau Ricci Institute, 2019)
In 2000, the China-Africa relationship was further strengthened with the establishment of the Forum on China-Africa Cooperation (FOCAC). The FOCAC offers a platform for consultation and cooperation mechanisms aimed at deepening diplomatic, security, trade and investment relations between China and African countries. Later came the Belt and Road Initiative (BRI) in 2013, an international trade network initiated by China that connects the three continents of Asia, Europe and Africa. The BRI focuses on the following key areas: cultural exchange; policy coordination; facilities connectivity; trade and investment; and financial integration. The BRI shares development objectives similar to those of the United Nations’ Sustainable Development Goals (SDGs). In fact, the BRI implements part of the SDGs and provides a practical mechanism to strengthen the Sino-Africa relationship, which Africa can leverage to meet its Sustainable Goals. Africa is linked through the “Road” of the BRI plan and has received infrastructural projects funded by China to facilitate trade and integration of the national economies along the trading route. Through the establishment of Economic and Trade Zones which attracts investments from Chinese companies, and building infrastructures such as sea ports and railways, China through the BRI framework is helping Africa meet UN SGD Goal 9 concerning industry, innovation and infrastructure. A practical effect is that the BRI is helping African countries overcome the infrastructure gap, create jobs, acquire skills and promote integration between countries.

Jan Jacob Slauerhoff’s the forbidden realm: in Camoes’s footsteps from Lisbon to Macau - Morais, Isabel (The City and the Ocean: Journeys, Memory, Imagination, 2012)

Job stressors, psycholiogical capital, burnout and work engagement among hotel-casino office workers - Sng, Woei Tyng (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Jobs satisfaction in the public service sector: a case study of frontline employees in [DAE] - Choi, Pok Hang (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

John Alexander Holm (1943-2015) - Baxter, Alan N. (Journal of Pidgin and Creole Languages, 2016)

"Join" a Multifunctional Board Game Table - Leong, Hei U.; Caires, Carlos (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Joseph Ma Xiangbo – the John Henry Newman of China? An Attempt to Rehabilitate an Underdog “Father” of Chinese Catholicism 若瑟馬相伯 – 中國的若望享利紐曼? 試替一位無名的中華公教教父振聲 - Law, Cyril Jerome (Macau Ricci Institute Forum, 2019)

Key success factors of the small and medium-sized enterprises (SMES) in Macao - Wong, Sio Kuan (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Kindergarten and Primary Teachers’ Attitudes Toward Curriculum Reform in Macau. - Tchiang, Isabel (University of Saint Joseph, 2018)

Kindergarten teachers' perception of progressive education: a case study - Leong, Cheng I. (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Knowledge transfer in cross cultural team: a case study of Sino French water development company Limited - Lam, Ian Kit (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Korean memorial service for the dead: a re-evaluation of the Christians' understanding - Song, Jeongmin (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Religious Studies (MRS); University of Saint Joseph

La Dottrina Sociale della Chiesa in Cina. Un riferimento per l’etica degli affari (“Catholic Social Teaching in China. A reference for Business Ethics”) - Rothlin, Stephan (La Chiesa in Cina. Un future da scrivere, 2019)

Las Vegas Sands Corp - Wu, Chi Leng (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Law on Race and Slavery, Brazil, 1824 -1888 - Morais, Isabel (Encyclopedia of Free Blacks and People of Color in the Americas: The African-American Heritage of Freedom, 2011)
When Columbus arrived in 1492, the first free black person--a sailor--set foot in the Americas. Over the next 400 years, as slavery spread and became entrenched in the Western Hemisphere, free blacks built communities throughout North and South America, playing a critical role in every region, colony, and country. From Canada to the Caribbean to Chile, they established vital economic and social institutions, championed the cause of abolition, and formed a bridge between the worlds of free whites and enslaved blacks. They worked as artisans, farmers, ministers, merchants, shipbuilders, and reporters. Many free blacks served in the military and fought in every major war, including the American Revolution, the Haitian Revolution, and the Latin American wars for independence. Others served in government, and some--like presidents Bernardino Rivadavia of Argentina and Vicente Guerrero of Mexico--became national leaders.Free people of color in the United States and the Americas hold a unique status in global history. Never before and never since has such a group existed in large numbers anywhere in the world. Long shrouded in obscurity and overshadowed by scholarship on slavery and race, the free black community has become a growing and vibrant field of study as historians uncover vast material on this group, revealing how they lived, how they shaped society, and how they transformed the history of every nation in the hemisphere.Encyclopedia of Free Blacks and People of Color in the Americas is the first reference book to cover this crucial subject. Arranged alphabetically, this new, two-volume encyclopedia includes articles on all major events, issues, and concepts relevant to the free black community in the United States from the colonial period to the Civil War and in the rest of the Western Hemisphere from the late 1400s to the late 1800s, when emancipation became universal. Nearly 400 articles cover every country, colony, state, city, and region in the Americas with a significant presence of free blacks, and biographies, thematic articles, and entries on related subjects shed light on this fascinating topic. Featuring primary sources, illustrations, maps, tables, charts, a chronology, cross-references, suggestions for further reading, and a bibliography, this unique, original, and groundbreaking encyclopedia provides a wealth of information not available anywhere else.Entries include:-Abolitionist movement in Brazil -Zabeau Bellanton -Captain Cudjoe -Coffee cultivation -Education and literacy -Forten family -Free black artisans -French Caribbean -Gender attitudes -Guerrero (slave ship) -Haitian Revolution -La Escalera Plot -Laws of free birth -Legal discrimination on the basis of race -Living "as free" -Toussaint Louverture -Maroons -Marriage between free and slave -Midwives and traditional healers -Negro Convention Movement -Rebecca Protten -Somerset v. Stewart.

Lead: An iOS Application to Help in the Construction of New Habits - de Aguiar, André Wescley Oliveira; Bezerra, Jagni Dasa Horta; Marques, João Alexandre Lobo; de Alexandria, Auzuir Ripardo (International Journal of Information and Electronics Engineering, 2019)

Leadership for self-organisation: complexity theory and communicative action - Morrison, Keith (International Journal of Complexity in Leadership and Management, 2011)

Learning Computer Science: Dimensions of Variation Within What Chinese Students Learn - Thota, Neena; Berglund, Anders (ACM Transactions on Computing Education, 2016)
We know from research that there is an intimate relationship between student learning and the context of learning. What is not known or understood well enough is the relationship of the students’ background and previous studies to the understanding and learning of the subject area—here, computer science (CS). To show the contextual influences on learning CS, we present empirical data from a qualitative investigation of the experiences of Chinese students studying for a master degree at Sweden's Uppsala University. Data were collected of the students’ understanding and learning of CS, their experience of the teaching and their own studies, and of their personal development in Sweden. Using an analysis framework grounded in phenomenography, we analytically separated the what and how aspects of learning. In this article, we describe the what, or the content of the students’ learning, and identify dimensions of variation in the experiences of students. These dimensions relate to the foci of the CS programs, the learning outcomes, and the impact of the studies. The findings from the analyses indicate pedagogical and pragmatic implications for teaching and learning CS in higher education institutions. The study extends the traditional use of phenomenography through the discussion of the dimensions of variation in the experiences and the values within the dimensions. It opens the way for understanding the relational nature of learning in computing education.
Keywords: Computer science education; context; phenomenography; qualitative research; variation theory

Learning strategies and students adaptation to college: a mixed methods research in higher education institutions - Kwong, Ho Keung (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Legal Mechanisms for the Pursuit of Fugitives Overseas - Yang, Cheng V (University of Saint Joseph, 2017)

Leisure time and well being of elderly in Macau - Dias, Anabela Maria (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Light pollution as an environmental problem in Macao SAR: spatial and temporal variation of night sky brightness and survey on public awareness - Cheok, Chi Hou (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Light Pollution in Macao: Assessment of Night-Sky Brightness and Potential Implications - Tam, Ka Ka (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Like a Tree Planted By Streams of Water :The Baptist Church Takes Root In Macao (John and Lilian Galloway 1908-1968) - Ballew, Robert Lawrence (University of Saint Joseph, 2015)
In 2014 Macao Baptist Church celebrated it’s 110th anniversary. How did the Baptist church come to be established in the Portuguese, predominantly Catholic and Buddhist city of Macao? Through careful examination of letters and reports from the main protagonists, John Laurels and Lilian Reeves Todd Galloway, the process of establishing the Baptist church can be revealed and understood within the greater context of the Baptist missionary work in China. The Galloway’s work will be evaluated through a framework of missions eras presented by Dr. Ralph D. Winter. This work looks at the material in two major sections; first, the lives of the Galloways in Macao from 1908 to 1968, and second, the missionary methods of the Galloways over the same period. Using missiological methods of the Kingdom Mission era, the Galloways stood firmly in the Church Mission era focusing their efforts on Personal rather than Social Transformation efforts. Their work laid the foundation for a century of Baptist work in Macao by local Christians as well as foreign missionaries.
Keywords: Baptists; China Macau (Special Administrative Region); China--Macau (Special Administrative Region); Christianity; Church property; Education; Thesis and Dissertations PhD in Religious Studies (D-RS); University of Saint Joseph

Listening to the Environment: Importance of Early Acoustic Experience on Hearing and Development in Zebrafish - Vasconcelos, Raquel (University of Saint Joseph, 2016)

Listening to the Environment: Importance of Early Acoustic Experience on Hearing and Development in Zebrafish - Vasconcelos, Raquel (University of Saint Joseph, 2018)

Literatura e Resistência em Timor-Leste: Identidade e Travessias da Língua Portuguesa na Crónica de Luís Cardoso - Carvalho, João Pedro de Góis Ribeiro de (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Lusophone Studies in Linguistics and Literature (MLLS); University of Saint Joseph

“Little Black Rose” at the 1934 Exposição Colonial Portuguesa - Morais, Isabel (Gendering the Fairs: Histories of Women and Gender at Fairs, 2010)

Lone parents' experiences as higher education students: learning to juggle - Morrison, Keith (Educational Research and Evaluation, 2013)

Loudness Measurement of Multitrack Audio Content Using Modifications of ITU-R BS.1770 - Barbosa, Alvaro; Pestana, Pedro; Reiss, Josh (2013)

Loving music: an analysis on the latent structure of students' reasons in wanting to learn music - Choi, Sin Va (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Luanda no compasso do Tempo Através de Luuanda, o desejo de kianda e os transparentes: uma abordagem comparativa - Pedrosa, Maria Emilia Rodrigues (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Lusophone Studies in Linguistics and Literature (MLLS); University of Saint Joseph

Lugares da Memória, Representações e Poderes - Simões, José Manuel da Silva (Rizoma, 2014)
No seguimento de uma série de contactos estreitos com uma comunidade social situada nos municípios de Baía da Traição, Rio Tinto, Marcação e Mataraca, a 85 quilómetros de distância de João Pessoa, capital do Estado da Paraíba, decidi, desde 2006, levar a efeito um intenso trabalho de campo nestas aldeias indígenas com o objectivo de concretizar um projeto de investigação que englobasse em obrigatória interdisciplinaridade os campos tantas vezes excessivamente singulares da História, da Sociologia, da Política, da Antropologia Cultural e das Teorias da Comunicação, acompanhando e refletindo sobre características e organização social, rituais, manifestações de carácter religioso, evolução histórica, usos e costumes de uma tribo que se abriu quase rendida ao exterior, mas porfiando em manter, todavia, traços e, sobretudo, um discurso narrativo de representações culturais ancestrais. Esta propositada interdisciplinaridade persegue um objectivo epistemológico bem preciso: transformar a investigação empírica em contribuição para uma nova teoria da história da comunicação – a comunicação antropo-histórica entre comunidades ditas tradicionais e o “outro” – a área por mim privilegiada em investigações anteriores, nomeadamente ao nível da licenciatura e do mestrado. Os Potiguara, cuja sociedade ainda não é alfabetizada e, na sua maioria, baseiam a sua cultura na tradição oral, transmitindo os seus lugares da memória sobretudo através do poder do português do Brasil, mesmo quando adornado por escassas palavras tupi, é graças à mensagem e à representação que algumas das suas manifestações culturais reinventam continuadamente a sua identidade Potiguara. É, assim, a mensagem e a representação que inventam o real social e reinventam dinamicamente a sua identidade cultural.
Keywords: Lugares de Memória

Lusofonia, encruzilhadas culturais, Actas da Conferência sobre Lusofonia - Correia, Ana; Sousa, Ivo (Saint Joseph University Press, 2011)

Lusophone-African multinational enterprises internationalization mode: a case analysis of Angolan and Mozambican enterprises - Gonçalves, Marcus Vinicius Amaral (University of Saint Joseph, 2017)
Several internationalization theories have been developed over the past few decades that have made great contributions in explaining enterprise internationalization and their mode of entry strategy. It has been suggested that the determinants of entry mode choice of enterprises from emerging and frontier markets differ from those of comparable enterprises from advanced economies. Literature review appears to indicate that there is a need to expand the framework for entry mode strategies to accommodate the expansion issues enterprises from emerging and frontier countries face in the global marketplace. Nevertheless, not much information and acceptable conclusion has been made on how MNEs from frontier markets internationalize and what factors influence their choice of entry into those markets. This study investigated the internationalization strategies of Lusophone Africa MNEs from Angola and Mozambique, more specifically their entry mode. Information was gathered through a survey of 29 MNE’s upper management respondents and subsequent face-to-face semi-structured interviews with 24 of them in their countries. The results of this study suggest that most MNEs opted for equity-based investment strategies, mainly joint venture and M&E as their preferred mode of entry when internationalizing. A significant group of them opted for e- commerce/e-business strategies, and direct and indirect exports. A smaller portion of the interviewees chose Greenfield investment as a mode of entry. Many of these MNEs could be classified as born global/INV. Finally, this study presents a conceptual framework for use in studying the entry mode choice of enterprises from Lusophone Africa frontier markets and presents research propositions for better understanding the determinants of entry mode strategies of enterprise from Angola and Mozambique. Keywords: Internationalization, Entry Mode, Emerging Markets, Frontier Markets, Lusophone African MNEs, Angola, Mozambique
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph

Lusophony Risks to Be a Heritage with No Future - Leandro, F. J. (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2017)

Luxury brand development in Macau - Chio, Lai Teng (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Macao: A Study on the Impact of Global, Regional and Local Forces. - Lampo, Alessandro; Care, Leanda (Signapore Management University, 2011)
Over the years Macao has been exposed to different cultures and has been influenced by various political and economic interests. The booming casino economy has ultimately transformed the city into the largest gambling hub in the world. In spite of the consensus about Macao's shiny future, there are factors (such as the large reliance on a single industry) and socio-economic problems (such as labor shortage, unequal income distribution, and inflationary pressure) that moderate the optimism. By making use of the Chatterjee and Nankervis' convergent and divergent process model for management, this paper examines how global, regional, and local forces have impacted the economic development process, form and type of organizations in Macao. The paper also suggests that the government implement a framework that develops and diversifies the economy but also takes into consideration the social needs of the community.

Macao air quality forecast using statistical methods - Lei, Man Tat; Monjardino, Joana; Mendes, Luisa; Ferreira, Francisco (International Journal of Environmental Impacts: Management, Mitigation and Recovery, 2019)

Macao air quality forecast using statistical methods - Lei, Man Tat; Monjardino, Joana; Mendes, Luisa; Gonçalves, David; Ferreira, Francisco (Air Quality, Atmosphere & Health, 2019)
The levels of air pollution in Macao often exceeded the levels recommended by WHO. In order for the population to take precautionary measures and avoid further health risks under high pollutant exposure, it is important to develop a reliable air quality forecast. Statistical models based on linear multiple regression (MR) and classification and regression trees (CART) analysis were developed successfully, for Macao, to predict the next day concentrations of NO2, PM10, PM2.5, and O3. All the developed models were statistically significantly valid with a 95% confidence level with high coefficients of determination (from 0.78 to 0.93) for all pollutants. The models utilized meteorological and air quality variables based on 5 years of historical data, from 2013 to 2017. Data from 2013 to 2016 were used to develop the statistical models and data from 2017 was used for validation purposes. A wide range of meteorological and air quality variables was identified, and only some were selected as significant independent variables. Meteorological variables were selected from an extensive list of variables, including geopotential height, relative humidity, atmospheric stability, and air temperature at different vertical levels. Air quality variables translate the resilience of the recent past concentrations of each pollutant and usually are maximum and/or the average of latest 24-h levels. The models were applied in forecasting the next day average daily concentrations for NO2 and PM and maximum hourly O3 levels for five air quality monitoring stations. The results are expected to be an operational air quality forecast for Macao.
Keywords: Macao; NO2; O3; PM10; PM2.5; Particulate matter

Macao Caught between the "Tropical China" and Oriental-style: An Approach to the Colonial and Post-colonial Contexts/Macau entre a "China Tropical" e a lusofonia a Oriente: Algumas achegas sobre os contextos colonial e pos-colonial/Macao entre la "Chine tropicale" et la lusophonie a l'orientale: contribution a l'etude des contextes colonial et post-colonial. - Morais, Isabel (Portuguese Studies Review, 2018)
Gale OneFile includes Macao Caught between the "Tropical China&q by Isabel Morais. Click to explore.

Macao development strategy research centre: work report - He, Wenjing (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Macao Government recruitment system: central recruitment - Ho, Weng Sam (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Macao Shaped by Use – Formalizing the Vernacular Customization of the City - Soares, Nuno; Simões, Filipa (Imminent Commons: Commoning Cities: Seoul Biennale of Architecture and Urbanism 2017, 2017)

Macao Shaped by Use –Formalizing the Vernacular Customization of the City in Choi - Soares, Nuno; Simões, F. (Imminent Commons: Commoning Cities: Seoul Biennale of Architecture and Urbanism, 2017)

Macao Shaped by Use –Formalizing the Vernacular Customization of the City in Choi, H. & Pai, H. (ed.) - Soares, Nuno; F., Simões (Imminent commons: commoning cities, 2017)

Macau, Are We Ready? Challenges On Healthcare Delivery in Nursing Home Settings (QNQ Study - Phase Two) - Ho, Jacky C. K (University of Saint Joseph, 2015)

Macau as a wealth management hub for economic diversfication: a feasibilit study - Ho, Chi Hong (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Macau comparative study with intelligent cities - Lao, Ka Fun (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Macau consumers' attitudes toward mobile advertising - Wong, Iok Fong (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Macau entre a “China Tropical” e a lusofonia a Oriente: Algumas achegas sobre os contextos colonial e pós-colonial - Morais, Isabel (Portuguese Studies Review, 2018)

Macau entre a ‘China Tropical’ e a Lusofonia a Oriente: Algumas achegas sobre os contextos colonial e pós-colonial - Morais, Isabel (Novas perspetivas sobre o luso-tropicalismo, Portuguese Studies Review PSR, 2018)

Macau fashion industry in the 21st Century: a global studies perspective on Asia-Europe cultural exchange - Dias Cardoso, Ana Cláduia (University of Saint Joseph, 2017)
Macau is a dynamic city with a unique blend of Eastern and Western cultures, which has become a well-known travel destination. Macau is not only home to the casinos, but also a shopping paradise, where we can find international luxury brands and local designer brands. The local fashion industry has a strong follower base, taking a different route than that of the Textile and Garment Industry in the 1980s. Nowadays, the local Fashion Industry is not only focused on production, but more on the design and creativity. Macau is a city rooted in the casino industry, having shifted from an industrial economy into a service-based one. This study aims to assess the relations between Asia and Europe with regard to their impact on the creative process of local fashion designers, to understand how local designers balance between market, creativity and aesthetics. Also, it is important to understand how Macau government supports local brands such as: “Made in Macau”. In order to accomplish our goal, several academic areas will be addressed, such as fashion design and the cultural and creative industries in their broad sense, (aesthetics, history, creativity, identity, economy, ergonomics, cognition, and social value). A mix of quantitative and qualitative methods have been used, including questionnaires, open-ended interviews, case-study research, ethnographic methods, historical research and visual methodologies. In the following chapters, this studies will describe mainly the Macau fashion industry in a globalized era and the multiculturalism’s influence on the local fashion designer’s collections
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; Thesis and Dissertations PhD in Global Studies (D-GLS); University of Saint Joseph

Macau Foundation Research Project MF/2017/16: Exploring Educational Leaders’ Perspectives of Inclusion: A Macao and Oporto Comparison. - Correia, Ana (University of Saint Joseph, 2017)

Macau ocean trade - Angeja, Daniela Ruas Joseph De Araujo (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Macau, Quality of Life - Davey, Gareth; Rato, Ricardo (Encyclopedia of Quality of Life and Well-Being Research, 2014)

Macau's Strategies to Develop Training of Talented People with Expertise in the Cooperation between China and Portuguese Speaking Countries - Alves, Jose (University of Saint Joseph, 2015)

Macau Shaped by Use - Vernacular Customization of the City - Choi, Helen Hejung; Pai, Hyungmin (Imminent Commons: Commoning Cities", Seoul Biennale of Srchitecture and Urbanism, 2017)

MaGIC – Petrology and Geochemistry of Igneous Rocks from Macao: Implications for the Crustal Evolution of Southern China. - Dias, Ágata (University of Saint Joseph, 2017)

Malacca Creole Portuguese in the 19th century: Evidence of a wider lectal range? - Baxter, Alan N. (Journal of Pidgin and Creole Languages, 2018)
Abstract Earlier linguistic research suggested that Malacca Creole Portuguese (MCP) had existed without diglossia with Portuguese ever since the Dutch conquest of Portuguese Malacca in 1642, yet it had experienced some contact with Portuguese in the 19th and 20th centuries. The present study adds significantly to this discussion. It considers a range of information from sociohistorical studies and archival sources (including linguistic data) relating to the Dutch (1642–1795, 1818–1823) and early British (1795–1818, 1823–1884) colonial periods. For the Dutch period, it is seen that contact with other Creole Portuguese communities is likely to have persisted for some time. Most significant, however, is the finding that 19th century texts in Portuguese and creole Portuguese, recently identified in archival sources in London and Graz, show that Portuguese continued to be part of the Malacca sociolinguistic setting until the early British period, and that missionary Indo-Portuguese also had a presence at that time. It is concluded that, rather than presenting a narrow lectal range akin to that of the MCP community in the late 20th century, the creole lectal grid in the 19th century was more complex, and included dimensions of a continuum in a diglossic relationship with Portuguese.

Management in China - Cheang, Sam I. (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management in China - Tang, Sao Pang (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management in Macao: global, regional, local forces and critical challenges - Lampo, Alessandro (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management issues in Hong Kong - Iun, Mio Hong (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management style change: a Singapore prespective - Antunes, João Maria Nolasco Lamas Costa (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management style changes in: Malaysia - Tam, Mei San (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management style in United Kingdom - Sun, Lam (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management Transition in South Korea: A Case Study - Chan, Wai Ip; Trimarchi, Michael; Negreiros, Joao (Asian Journal of Business and Management Sciences, 2012)
South Korea management system has been influenced significantly by their traditional social and religious beliefs for hundreds of years. Yet, the 1997 Asian financial crisis has gradually confirmed this shifted, from the Confucius mentality to a close Westernized system. This paper aims to evaluate this management transition in South Korea. The theoretical model of the convergent-divergent, as proposed by Chatterjee and Nankervis [2006], is applied to identify a number of critical factors. The aforementioned factors altogether have influenced the management system in four main vectors: (A) From seniority to meritocracy performance management; (B) From consultative to individualistic decision-making style; (C) From ignoring to embracing corporate governance; (D) From avoiding to improving environmental sustainability.

Managing complex change in school: engaging pedagogy, technology, learning and leadership - Garcia, Alejandro Salcedo; Morrison, Keith (Routledge, 2014)
Keywords: EDUCATION / Educational Policy & Reform / General; EDUCATION / Evaluation; EDUCATION / Leadership; Educational change; Educational leadership; Educational technology

Marian Piety and Ecumenical Convergence: Challenges and Opportunities - Eleutério, JM (Orientis Aura: Macau Perspectives in Religious …, 2017)
In the Catholic world, the year 2017 is marked by the celebration of the 100th anniversary of the Apparitions of Mary in Fátima, Portugal. Although the field of the devotional and popular …

Marketing strategies for a global textbook company to expand into the secondary school market in Macau - Chan, Ka Pou (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Maximizing verbal communication in English amongst Macau Chinese secondary students in private tutorial sessions - Fernandes, Keith Otteran Reis (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

MB intelligence-consultancy limited - Andorinho, Rita da Costa (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Meditation practice: impact on the quality relationships, level of psychological distress, anxiety and depression - Baldinho, Gloria (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Meetings and conventions in Macao: Challenges and opportunities - Che, Sio Wang (University of Saint Joseph, 2016)
Keywords: Challenges; Macau; Meetings; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Mental health and sociodemographics profile as predictors of eating attitude - Pereira, Patricia Teresa (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Mesozoic Granitic Magmatism in Macao, Southeast China - Quelhas, P. M.; Mata, J.; Lou, U. T.; Ribeiro, M. L.; Dias, Ágata (AGU Fall Meeting Abstracts, 2016)
Macao ( 30 Km2) is a territory characterized by small granitic intrusions, located along the coastal region of Southeast China (Cathaysia Block). Granitoids occur as different facies, including microgranite dykes, with distinct textural, mineralogical and geochemical features, for which a middle-upper Jurassic age ( 164 Ma) has been proposed. New data suggest that these granitoids are mostly high-K calc-alkaline metaluminous (A/CNK = 0.8 - 1.1) biotite granites, consistent with total absence of primary muscovite. They show variable amounts of SiO2 (67-77%), reflecting different degrees of magmatic evolution. There is also variability in terms of trace elements, particularly Rare Earth Elements (REEs), evidenced by decreasing (La/Sm)N, (Gd/Lu)N, (Ce/Yb)N and (Eu/Eu*)N towards the more evolved samples, which can be partly attributed to fractional crystallization processes. Most of the granitoids are characterized by (La/Yb)N = 3 - 10.8, showing negative Ba, Nb, Sr, Zr, P, Ti and Eu anomalies. On the other hand, microgranite dykes, along with a few more evolved granites, show an opposite tendency, being usually enriched in HREEs relatively to LREEs with (La/Yb)N = 0.4 - 1.1. Our data suggests intermediate genetic affinities between I-type and A-type granites. Although these granitoids are mostly metaluminous (characteristic of I-types), Ga/Al ratios, usually used to identify A-types, are close to the accepted boundary between A-type and other granite types. The affinities with A-type granites are more marked for the more evolved facies, which depict higher values of FeOt/MgO (14 - 60) and K2O/MgO (60 - 250). Their trace element characteristics are also transitional between WPG (Within-plate granites) and Syn-COLG (Collision Granites). We interpret those transitional characteristics (A/I and WPG/Syn-COLG) of Macao granitoids as reflecting an origin by melting of infracrustal sources over a period of high heat transfer from mantle to crust during an extensional tectonic setting probably contemporaneous with the subduction of the paleo-Pacific plate beneath the Eurasia, whose paleo-suture is thought to be located in the east flank of the Central Range, Taiwan.
Keywords: 8499 General or miscellaneous; VOLCANOLOGY

Message from general chairs - Berglund, A. (Proceedings - 2013 Learning and Teaching in Computing and Engineering, LaTiCE 2013, 2013)

Metodologias e estratégias no ensino de vocabulário da língua Portuguesa em duas escolas secundárias de Macau - Rosário, Isabel Dillon Lei Do (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Mianzi: uncovering its roles in Chinese people's way of living - Tang, Junhui (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Microsoft Power BI Desktop for Data Analytics - NEGREIROS, J. Garrott Marques; MARQUES, JA Lobo (2019)

Migrant transnationalism and religious transformation: religious faith and practice among Filipino migrants (An Anthroplogical Approach Focusing on Macau) - Alabanza, Ian Shelley Sasha Pugal (University of Saint Joseph, 2016)
Religion and migration are both phenomena that have endured perennially in the experience of humanity. However, studies on the relationship of these two subjects are not as prevalent compared to how widespread international migration has become especially among people coming from religious societies. This work contributes to the knowledge base on the significance of religion within the context of international migration by looking at how religious faith and practice evolve as a result of the experience of migration. Interviews about the migration narratives of Filipino Catholics working in Macau were conducted. These were supported by data collected through the use of survey questionnaires that look into changes in religious practices of respondents as well as their attitudes towards faith and belief. The study has found that there is constancy in the religious faith and practice of Filipino Catholics even amidst external changes to the physical and social environment brought about by moving to a predominantly secular society. Through recourse to anthropological analysis, this immutability of faith is attributable to the unique ethnographic feature of Filipinos’ high regard for the centrality and importance of interiority in their life. Keywords: migration, immigrant religion, faith, Filipino religiosity
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

Modelling the influence of mobile information and communication technologies on the festival tourism experience - Silva, Manuel Vasconcelos Ferreira Correia da (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Modelling the Neuromarketing application framework for tourism and entertainment industries in Macau and the Greater Bay Area (University of Saint Joseph, 2019)

Molecular cuisine in Macao - Wong, Un (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Monitoring Temporal Personal Information Regarding Soundscapes and Movement, as a Way to Enhance Social Interactions - Barbosa, Alvaro; Cordeiro, Joao (Springer - Lecture Notes in Computer Science, 2013)

MOOCs and their impact on academics - Sheard, Judy; Eckerdal, Anna; Kinnunen, Päivi; Malmi, Lauri; Nylén, Aletta; Thota, Neena (Association for Computing Machinery, 2014)
Massive Open Online Courses (MOOCs) have recently become a hot topic in the academic world, launching a wide ranging discussion on a number of issues. In this research, we surveyed academics' awareness, attitudes, perceptions, and experiences of MOOCs. We received responses from 236 academics from 23 countries, who were working in different roles such as teachers, researchers, managers, and pedagogical developers. Participants were invited to answer questions concerning their awareness and attitudes towards MOOCs. For participants with some knowledge of MOOCs, we requested their experiences and their observations of the impact of MOOCS on their students, teaching colleagues, and within their institutions. We found the most common reaction to MOOCs amongst the academics was concern but many were positive about the phenomenon. The academics claimed their students could be motivated to take MOOCs because of flexibility and no cost involved. While many academics were not aware of their students taking a MOOC and had not observed any changes to teaching programs at their institutions because of MOOCs, there was evidence of some activity and future plans for engagement in MOOCs.
Keywords: MOOCs; academics; distance learning; e-learning; massive open online courses; open learning; pedagogy

Moral values in education: a case study of one secondary school in Macau - Chen, Xin Wang (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Motivation and factors affecting Japanese learning at the institute for tourism studies - Lao, Meng (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Motivation in learning science in the context of Macau secondary school students: understanding the taxonomy of academic motivation in science learning - Mok, Sao Kuan (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Motives of Traditional and Emerging Donors in Aid Giving: Comparative Study between China and France - Diakite, Ansoumane D.; Phillips, Jenny O. L. (Journal of Social and Political Sciences, 2019)
Since the beginning of bilateral aid giving in the aftermath of the Second World War, the motives for aid giving have changed from being purely political and humanitarian to a mix of different interests. While poverty reduction is frequently stated as the goal of aid giving, it is commonplace for donors to use aid to advance their national interests. The rise of new, emerging donors is creating discussion in both the political and academic fields of aid giving. Traditional or western donors see emerging donors, such as China’s efforts in aid-giving as seeking the natural resources of the recipient countries. This paper provides a historical analysis of the aid-giving motivations underlying an emerging donor, China, and a traditional donor, France. The motives for China’s and France’s aid giving to African countries, with special focus on Guinea, show a great number of similarities.
Keywords: Aid Giving Motives, Emerging Donor, Traditional Donor, Poverty Reduction

Multi-view Convolution Neural Network with Swarm Search Based Hyperparameter Optimization for Enhancing Heart Disease and Breast Cancer Detection - Lan, K.; Li, T.; Fong, S.; Marques, J.A.L.; Wong, R.K. (5th International Conference on Soft Computing and Machine Intelligence, ISCMI 2018, 2018)

Murky shooting: The use of auditory (non-speech) feedback on mobile audiogames - Cordeiro, J.; Baltazar, A.; Barbosa, A. (ACM International Conference Proceeding Series, 2012)

Music training influences on brain development and as a tool for learning improvement - Ferreira, Ana Filipa Neves (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

NEFS: Neo Eco Fabrican System - Ho, Ka Ieng (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Negative affect among undergraduates: Why are higher levels reported by Asian students?: Negative affect in Asian undergraduates - Found, Andrew; Cheong, Hoi Ieng; Duarte, Carlos (Asia-Pacific Psychiatry, 2012)

Neuroendocrinology of Social Behavior in Teleost Fish - Gonçalves, David; Félix, Ana S.; Oliveira, Rui F. (Hormones, Brain and Behavior, 2017)

Neurogenomic mechanisms of social plasticity - Cardoso, Sara D.; Teles, Magda C.; Oliveira, Rui F. (Journal of Experimental Biology, 2015)
Skip to Next Section Group-living animals must adjust the expression of their social behaviour to changes in their social environment and to transitions between life-history stages, and this social plasticity can be seen as an adaptive trait that can be under positive selection when changes in the environment outpace the rate of genetic evolutionary change. Here, we propose a conceptual framework for understanding the neuromolecular mechanisms of social plasticity. According to this framework, social plasticity is achieved by rewiring or by biochemically switching nodes of a neural network underlying social behaviour in response to perceived social information. Therefore, at the molecular level, it depends on the social regulation of gene expression, so that different genomic and epigenetic states of this brain network correspond to different behavioural states, and the switches between states are orchestrated by signalling pathways that interface the social environment and the genotype. Different types of social plasticity can be recognized based on the observed patterns of inter- versus intra-individual occurrence, time scale and reversibility. It is proposed that these different types of social plasticity rely on different proximate mechanisms at the physiological, neural and genomic level.

New geochemical constraints on I-type granites of Macao: evidences for fractional crystallization and petrogenetic affinities with Jurassic-Cretaceous granites in SE China - Dias, Ágata; Quelhas, P; Mata, J; Lou, U T; Borges, R; Ribeiro, M. L (Goldschmidt, 2017)

Newman and the Ministerial Priesthood - Law, Cyril Jerome (Friends of the Ordinariate, 2018)

NIME Education at the School of Arts of the Portuguese Catholic University / CITAR - Barbosa, Alvaro; Martins, Luis (2013)

NIME education at the school of arts of the portuguese catholic university/CITAR - Martins, L.G.; Barbosa, A. (Proceedings - 2013 Learning and Teaching in Computing and Engineering, LaTiCE 2013, 2013)

Nineteenth-Century Women's Travel Writings: A Case Study on Ana D'Almeida's Dairy and Chinese Women's Writing - Leong, Si Kei (University of Saint Joseph, 2011)
We live in an era in which critique of the West has become a deep-rooted phenomenon of the lives of non-Europeans. This paper contributes to the study of European women perception of South East Asia as mirrored in travel writing accounts and, independently but syncronic, of the Chinese women poets who wrote during a period a few decades before and after the mid nineteenth century. I shall be analysing the Western concept of femininity and domesticity in relation to and symultaneously attempting to reformulate Edward Said’s concept of Orientalism. Central to my research method is the fact that I am trying to add to to a traditional Western-oriented gender issues approach - baded on a review of the mid- nineteenth women travel writers - a reversed view, that being the representation of the Orient emerging from the vision of Chinese women literature. My research not only focuses on the literariness of travel writing, which has been widely neglected, but also on a vision of the Orient that is represented by some Chinese women writers in the nineteenth century –Gan Lirou 甘立媃 (1743-1819) and Lü Bicheng 呂碧城 (1883 – 1943). My research is not a survey study of Chinese literature, and it does not claim to be exhaustive. Instead, I attempt to systematize the problem of Western representations of the Orient by taking Ana d’Almeida’s diary, A Lady’s Visit to Manilla and Japan, as central reference and source of conceptual classification. From there, I am trying to further some gender issues drawn from Ana d'Almeida's text and identify symetric instances of those representations, if present, in Chinese literary texts written roughly in the same historical period. Expending Edward Said’s Orientalism, this paper tries to challenge the classic univocal Orient-Occident approach and to mirror Western Orientalist and pseudo- Orientalist ideas into contemporary Chinese writings. This is also meant to be an introduction to this cross-cultural comparative approach of feminity and domesticity open for further contributions in gender studies as well as in fields bordering social history, history of literature, literary theory and cultural anthropology
Keywords: Thesis and Dissertations PhD in History (D-HIS); University of Saint Joseph Thesis and Dissertations PhD in

Non-Native Raters and Native Speech: Other Perspective for the Research on Comprehensibility of Second Language Input - Figueiredo, Sandra; Simões, Edlia; Martins, Margarida Alves; Fernandes da Silva, Carlos (synergy, 2017)
Abstract: This study examines how specific variables such as age, first language, nationality, school grade and socioeconomic status (SES) affect the comprehensibility of second language (L2) speech in 92 second/non-native language learners. Comprehensibility refers to the degree of speech understanding. Fluency, rhythm, grammatical features and word stressing are concurrent factors for the listening comprehension (and the listener comprehensibility) mainly in L2 context. Research evidence focused the quality and differences of speech samples produced by the L2 learners and the comprehensibility rated by native speakers. In reverse scenario there is less evidence on the judgment of L2 learners for speech samples produced by native speakers. In this study we analysed if the comprehensibility ability of 92 young Portuguese L2 learners differ in the following conditions: age, nationality, home language, school grade, proficiency and socioeconomic status. Speech (one text) was recorded by a native speaker and was judged by L2 speakers using 1-5 Likert scale for comprehension difficulty. Main results showed that neither age nor home language had influence for comprehensibility, but socioeconomic, nationality and grades accounted for statistical differences between the groups tested. Also, data suggested that phonetic features are more likely important for the beginner in second language learning compared to the semantic features of speech that heavily depend on vocabulary domain. Keywords: Speech comprehensibility, nationality, grades, socioeconomic status, second language. Read more →

nventory of Portuguese-based Intangible and Tangible Heritage in Larantuka and Sikka (Maumere) in Flores Island (Indonesia): Legacies and Realms of Memory of Portuguese Eurasian Communities in a Muslim Country [Research Report] - Morais, Isabel; Baxter, Alan (University of Saint Joseph, 2018)

O Espaço ao Espaço Público e ao Sentido dos Fatos que os Media nos Oferecem - Simões, José Manuel (Revista GEMInIS, 2018)
Comunicar é tornar comum e informar é dar forma à comunicação. Entre um e outro vai frequentemente uma distancia que nem sempre é possível eliminar. O objetivo deste artigo é mostrar que tanto a comunicação como a informação são um espaço ao sentido da vida. Pese embora as contrariedades e obstáculos, a conivência com os poderes, os imperativos de rentabilidade, a pressão do tempo e a aceleração, os media oferecem um espaço ao espaço público, ao sentido dos fatos, à interpelação; um espaço ao sentido da vida.

O impacto das políticas educativas coloniais Portuguesas: o caso de Macau 1835-1920 - Domingues, Maria Alexandra de Aragão Pozal (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

O Jornal Echo Macaense (1893-1899): uma visão da educação em Macau no séc. XIX - Capela, Nuno Gabriel Teixeira (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

O papel da imprensa em língua portuguesa de Macau: a ética, a ideologia do proissionalismo e o Código Deontológico dos Jornalistas - Simões, José Manuel (Estudos em Jornalismo e Mídia, 2019)
In Macao, Special Autonomous Region of China, there are two professional codes of journalists: one by the Portuguese and English Press Association of Macao and the other by the Macao Journalists’ Association, and there is no regulator in the territory or anyone who administers the rules or sanctions the journalists activity. here’s also no cases of known or reported censorship. However, according to the latest human rights report for this small region of Asia, “the Government has taken steps to limit the coverage of unfavorable news”, admitting the practice of self-censorship by the media.

O património industrial de Macau até 1999: estudo das Fábricas de Panchões - Teixeira, Vitor (Review of Culture, 2015)

O português dos Tongas de São Tomé. In Oliveira, Márcia Santos Duarte; Araujo, Gabriel Antunes. (orgs.) O português na Africa atlântica - Baxter, A. N. (Humanitas/FAPESP, 2018)

O segredo do sucesso escolar: contributo da web 2.0 - Baptista, Zélia Maria de Oliveira (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

O Sonho e o Desejo Libertários da "Lusa Macaense" Lee Li-Lyang: O Heterónimo Feminino na poética de Virgílio De Lemos", - Morais, Isabel Maria da Costa (Entre a Desmistificação e a utopia: Indagação sobre as Lusofonias , Macau: University of Saint Joseph.69-95, 2014)
Virgílio de Lemos (1929-2013), poeta de vanguarda, é um dos precursores da modernidade e experimentalismo como criador do “barroco estético” que ele próprio designou como a linguagem poética marcante nas letras moçambicanas no das décadas de 50 e 60

Obediência militar, liberdade e consciência, Ética Aplicada: Política, Edições 70, - Carreiras, H.; Leandro, F. J. (2018)

Occurance, Distribution and Bioremediation of Endocrine Disrupting Chemicals in Coastal Sediments from Macao SAR, China - Lebel, Alexandre (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Oestradiol and prostaglandin F2α regulate sexual display in female of a sex-role reversed fish - Gonçalves, David (2014)

Old-age pension and pesponsibilities: a work report on macau social security fund - Wong, Ka Lai (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Online and paper evaluations of courses: a literature review and case study - Morrison, Keith (Educational Research and Evaluation, 2013)

Ontogenetic development of the inner ear saccule and utricle in the Lusitanian toadfish: Potential implications for auditory sensitivity - Chaves, Patrícia P.; Valdoria, Ciara M. C.; Amorim, M. Clara P.; Vasconcelos, Raquel O. (Hearing Research, 2017)
Studies addressing structure-function relationships of the fish auditory system during development are sparse compared to other taxa. The Batrachoididae has become an important group to investigate mechanisms of auditory plasticity and evolution of auditory-vocal systems. A recent study reported ontogenetic improvements in the inner ear saccule sensitivity of the Lusitanian toadfish, Halobatrachus didactylus, but whether this results from changes in the sensory morphology remains unknown. We investigated how the macula and organization of auditory receptors in the saccule and utricle change during growth in this species. Inner ear sensory epithelia were removed from the end organs of previously PFA-fixed specimens, from non-vocal posthatch fry (<1.4 cm, standard length) to adults (>23 cm). Epithelia were phalloidin-stained and analysed for area, shape, number and orientation patterns of hair cells (HC), and number and size of saccular supporting cells (SC). Saccular macula area expanded 41x in total, and significantly more (relative to body length) among vocal juveniles (2.3–2.9 cm). Saccular HC number increased 25x but HC density decreased, suggesting that HC addition is slower relative to epithelial growth. While SC density decreased, SC apical area increased, contributing to the epithelial expansion. The utricule revealed increased HC density (striolar region) and less epithelial expansion (5x) with growth, contrasting with the saccule that may have a different developmental pattern due to its larger size and main auditory functions. Both macula shape and HC orientation patterns were already established in the posthatch fry and retained throughout growth in both end organs. We suggest that previously reported ontogenetic improvements in saccular sensitivity might be associated with changes in HC number (not density), size and/or molecular mechanisms controlling HC sensitivity. This is one of the first studies investigating the ontogenetic development of the saccule and utricle in a vocal fish and how it potentially relates to auditory enhancement for acoustic communication.
Keywords: Auditory sensitivity; Batrachoididae; Hair cell; Ontogeny; Saccule; Utricle

Open Innovation as Means of Building Social Capital: A Way to Globalization for Traditional SMEs - Phillips, Jenny O. L. (Journal of Strategic Innovation and Sustainability, 2018)
This research explores innovation of traditional SMEs that do not actively invest in innovation. Elements of open innovation have been identified in these firms in their effort to build social capital which they perceive as pertinent to their businesses. The result of the research shows that instead of using social capital as means for innovation, the unintentional practice of open innovation has contributed to the development of social capital, which further opens up potential for globalization. As a result, a model of open innovation as means of developing social capital for enhancing globalization potential for SMEs was developed.
Keywords: Innovation; SMEs; Social Capital; Sustainability

Opportunity and challenge on service delivery reform of public service center - Lei, Wai Tak (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Optimize the internal policym procedure and develop reform in government services: a case study on Macao immigration department for non-resident workers - Tang, Lai Ieng (University of Saint Joseph, 2013)
Keywords: Civil service; Immigration Department; Macao; Non-resident Workers; Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Os Índios Potiguara: memória, asilo e poder - Simões, José Manuel (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations PhD in Global Studies (D-GLS); University of Saint Joseph

Os índios potiguara: memória, asilo e poder - Simões, José Manuel (Coleção mediaXXI, 2013)

Overall Opinion on Macau Urban Planning and the Five-Year Plan. - Pinheiro, Francisco Vizeu; Penny, W. (Journal of Macau Studies- Boletim de Estudos de Macau, 2017)

Panos, traje e moda em Angola: a linguagem política do corpo - Correia, Ana; Ribeiro, Xénia (Lusofonia, Encruzilhadas Culturais, Actas da Conferência sobre Lusofonia, 2011)

Parenting beliefs and practices among Chinese families in Macau: a case study - Ieong, Man Wa (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Parenting on depression: the mediating role of self-esteem - Noronha, Cintia Chan De (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Parents views of play in Macao infant education - Conceção, Sandra Susana de Matos (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Parents views on special education in Macao - Wong, Man Wa (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Pathophysiological, cardiovascular and neuroendocrine changes in hypertensive patients during the hemodialysis session - Gutiérrez-Adrianzén, O. A.; Moraes, M. E. A.; Almeida, A. P.; Lima, J. W. O.; Marinho, M. F.; Marques, A. L.; Madeiro, J. P. V.; Nepomuceno, L.; da Silva Jr, J. M. S.; Silva Jr, G. B.; Daher, E. F.; Rodrigues Sobrinho, C. R. M. (Journal of Human Hypertension, 2015)
The pathophysiological mechanisms of arterial hypertension during hemodialysis (HD) in patients with end-stage renal disease (ESRD) are still poorly understood. The aim of this study is to investigate physiological, cardiovascular and neuroendocrine changes in patients with ESRD and its correlation with changes in blood pressure (BP) during the HD session. The present study included 21 patients with ESRD undergoing chronic HD treatment. Group A (study) consisted of patients who had BP increase and group B (control) consisted of those who had BP reduction during HD session. Echocardiograms were performed during the HD session to evaluate cardiac output (CO) and systemic vascular resistance (SVR). Before and after the HD session, blood samples were collected to measure brain natriuretic peptide (BNP), catecholamines, endothelin-1 (ET-1), nitric oxide (NO), electrolytes, hematocrit, albumin and nitrogen substances. The mean age of the studied patients was 43±4.9 years, and 54.6% were males. SVR significantly increased in group A (P<0.001). There were no differences in the values of BNP, NO, adrenalin, dopamin and noradrenalin, before and after dialysis, between the two groups. The mean value of ET-1, post HD, was 25.9 pg ml−1 in group A and 13.3 pg ml−1 in group B (P=<0.001). Patients with ESRD showed different hemodynamic patterns during the HD session, with significant BP increase in group A, caused by an increase in SVR possibly due to endothelial dysfunction, evidenced by an increase in serum ET-1 levels.
Keywords: End-stage renal disease; Haemodialysis; Hypertension

Pathway to drug addiction among Macau teenagers - Cheang, Tat Hin (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Pekinger Nachtgespräche: Gott und die Welt in China (Nighttalks in Beijing. God and the World in China) - Rothlin, Stephan; Achten, Peter (Fromm Verlag, 2018)

Perceived benefits of long-term iyengar yoga practice - Ho, Canossa (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Perceived competence and social acceptance of preschool children in Macao: a case study - Teixeira, Vitor; Correia, Ana (International Journal of Learning and Teaching, 2017)

Perceived efficacy of teachers in Macao and their alacrity to engage with inclusive education - Monteiro, Elisa; Kuok, A. C. H.; Correia, Ana; Forlin, Chris; Teixeira, Vitor (International Journal of Inclusive Education, 2019)
This paper reports findings of a mixed methods study examining private school teachers’ perceptions of efficacy in dealing with the challenges presented by inclusive education in Macao. This is highly pertinent after the Government invited consultation to propose changes to amendments of the Decree Law of 1996 concerning the education of students with Special Education Needs (SEN) which will likely see private schools being required to accept these students in the future. Within the context of teacher preparedness for inclusive education, the study found that a number of teachers felt that they were not at all prepared to teach students with SEN. Whilst some teachers suggested that they lacked skills and knowledge in teaching in inclusive classrooms, some felt overwhelmed with the challenges. The teachers proposed that they would need to know how to provide instructional adaptations and modifications to support students with SEN. Implications for continuous development of teacher training and education are discussed within the context of improving teacher efficacy and how private school teachers could better respond to the challenges of inclusive education in Macao.
Keywords: Inclusive education; Macao; teacher education; teacher efficacy

Perceived motivation of telephone counseling volunteers in Macau - Chao, Weng Man (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Percepções de justiça na avaliação de alunos: exploração de situações no ensino secundário em Macau - Pablo, Alberto Manuel da Conceição (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Perception and insight on the psychological and environmental risk factors contributing to first time drug use among young adults in Macau - Lei, Hon Nei (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Perceptions of top management team diversity and company financial performance: BNU Macau - Agues, Alison Brito (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Perfect Take: Experience Design and New Interfaces for Musical Expression - Barbosa, Alvaro; Makelberge, Nicolas; Perrota, Andre; Ferreira, Luis Sarmento (NIME, 2012)

Performance evaluation of Macao governmental web portal - Cordova, Vicente Jorge (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Performance management in the public sector: the case of Macau - Lai, Pou San (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Personality and learning styles surrounded by W3 software: The Macao Portuguese school case - Negreiros, João; Baptista, Zelia; Lee, Leanda (Education and Information Technologies, 2014)
One of the purposes of this study is to evaluate how the choice of teaching method can be assisted by knowledge of a student’s personality type and learning style. The present research is undertaken in the context of Web 2.0 tools use within the Portuguese literature subject at Escola Portuguesa de Macao (EPM). The Felder-Soloman index of learning style (ILS) and the Myers-Briggs Type Indicator (MBTI) based upon Jung’s theory of psychological nature were used as measures of learning style and personality type with 8th grade EPM students. Descriptive and chi-squared correlation statistical results of the associations between personality and learners types are presented. These results are discussed positing that the knowledge of student’s personality traits and learning styles together may have a notable implication for teaching methods.
Keywords: Escola Portuguesa de Macao (EPM); Felder and Soloman; ILS; MBTI; Myers and Briggs; Web 2.0

Perspectives on Inclusion - Correia, Ana; Couzens, Donna; Ho, Ka Lee Carrie (University of Saint Joseph, 2019)
In an inclusive education system, educators engage with increasing their understanding of individual differences, especially in regard to learning, and develop and adjust learning and assessment tasks and contexts in ways that make them accessible and appropriate for all students regardless of starting ability levels, interests, learning strengths and weaknesses. In inclusive schools, diverse approaches to learning are valued and all learners are challenged and supported to be successful in their learning goals. Macao has begun the journey to develop an increasingly inclusive education system. This book has been written as the journey is beggining and explores some of the different perspectives twoard inclusion and interpretaions of "inclusive education" within Macao's education systems and the wider community at this time. The main aims of the research presented in this book are to understand the different views and roles of staff in Macao schools and in the wider community. The book raises questions about how inclusion in Macao might unfold and identifies areas where efforts may be needed to progress inclusive education.

Perspectives on management styles in Japan - Melo, Hugo Hermano Brum de (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Petrology and Geochemistry of Granitic Rocks from Macao - Dias, Ágata; Quelhas, P; Lou, U; Mata, J; Ribeiro, M L (Goldschmidt, 2016)

Petrology and Geochemistry of Igneous Rocks from Macao: Implications for the Crustal Evolution of Southern China - Dias, Ágata (University of Saint Joseph, 2016)

Petrology and Geochemistry of Igneous Rocks from Macao: Implications for the Crustal Evolution of Southern China - Dias, Ágata (University of Saint Joseph, 2018)

Petrology and geochemistry of the igneous rocks from Macao (South China) :tectono-magmatic implications - Quelhas, Pedro Moniz (University of Saint Joseph; Universidade de Lisboa. Faculdade de Ciências, 2019)
The territory of Macao is composed of several granitic intrusions belonging to one of the biggest granite provinces in the world, the Southeast China Magmatic Belt (SCMB), located in the southeast (SE) area of the Cathaysia Block. The SCMB is known by the occurrence of large volumes of Mesozoic magmatic rocks (over 90% are granitic rocks and equivalent volcanic rocks with minor basalts), occupying a total outcrop area of nearly 200.000 km2. The geology of Macao (~30 Km2) is dominated by granitic rocks displaying a wide range of textural, mineralogical and chemical features, making it an ideal region to study these rocks and the petrogenetic processes responsible for their diversity. This study employed a wide range of research methodologies, namely field studies, petrography, zircon geochronology, mineral chemistry, whole-rock elemental and isotopic geochemistry to determine the nature of the source, the petrogenetic processes and the tectonic regimes of the Mesozoic magmatism in this region. Thus, the data collected along this study aims to provide new knowledge on the tectono-magmatic evolution of Macao, in particular, and of SE China, in general. The results obtained from the high-precision U–Pb zircon geochronology, acquired through isotope dilution thermal ionization mass spectrometry (ID-TIMS) and in-situ laser ablation multi-collector inductively coupled mass spectrometry (LA-MC-ICPMS), revealed different ages for Macao granites. Despite its relatively small area, the determined ages tightly constrain the Macao granitic magmatism to two periods, ranging from 164.5 ± 0.6 to 162.9 ± 0.7 Ma (MGI – Macao Group I granites) and 156.6 ± 0.2 to 155.5 ± 0.8 Ma (MGII – Macao Group II granites). In addition, younger dacitic rocks were dated at 150.6 ± 0.6 Ma and <120 Ma. The existence of two proximal but distinct granitic pulses, spanning for a time of about 9 Ma and separated by ca. 6 Ma, in the Macao granitic suite suggests that it was incrementally assembled. This hypothesis is also extendable to the neighbouring Hong Kong region, where the magmatic activity occurred in four major pulses spanning for about 24 Ma. However, the MGII granites indicate the occurrence, on the Pearl River Delta region, of a magmatic pulse between those defined in Hong Kong at the origin of Lamma Suite (165–160 Ma) and the Kwai Chung Suite (148–146 Ma). In addition, Rare Element Earth (REE) ratios suggest that this pulse may only occur in Macao area, while MGI granites show evolving trends of REE ratios similar to those of Jurassic granites outcropping in vast areas of the Cathaysia Block (SE China). Inheritance patterns in the zircon U–Pb data indicate the presence of a population of antecrysts (165–180 Ma) crystallized from earlier magmatic pulses and a population of inherited zircons, from Precambrian to Phanerozoic sources, incorporated into the magmas during melting and/or ascent/emplacement at crustal levels. The oldest inherited ages (2.4 Ga and possibly 2.9 Ga) suggest contribution of Proterozoic and possibly of late Archaean crustal sources for the Macao magmatism. The granitic rocks of Macao are mainly high-K calc-alkaline metaluminous to weakly peraluminous I-type granites with variable degrees of fractionation. Fractional crystallization played an important role in the evolution of these granites, though the fractionation paths differ for the highly fractionated facies of both groups mainly due to distinct accessory fractionating phases. Such difference is evident by distinct REE evolution trends: while MGI magmas seem to have evolved by gradual enrichment in heavy REE relatively to light REE, originating progressively flatter REE patterns, magmas from MGII are marked by depletion of middle REE, leading to progressively concave upward REE patterns. However, while most of the geochemical variation of the MGII granites can be explained by fractional crystallization, the same is not true for MGI granites. The MGI highly fractionated granites show evidence for the REE tetrad effect and are characterized by non-CHArge-and-RAdius-Controlled (non-CHARAC) behaviour of trace elements, suggesting late-stage melt/fluid interactions involving F-rich fluids. The stage of evolution represented by the MGI highly fractionated granites corresponds to the onset of fluid/melt interaction in a highly evolved granitic system, which may have led to enhanced hydrothermal activity in more evolved stages, as those represented in neighbouring areas in SE China. Significant differences in isotopic composition were also observed, with the MGII being characterized by a much narrow range of initial 87Sr/86Sr ratios and εNd(t) and εHf(t) values than MGI. Based on these differences, the MGII granites are considered to be part of a comagmatic suite that has evolved in closed system, contrasting with what can be inferred for MGI. The increase in initial 87Sr/86Sr ratios with degree of evolution, the presence of metasedimentary enclaves and the high percentage of inherited zircon with Paleozoic ages in MGI, suggest the occurrence of an assimilation fractionation crystallization (AFC) process. The AFC processes were a major cause for the I-S transitional characteristics of the MGI highly fractionated granites and possibly of the other similar Jurassic biotite granites in SE China. The observed decoupling of Sr, Nd and Hf isotope systems might have resulted from magma mixing between the granitic and more mafic magmas, which caused the homogenization of Sr isotope ratios but not of the Nd and Hf ones. Such process is also supported by the occurrence of Microgranular Mafic Enclaves (MME) hosted by the granites. Isotope and major element compositions together with model ages strongly suggest that Macao granitic magmas were generated by partial melting of infracrustal medium-to-high K basaltic Paleo-Proterozoic to Mesoproterozoic protoliths heated by, and mixed to some degree with mantle-derived magmas. The temporal and spatial association of Macao and SE China Jurassic I-type granites with basaltic/gabbroic rocks, syenites and A-type granites, displaying typical intraplate chemical features, indicates an extensional regime rather than an active margin for the origin of these rocks. It also points to an important role of mantle-derived magmas in the production of SE China Jurassic granites. Adiabatic decompression melting of the asthenospheric mantle produced mafic magmas, which underplated at the base of the crust (Moho), subsequently triggering partial melting of the lower crust to generate the granitic magmas. The Jurassic Macao granites are interpreted as being produced in an intraplate extensional setting related to the break-off and foundering of a previously flat-slab (Paleo-Pacific plate) beneath the Eurasian plate. The boundary between east and west Cathaysia blocks is roughly along the Zhenghe-Dapu Fault (ZDF), which intersects the SE China coast near Hong Kong and is thought to have played a major role for the Mesozoic magmatic activity in this region. The stronger isotopic affinities of Macao granites with the other granitic rocks and lower crustal xenoliths from the western Cathaysia Block suggest that the ZDF is likely to pass south of Macao, a fact that has not been mentioned before. In addition to the Early Yanshanian (Jurassic) granitic magmatism in Macao, the younger ages obtained for the dacite dykes indicate that the territory was also affected, to a lesser degree, by Late Yanshanian (Cretaceous) magmatism. The transition from granitic to dacitic magmatism most likely corresponds to a change in the regional tectonic regime, which induced a significant change in the magma genesis processes. In contrast with the intraplate features of Macao and SE China Jurassic granites and coeval mafic rocks, the geochemical features of the Macao dacite dykes (e.g. high LILE/HFSE ratios and negative anomalies of Nb, Ta and Ti) are identical to those characterizing arc-like subduction-related magmas. These dacites are most likely evolved products of arc-like magmatism and may testify the reestablishment of a normal subduction system in this area of SE China.
Keywords: Thesis and Dissertations PhD in Science (D-SC); University of Saint Joseph

Placement, inclusion, law and teachers’ perceptions in Macao’s schools - Teixeira, Vitor; Correia, Ana; Monteiro, Elisa; Kuok, A. C. H.; Forlin, Chris (International Journal of Inclusive Education, 2018)
In Macao, the government has initiated a debate regarding revisions in the Decree Law in order to promote a more inclusive schooling system. In this Special Administrative Region of China, inclusive education is one of three possible types of special education that are likely be legislated in the future. The way the teachers perceive the different aspects related to inclusive education, namely the principles, concepts and law, is essential for its full implementation. The aim of this study is to understand teachers’ perceptions about the proposed amendments in the consultation document for changes in the special education regime. In particular, we focus on teachers’ acceptance of the recommended role of parents, the proposed placement models and expectations for teacher training. A mixed-methods approach with a survey of a sample of 500 teachers in private schools and interviews to a sub-sample of 20 provide the data. While agreeing in principle with the majority of the proposed changes in the Decree Law, there were several reservations made by the teachers, especially regarding the extent of parental choice, placement decisions and teacher training. Recommendations to continue the pathway for a more inclusive education system in Macao and for further research are made.
Keywords: Disability; education policy; inclusive education; special education; special education needs

Plasticity in reproductive behaviour in two populations of the peacock blenny - Oliveira, Rui F.; Simões, Mariana G.; Gonçalves, David; Saraiva, João L. (Behaviour, 2011)

Poesia e navegação: o impacto da história e do mito na definição de uma poética especificamente portuguesa - Borges, Vera (De Portugal a Macau. Filosofia e literatura no diálogo das culturas, 2017)
Maria Celeste Natário, Renato Epifânio, Carlos Ascenso André, Gonçalo Cordeiro, Inocência Mata, Jorge Rangel, Maria Antónia Espadinha

Policy Reform for Higher Education in Macao - Chan, Weng I. (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Pollution state of the coastal systems of Macao and the potential role of mangroves in heavy metals remediation - Lo, Leng Ian (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Portuguese as an Additional Language: Domains Use among Young Learners - Neves, Ana Cristina (Language Policy and Language Acquisition Planning, 2018)
Three key concepts will make up the pillars of this paper: second, foreign and heritage languages. Whenever appropriate “additional language” will be used as an umbrella term. A study of the domains of language use will be applied to these three different sociolinguistic contexts. To date, there are not many empirical studies on the domains of language and, more specifically, among young learners in different areal contexts, as it is the case of this study.
Keywords: Additional language; Domains of language use; Foreign language; Heritage language; Language policy; Second language

Post-migration stress and mental health of Filipino female domestic workers in Macau: the moderating role of social networks - Mendoza, Norman B. (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Postal service in Macao CTT in 2016: a work report of the strategic management of Public Postal Service - Wong, Ho Cheng (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Postgraduate Certificate Program of Education in University of Saint Joseph: Cultivating the Rationales and Techniques of Culturally Responsive Teaching among Teachers in Macau (“聖若瑟大學學位後證書課程: 澳門教師文化关联教學理念和技能的培養”in Chinese) - Ge, Yun (University of Saint Joseph, 2018)

Potential Ecological Risk of Heavy Metal Distribution in Cemetery Soils - Amuno, S. A. (Water, Air, & Soil Pollution, 2013)
In this paper, preliminary investigation was conducted to evaluate the potential ecological risk of heavy metals contamination in cemetery soils. Necrosol samples were collected from within and around the vicinity of the largest mass grave in Rwanda and analyzed for heavy metal concentrations using total digestion–inductively coupled plasma mass spectrometry and instrumental neutron activation analysis. Based on the concentrations of As, Cu, Cr, Pb, and Zn, the overall contamination degree (Cdeg) and potential ecological risks status (RI) of the necrosols were determined. The preliminary results revealed that the associated cemetery soils are only contaminated to a low degree. On the other hand, assessment of the potential ecological risk index (RI) revealed that cumulative heavy metal content of the soil do not pose any significant ecological risks. These findings, therefore, suggest that, while cemetery soils may be toxic due to the accumulation of certain heavy metals, their overall ecological risks may be minimal and insignificant.
Keywords: Cemetery soils; Environmental management; Heavy metals; Mass graves

Potential for the design of an energy saving facade system using agglomerated cork: Implications in subtropical climates - Afonso, F. (Sustainable Buildings and Structures: Building a Sustainable Tomorrow, 2019)
Agglomerated cork is a known material by its contribution to the sustainment of the environment, not only because it is a wholly natural material, without chemical additives, but also because its industrial process of production results from the lowest quality residues of cork or industrial waste material, unsuitable for other applications. It is a reusable material, which means, the cork facade elements can be converted into a new agglomerated material, demonstrating a huge potential for adaptation to existing buildings following a reversible process. It is durable, lightweight, water resistant, low-cost material, some of the properties that may qualify it as suitable for application in large surfaces of vertical construction façades. The aim of this article is to analyze the mechanical, thermal and acoustic characteristics of cork composites against site-specific climatic conditions of subtropical climates and its suitability as an external coating system for residential buildings with the goal to reduce the energy consumption for cooling the inner environment. In high-density cities like Guangzhou, Shenzhen and Hong Kong the majority of the buildings starting from the 1960s until early 21st century (Brach & Song 2006), did not integrate thermal insulation systems into external walls, producing a high level of heat transfer through the external façade from the outside environment during spring and summer seasons. Due to the extremely fast urban growth of the modern Chinese city, little importance is given to the quality of the external walls in current residential building construction. For at least during six months each year the consumption of energy due to air conditioning in Guangdong province is extremely high. The study concluded that substantial energy could be saved by implementing an external coating upgrade to existing buildings. Additionally, this study details the result obtained through software for energy simulations (Design Builder, ENVI-met) demonstrating the potential of this project to produce homogeneous and comfortable inside temperatures, which cools the indoor ambient temperature in summer time.

Potential for the design of an energy saving facade system using agglomerated cork: Implications in subtropical climates - Afonso, Filipe (The 2nd International Conference on Sustainable Buildings and Structures, 2019)

Potential for the design of an energy saving facade system using agglomerated cork: implications in subtropical climates - Afonso, Filipe (The 2nd International Conference on Sustainable Buildings and Structures, 2019)

Pre-marital counseling: the experience of Chinese Christian couples in Macau - Pun, Oi Kuan (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Preparatory gestures in choral-orchestral works - Ho, Cheok Ngai (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Choral Conducting (MCC); University of Saint Joseph

Preparing Pre-service Teachers to Become Effective Inclusive Practitioners: Impact on Self-Efficacy (University of Saint Joseph, 2019)

Preservation and Sustainability of Industrial Heritage in the Urban Renewal: A Case Study of Iec Long Firecracker Factory in Taipa, Macao - Zhu, Rong; Pinheiro, Francisco Vizeu (2010 International Conference on E-Product E-Service and E-Entertainment, 2010)
As an incomparable implication of industrial culture, the industrial heritage has a wide range of historical, technological, social, architectural or scientific values. With the process of large-scale contemporary urban revitalization, abandoned industrial buildings and areas always become the targets of urban renewal and redevelopment due to the ongoing transformation on structural changes of economy and adjustments of plot usage. Although the research and discussion on preservation of industrial heritage have been launched in the fields of theory and practice in China, many former industrial areas and buildings are still undergoing extreme threats and irreversible damages. Taking Iec Long Fireworks Factory which is the only well preserved survivor of industrial heritage in Macao as a case study, this paper presents its historic background, present challenges and future envisions of development. Based on group investigations and SWOT analysis, integrated strategies are proposed to preserve and revitalize the old factory ruins and their landscape settings. The conclusions show the significance to preserve and reuse industrial heritage opened for the urban renewal, which also could be a good contribution for sustainability of history and culture, environment, society and tourism.
Keywords: Architecture; Buildings; Cultural differences; Fires; History; International Committee; Production facilities

Preserving Cultural Identity by Rehabilitation of Public Spaces, Case Study Analyses on the Historic Center of Macao. - Pinheiro, Francisco Vizeu (Urban Design, 2017)

Principal perspectives - Correia, Ana; Tchiang, Van Man (Perspectives on Inclusion, 2019)

Privacy in sound-based social networks - Cordeiro, J.; Barbosa, A. (Communications in Computer and Information Science, 2014)

Professional Ethics as Training in Civic Education - Rothlin, Stephan (Hong Kong Journal of Catholic Studies, 2018)

Profile technician business plan 2011-12 - Silva, Miguel P. F. Gomes da (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Programming Course Design: Phenomenographic Approach to Learning and Teaching - Thota, Neena (2014 International Conference on Teaching and Learning in Computing and Engineering, 2014)
Phenomenography is a well-known empirical research approach that is often used to investigate students' ways of learning programming. Phenomenographic pedagogy is an instructional approach to plan learning and teaching activities. This theoretical paper gives an overview of prior research in phenomenographic studies of programming and shows how the results from these research studies can be applied to course design. Pedagogic principles grounded in the phenomenographic perspective on teaching and learning are then presented that consider how to tie students' experiences to the course goals (relevance structure) and how to apply variation theory to focus on the desired critical aspects of learning. Building on this, an introductory object-oriented programming course is described as an example of research-based course design. The insights gained from the experience of running the course are shared with the community of computer science educators, as also the benefits and responsibilities for those who wish to adopt the phenomenographic perspective on learning to plan their teaching. The development of an increased awareness of the variation in students' ways of experiencing programming and the need to broaden the context of the programming course are discussed.
Keywords: Communities; Computer languages; Education; Programming profession; Syntactics; Writing; introductory programming; object-oriented programming; phenomenography; variation theory

Project “HEALTHY EATING GAINS HEALTHY LIFE”: develops community to prevent non-communicable diseases (NCDs) in Macao - Cheang, Van Si (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Project management methodologies: an effectiveness analysis of PMBOK and Agile on Macau's Construction Industry - Morais, João Jose Bragança dos Reis de (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Project management of hotel opening processes in greater China - Noordzij, Gert (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Promoting Awareness for the Acoustic Phenomenon: a Survey of Pedagogical Practices and Research Projects Developed at EA/CITAR - Cordeiro, João; Gomes, José Alberto; Gonçalves, Miguel (Invisible Places, 2014)
At EA/CITAR (School of Arts/Research Centre in Science and Technology of the Arts), sound has always assumed a fundamental role, both in academic research and curricular offer, featuring a Master Program in Sound Design and a Doctoral Program Specialization in Computer Music. This paper presents an overview of some recent artistic/research projects undertaken by students and researchers at this institution, which stimulate the user/listener awareness for the acoustic phenomenon. Furthermore, we describe three pedagogical practices, stemming from Soundscape and Film Sound studies, which aim at training students to avoid the devious influence of sight on the assessment of soundscapes.

Promoting positive peer pressure through small group peer interaction - Vargas, Maria Chrislina Bondoc (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Prospects and pitfalls of being a good communicator: Contemplating the career choices of female students in Macau - Correia, Ana; Marques, Tania (8th Annual Conference of the Asian Studies Association of Hong Kong, 2013)

Protestant Christianity in Communist China - Chan, Hon-keong (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Religious Studies (MRS); University of Saint Joseph

Psychological health components as predictors of academic emotions - Sin, Wai Wun (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Psychological well-being and clinical symptoms as determinants of intuitive eating - Xavier, Elisa Maria (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Public and family stigma of seeking psychological help among Chinese college students - Sou, Kuai Long (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Pyrolysis of Sewage Sludge in Macau: A Feasibility Study - Mak, Shui Sun (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Quality assurance for Macao's higher education institutions: challenges and opportunities - Cheong, Wai San (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Quality of Life in Macau, China - Rato, Ricardo; Davey, Gareth (Social Indicators Research, 2012)
We report the initial findings of an ongoing, long-term investigation into subjective quality of life in Macau, a Special Administrative Region of China. Data were collected via quarterly public surveys (2007 to 2009; n = 8,230), as part of the Macau Quality of Life Report. The main aims of the study were to: (a) ascertain the public’s satisfaction with life and with the regional situation in Macau; (b) confirm the utility of the International Wellbeing Index (IWI) as a measure of subjective life quality; and (c) contribute to ongoing discussion in the literature on quality of life in China. The data indicated moderate levels of personal (PWI = 64.4; range 63–66.7) and national (NWI = 59.7; 57.4–63.7) wellbeing across the study period, which implies that residents in Macau are generally satisfied with life. The lowest scores were reported in the first quarter of 2009, a period of great economic uncertainty in Macau and the world, but were positioned within the normative range. The IWI demonstrated good psychometric performance, consistent with previous studies in China and the West, which confirmed its utility. These findings are discussed in relation to the IWI’s theoretical underpinnings and the literature.
Keywords: China; International Wellbeing index; Macau; Quality of life

Quality of Work Life in Macau - Rato, Ricardo; Davey, Gareth (Happiness Across Cultures: Views of Happiness and Quality of Life in Non-Western Cultures, 2012)
This chapter explores Quality of Work Life (QWL) in Macau. We investigate the meanings and importance of QWL and its implications in terms of happiness and business performance. Although QWL is central to people’s lives, research on this topic is still in its infancy in Macau. Our interviews revealed three salient themes of QWL: Work context, the perceived benefits and demands of the job; Organization, mainly work environment and factors within the organizational context mediating QWL; and the implications of QWL on overall living and happiness.
Keywords: Gaming Industry; Gaming Revenue; Gaming Section; International Wellbeing Index; Work Context

Raising the quality of secondary education in Macao with effecive government funding in private schools: a case study in Santa Rosa de Lima (a private high school) - Man, Kam Tou (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Re-conceptualising computer literacy teaching and learning using constructivist principles and peer-tutoring - Wong, Kin Ming (University of Saint Joseph, 2015)
Nowadays, many university students (in Macau) are required to attend computer literacy courses to develop their basic skill levels and knowledge as part of their literacy foundation requirements. To be effective, such courses, which are very staff intensive and require access to expensive equipment and software, necessitate high levels of individual teaching. Evidence gathered at two study sites during this research, strongly suggests that many students may not be benefiting sufficiently from their computer literacy courses. Teachers frequently complain about the weak IT skills of many course graduates. This research proposes an innovative model for designing and delivering computer literacy courses based on constructivist principles, using peer-tutoring and blended learning to increase cost effectiveness and to improve student outcomes. Central to the model being proposed is the training and deployment of former course graduates as peer instructors and assessors. Constructivist principles provide a conceptual framework to ensure that the curriculum content, teaching strategies, learning styles and assessment procedures are properly aligned and fully understood by both the instructors and students to achieve high quality learning outcomes. An action research approach was used during the pilot and trail phases of the research to monitor the implementation of the model and evaluate its effectiveness using mixed methods. The planned two–phase action evaluation used a questionnaire to investigate the effectiveness of knowledge and skill transfer to students, and tutors’ learning progress; in-depth semi-structured interviews were used to survey, interpret and evaluate students’ and tutors’ perceptions of the new teaching and learning approach. Most respondents had a Confucian Heritage Cultural Background. For the first time, the research provides new insights into ways in which Confucian Heritage Cultural factors, interact with constructive principles in developing peer-tutoring methods in a university setting inMacau, and more widely
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

Reading acquisition in beginner readers: Typical errors in European Portuguese - Simões, Edlia; Martins, Margarida Alves (Educação e Pesquisa, 2018)

Reading policy and practice: an exploratory case study - Wong, Lai Ha (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Real estate transactions in Macau: issues and recommendations - Cheong, Kong Nam (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Realism philosophy and teachers' perceptions of teaching: some implications for school improvement in Macau - Gutierrez, Estrella Cruz (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Realizing the promises of replication studies in education - Morrison, Keith (Educational Research and Evaluation, 2019)

Redesigning historic cities facing rapid tourism growth: The Case of Macao’s World Heritage Centre and San Ma Lou Avenue - Pinheiro, Francisco Vizeu (Worldwide Hospitality and Tourism, 2017)

Reenquadrar percursos de formação o intérprete-tradutor em Macau: estudo de caso em contexto de trabalho - Costa, Manuela Rosa Franco Serpa Mendes da (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Relapse prevention: a reflection around high-risk situations, self-efficacy and life-style modifications in substance abusers - Bucho, Marta (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Relationship between depression, sleep quality and levels of physical activity in Macau adult population - Leong, Petra (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Relationship between personality factors and anger among Chinese female population in Macau - Lijadi, Anatasia Aledelina (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Relationship between Traditional Chinese Beliefs about Aetiology of Mental Disorders and Help Seeking: A Survey of the Elderly in Macao - Found, A. (East Asian Archives of Psychiatry: Official Journal of the Hong Kong College of Psychiatrists = Dong Ya Jing Shen Ke Xue Zhi: Xianggang Jing Shen Ke Yi Xue Yuan Qi Kan, 2016)
OBJECTIVE: A wide range of factors can influence help-seeking attitudes when individuals experience a mental disorder. The current study investigated the relationship between traditional Chinese beliefs related to the aetiology of mental disorders and help-seeking attitudes among elderly participants in Macao. METHODS: In order to ensure the suitability of participants for inclusion in this study, the participants were required to complete an initial screening test using the Short Portable Mental Status Questionnaire (SPMSQ). Participants who successfully passed the test (n = 183) completed a questionnaire that included the Inventory of Attitudes Toward Seeking Mental Health Services (IASMHS), a set of 9 items related to traditional Chinese beliefs about aetiology of mental disorders and demographic items. RESULTS: The IASMHS scores were higher for female participants and for participants who had completed high school compared with those who had never attended school or who had only completed primary education. Endorsement of traditional Chinese beliefs about the aetiology of mental disorders was higher for male participants. There was a negative correlation between traditional Chinese aetiology beliefs related to mental disorders and help-seeking attitudes. CONCLUSION: Traditional Chinese beliefs related to the aetiology of mental disorders are a negative factor that inhibits help seeking. Implications for efforts to increase the utilisation of mental health services by the elderly are discussed.
Keywords: Aged; Asian People; Asian continental ancestry group; Cultural Characteristics; Female; Health Knowledge, Attitudes, Practice; Help-seeking behavior; Humans; Macau; Male; Mental Disorders; Mental disorders / etiology; Patient Acceptance of Health Care

Relationship marketing in retail banking in Macau - Wong, Kuai Leong (University of Saint Joseph, 2015)
Keywords: Bank management; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Repertory grid: investigating personal constructs of novice programmers - Thota, Neena (Association for Computing Machinery, 2011)
In this paper, the repertory grid is presented as a technique to explore novice programmers' experiences within the context of an action research project. The theoretical and methodological aspects of the technique are discussed. The findings from the technique that combined quantitative and qualitative data analysis methods are provided. These findings relate to the learning process, learning content, and learning support as experienced by the students in an introductory object-oriented programming course. The repertory grid technique is then appraised for its relevance and usefulness to the project, and for its contribution to the diversity of computer science research methods. Insights gained from the use of the technique are shared with the community of computer science educators.
Keywords: mixed methods; novice programming; repertory grid

Research Methods in Education - Cohen, Louis; Manion, Lawrence; Morrison, Keith (Routledge, 2013)

Research methods in education - Morrison, Keith; Cohen, Louis; Manion, Lawrence (Routledge, 2018)

Research Projects: Petrology and Geochemistry of Igneous Rocks from Macao: Implications for the Crustal Evolution of Southern China - Dias, Ágata (University of Saint Joseph, 2018)

Researching international student migration in Asia: research design and project management issues - Ge, Yun; Ho, Kong Chong (Journal of Population Research, 2014)
In the context of Asia, the changing dynamics of higher education has increased the visibility and significance of the group of intraregional education migrants. There are several methodological issues which need to be addressed in conducting research for this group of migrants. First, how does the particular type of migrant group and Asian context influence the research design? Second, in order to capture the scale and diversity of this migrant group, how should research be conducted across multiple sites? Third, how does a mixed method design allow researchers to learn more about the behaviour, practice and orientations of education migrants? Our paper aims to make contributions to the discussions on the methods of education migration research in Asia through answering these questions. We use research experiences and preliminary data from a multinational project to illustrate the issues involved in the selection of methods, research design and project management.
Keywords: Asia; Higher education; International student migrants; Mixed methods; Multi-site design; Multicultural research

Responsible Entrepreneurship. How to Write a Business Plan (Chinese-English Version) - Rothlin, Stephan; Myers, T. A; Thompson, M (University of International Business and Economics Press, 2015)

Responsible gambling among casino staff in Macau – a pilot study - Ip, Chi Hou (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Rethinking special administrative regions Chinese cultural identities and the role of social media: a case study of Macau - Lou, Lai Chu (University of Saint Joseph, 2015)
Hong Kong and Macau were politically reunified with Mainland China in 1997 and 1999, respectively. These two cities culturally originated from Mainland China, but due to their own colonial experiences, the Chinese cultural identities within Hong Kong, Macau, and Mainland China became different. The nature of Chinese cultural identities within Hong Kong and Macau were hybridized, and they have formed their own Chinese cultural identities with their own peculiarities. The Internet is a popular communication medium and it facilitates cultural communication inside and outside of these three places. The high-speed development of modern technology leads to the variety of services that emerge in the Internet, such as discussion forum, Blog, Facebook, Twitter, etc. These new and open spaces serve as a platform for ordinary people to express themselves in different ways. General observations in the Internet reveal that the discussion on Chinese cultural identity among Hong Kong, Macau, and Mainland China exists. The combination of self-identity and reconstruction of self-cultural identity are happening in these differently colonized places. Some local Chinese people in Macau, and Taiwanese in Taiwan, share this kind of experience as well. Meanings in different issues via different symbols are formed and they can be seen from the photos that circulate in the Internet using threads posted in Blogs or discussion forums. All these kinds of images or contexts become symbols of recognizable identities. Internet use, therefore, has facilitated the cultural communication between Hong Kong, Macau, Mainland China, and Taiwan. It has also intensified the enlightenment of Chinese cultural identity, showing and highlighting in effect the remnants of recognizable traits in these territories that were once colonized by different states. In essence, they may arguably have formed heterogeneous Chinese cultural identities. This study presents the uniqueness of the formation of Macau identity in comparison to Hong Kong, and how different it was from Hong Kong after the end of the colonial period. This ‘awakening process’, it is argued, provides a new perspective for understanding the attendant connotations and evaluations of cultural identities, and the different perspectives used to understand how the Internet is reshaping the social world. The reconstruction of cultural identity is a global issue and cultural hybridity is an essential element for reconstruction of self-cultural identity in the postcolonial period. This study employs postcolonial theory, along with observation, in-depth interview and online data collection and content analysis that were adapted during the course of the research, in order to discuss this phenomenon
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

Road and traffic management in Macao challenges and way ahead - Lau, Kuai I. (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Ruy Guerra - Morais, Isabel (Dictionary of African Biography, 2012)

Saldanha hydrothermal field: the role of the sediment-cover in the preservation of ore-forming minerals - Dias, Ágata; Barriga, F (Third InterRidge Theoretical Institute: Magmatic and Tectonic Processes and Seabed Resources at Mid-Ocean Ridges. T2-09, 2015)

Sands China Limited - Ieong, Sio Ian (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

School environment’s influence on academic emotion - Lei, Weng Tong (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Science and Laudato Si’ on the Paradigm Shift towards Sustainable Development - Gassner, Franz (The Journal of the Macau Ricci Institute, 2018)
For sustainability researchers and global policy makers it is lucid clear that a radical turnaround of modern societies is needed to approach sustainable development paths. Pope Francis takes his stand on a basic paradigm shift in his Encyclical Letter Laudato Si’: Care for our Common Home (2015). He calls for a radical shift of mindsets and ecological and cultural conversion which are needed for sustainability and a life in dignity for all. The author compares aspects from sustainability research and Laudato Si’ and shows how science and Francis spiritual-theological take converge. Both call for the need of new mindsets and spiritual resources to nourish just life-styles and sustainable societies.

Searching for causality in the wrong places - Morrison, Keith (International Journal of Social Research Methodology, 2012)

Secondary Teachers’ Attitudes Toward Curriculum Reform in Macau (University of Saint Joseph, 2019)

Self construal and cross-cultural adjustment among Filipino migrant workers in Macau: the mediating role of communicative adaptability - Mordeno, Emelyn R. (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Self-regulation on gambling intention: the mediating role of injunctive norms - Ian, In Tong (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Semiotic multimodality :a filmic analysis of Wong Kar-Wai's in the mood for love / - Tan, Chee Seng (University of Saint Joseph, 2017)
The study builts on Bateman and Schmidt’s (2011) and Tseng’s (2009) research on film as a form of “cinematographic document,” and continues their efforts to construct a semiotic mode of film. The author recognizes the complexity of undertaking research in the domain of semiotic discourse. This study argues that as film analysis is about ways of seeing and synthesizing different cinematic styles, strategies; learnt cinematic conventions and reflective viewing is imperative. The interaction of robust multimodal resources, well-defined analytic units, based on dependable models, and conducted through a discursive process should align to produce fruitful filmic discourse. The study premised on the assumption that film is more than a “self-enclosed signification system” but a crucial “cultural practice” that “reflect and inflect culture.” Taken together, this view underscores the importance and interactivity of cinema, culture and society. To this end, the study contributes to filmic meaning making, the New Hong Kong Cinema, and finally, the present study invariably serves as a form of “social document” or “cultural artifacts” in its exploration of Hong Kong ever changing identity, culture and moods.
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

Senior secondary students perceptions of virtue and values: a case study in education in Macau - The Reh, Lawrence (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Sensory play and exploration in early childhood: classroom practices and development - Cardoso, Nair (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Service quality in education: MBA students' satisfaction perspective of MBA program at University Of Saint Joseph - Un, Weng Teng (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Service quality in the public sector: an exploration in Macao's public service and information center - Sio Lameiras, Nga Man Maria (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Set up and testing a secure cloud - Cheang, Son I. (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Information Technology (MIT); University of Saint Joseph

SHAPED BY USE - Individual designs reshaping the city - Soares, Nuno (HKIA Cross-Strait Architectural Design Symposium and Awards 2017, 2017)
Macau is the most densely populated territory in the world, a small but complex urban landscape populated by a myriad of informal devices that produce a dramatic impact on the image and use of the city, creating an ever-present layer shaped by use. The traditional fields of architectural and urban morphology base their analysis on the private and public space, on the forms of buildings, block, streets, and squares. However, the urban landscape is not only shaped top down by market forces, governments, institutional players, but also bottom-up by thousands of small scale interventions carried out daily by their inhabitants, to solve problems or seize opportunities, on the normal process of usage. This research summarizes an extensive analysis of Macau’s urban landscape focused on this layer of appropriation, aimed to identify these shapes generated by use or, in other words, the devices that materialize the phenomenon of appropriation of the public space. They can take the shape of window cages, rooftop houses, canopies, annexes, hawker booths, and outdoor ads. SHAPED BY USE Individual designs reshaping the city – is a typo morphological essay aimed to provide a methodological tool for the analysis of such phenomena, both in this and other similar urban contexts as well as a compelling starting point to speculate on how small scale individual designs can contribute to reactivate and be harnessed to positively reshape the city.

SHAPED BY USE - Mapping, Debating and Envisioning the Customization of Urban Space - Soares, Nuno (AIA (American Institute of Architects) Japan CES Lecture Series, 2018)

Shaped by use. Urban space appropriation in Macau - Soares, Nuno (PNUM 2012 - Portuguese Network of Urban Morphology, 2012)
The contemporary city is a complex system where a multitude of factors and dwellers interact, creating a multi-layered spatial structure that supports the urban life. To successfully research and intervene in this context, one needs to develop fitting approaches and methods to be able to analyze it in depth.

Shequ construction and service development in urban China: an examination of the Shenzhen model - Tang, Ning; Sun, Fei (Community Development Journal, 2017)

Shopping styles of Chinese generation Y: luxury shopping in Macau - Chan Sai Lai (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Signos de los tiempos: desafío a la Nueva Evangelización. El Concilo Vaticano II. Uma Perspectiva teológia. Vicente Vide - José R. Villar (Eds.) San Pablo: Madrid, 2013: - Stilwell, Peter (2013)

Social cues in the expression of sequential alternative reproductive tactics in young males of the peacock blenny, Salaria pavo - Fagundes, Teresa; Simões, Mariana G.; Gonçalves, David; Oliveira, Rui F. (Physiology & Behavior, 2012)

Social enterprise business plan: "green idea" - plastic recycling industry - Chan, Man Leng (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Social Impact Assessment: The Case of The Cradle of Hope Association in Macau - Vendramini, Marjory Rangel De Faria (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Social media propaganda: a case study on its role in the presidency of Rodrigo Duterte - Rivero, Reuben John Limto Rivero (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Social network predicts loss of fertilizations in nesting males of a fish with alternative reproductive tactics - Cardoso, Sara D.; Faustino, Ana I.; Costa, Silvia S.; Valério, Fábio; Gonçalves, David; Oliveira, Rui F. (acta ethologica, 2017)
Alternative reproductive tactics (ARTs) evolve when there is strong intra-sexual competition between conspecifics for access to mates. Typically, larger “bourgeois” males reproduce by securing the access to reproductive resources while smaller “parasitic” males reproduce by stealing fertilizations from larger males. A number of factors can influence the reproductive success of each tactic, including intrinsic (e.g. size) and extrinsic (e.g. tactic relative frequency) variables. An example where plastic ARTs occur is the peacock blenny Salaria pavo, with large males reproducing by defending nests and attracting females (bourgeois tactic) and small males reproducing by achieving sneaked fertilizations (parasitic tactic). In this study, we conducted field observations on individually tagged animals to determine their social network and collected eggs from 11 nests to determine the fertilization success of each male tactic. Paternity estimates for 550 offspring indicated an average fertilization success for nest-holder males of 95%. Nest-holder male morphological traits and social network parameters were tested as predictors of fertilization success, but only the number of sneakers present in the nest-holder’s social networks was found to be a predictor of paternity loss. Although male morphological traits had been previously found to be strongly correlated with reproductive success of nest-holder males, as measured by the number of eggs collected in the male’s nest, no correlation was found between any of the measured morphological traits and fertilization success for these males. The results suggest a stronger influence of the social environment than of morphological variables in the proportion of lost fertilizations by nest-holder males of this species.

Social unrest in Xinjiang in the 21st century: crisis of the Chinese multinational state? - Flores, Rui (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Sounding Architecture: Inter-Disciplinary Studio at HKU - Barbosa, Alvaro; Tsang, Thomas (Aalborg University, 2017)
Sounding Architecture, is the first collaborative teaching development between Department of Architecture and Department of Music at the University of Hong Kong (HKU), introduced in Fall 2016. In this paper we present critical observations about the studio after a final public presentation of all projects. The Review was conducted with demonstrations by groups of students supervised by different Lecturer, in each case focusing on a different strategy to create a connection between Sound, Music, Acoustics, Space and Architectural Design. There was an assumption that the core working process would have to include the design of a new musical instrument, which in some cases became the final deliverable of the Studio and in other cases a step in a process that leads to a different outcome (such as an architectural Design, a performance or social experiment). One other relevant aspect was that Digital technology was used in the design and fabrication of the physical instruments' prototypes, but in very few cases, it was used in the actual generation or enhancement of sound, with the instruments relying almost exclusively in acoustic and mechanical sound.

Soundscape-Sensing in Social Networks. - Cordeiro, Joao; Barbosa, Alvaro (2013)

Spatial Analysis Techniques Using MyGeoffice®: - Negreiros, João Garrott Marques (Advances in Geospatial Technologies, 2018)

Spatial modulation of the hydrological risk at Praia, Cape Verde - Silva, José Lino; Neves, Ana Cristina; Negreiros, João Garrott Marques (IOP Conference Series: Earth and Environmental Science, 2016)
Hydrology modeling became a relevant topic for the Cidade da Praia, Cabo Verde, Africa, due to negative impact risk to local population and its assets. The modeling via Geographical Information Systems (GIS) can help the decision-making process of space occupation and characterization for this type of risk. Under the municipalities of Praia, the phenomenon of flash flood is common, causing soil erosion and landslide. This constitutes a risk for the local habitat, particularly in districts with a lack of strong human infrastructures. To simulate, analyze and generate risk maps using GIS to help this county governance authorities for decision-making, thus, becomes the main aim of this article.

Spectral Characteristics of Popular Commercial Recordings 1950-2010 - Pestana, Pedro; Reiss, Josh; Ma, Z.; Barbosa, Alvaro (2013)

Sports motivation of adults with motor disability in Macau - Castilho, Leonardo Luís (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Sr and Nd isotopic composition of Jan Mayen and Loki’s Castle: a progress report - Cruz, M I; Marques, F A M; Dias, Ágata; Pedersen, R; Barriga, F (43rd Underwater Mining Institute, 2014)

Stages on change: exploring the transitions of heroin using the trans theoretical method - Wong, Ka Wo (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Steps of Greatness: Geopolitics of OBOR, Ed. University of Macau. - Leandro, Francisco José (University of Macau, 2018)

Strategic management coping with contemporary globalization: a work report on the administrative policy of the mpi - bell centre of english - Ma, Si Ka (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Strategies in vocal warm up - Chan, Wun Ming (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Choral Conducting (MCC); University of Saint Joseph

Strategies to reduce greenhouse gas in Macau: assessment on the potentials of natural gas development - Lei, Chon Kio (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Stress amongst teachers and organizational climate of schools in Macau - Jones, Christon Manuel (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Stress and coping of the high school students in Macau: factors and solution - Leong, Ka Chon (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Stress, depression and anxiety on gambling behavior: the mediating role of gambling related cognition - Chan, Ka Wa (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Striving for success in diversities: a case study on perspective of administrative and government policy of the cultural affairs bureau - Wong, Sut Ieng (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Striving for sucess in governmental management: a work report on administration and government policy of the monetary authority of macao - Choi, Lai Si (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Student choice of local tertiary education institutions by two local high schools - Vai, Man Kit (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Study and analysis of the Macau press in Chinese language - Wong, Hio In (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Study of everyday moral reasoning of senior secondary students in Macao - Ng, Sio Lin (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Study on management style changes in Germany - Chau, Manuel (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Study on management style changes in Mongolia - Fong, Mei Lei (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Study on the management transition in Switzerland - Mok, Wan Yin (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Study on the managerial style change in Australia - Tang, Pou I. (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Study on Urban Fabric and Public Space in Macau (Architects Association of Macau, 2012)

Subjective Wellbeing And Quality of Work Life in Macau - Rato, Ricardo Jorge Parreira (University of Saint Joseph, 2013)
Keywords: China; Macau (Special Administrative Region); Quality of life; Research

Subjective Wellbeing in China: A Review - Davey, Gareth; Rato, Ricardo (Journal of Happiness Studies, 2012)
We critically review studies of subjective wellbeing conducted in China by the International Wellbeing Group, and we evaluate the International Wellbeing Index (IWI), a new instrument they developed. Subjective wellbeing was positive and similar in studies across China, and conformed to the normative range. Its resilience (PWI = 61.2–67.1) mirrors survey findings conducted in Western countries, in agreement with Subjective Wellbeing Homeostasis. Reliability, validity and psychometric analyses support the utility of the IWI as a measure of subjective wellbeing. Our conclusions have implications for research and social development in China, discussed further in this review.
Keywords: China; Happiness; International wellbeing index; Quality of life; Subjective wellbeing

Succession in Chinese family business: transgenerational transmission of social capital in Macao - Phillips, Jenny Oliveros Lao (University of Saint Joseph, 2018)
This dissertation reports on a study which aims to add to the theoretical understanding of how social capital is transferred from one generation to the next in business families. Studies in the field of family business have emphasized the importance of succession for the survival of family businesses, but while the succession process and planning have been widely studied, the examination of social capital succession is scarce. As for the studies in family business’s social capital, the importance of social capital as a source of competitive advantage which already exists in business families have often been expressed, but there is a lack of research in the means of transferring this form of capital from the family business leaders to their successors. The study presented here addresses this gap in family business succession literature and social capital literature, explaining the means of transgenerational succession of social capital in family businesses. This is a qualitative research using the multiple case study method which aims to investigate the means of social capital transmission by comparing the cases of five different Chinese family businesses in Macau, which are in the succession process, with the successor currently managing the firm while the former generation business leaders are in the process of handing over the business and preparing for retirement. In doing so, this research offers a theoretical framework of explaining how social capital is transmitted from the incumbents to the successors throughout a five-stage succession process developed for this research. The forms of social capital that exists in family businesses are identified from previous literature, in order to clearly explain how these different forms of social capital are passed on from generation to generation based on the review on succession process introduced in published literature. A theoretical iii framework is formed from the two parent theories on family business succession and social capital, and is then verified empirically from five Chinese family businesses in Macau. The cases are developed through in-depth interviews with the incumbents and successors of the family businesses, informal interviews with stakeholders (including family members, business associates, non-family employees and customers), direct observation on the premises of the Chinese family businesses and secondary data, in order to study the process of intergenerational transmission of social capital in these Chinese family businesses
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph

Sujeitos ou objecto de aprendizagem? uma experiéncia de aprendizagem cooperativa na catequese da Igreja Católica - Souza, Maria das Virgens Costa de (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Sulfide mineralization of the Saldanha hydrothermal field (MAR): constraints from sulfur isotope in-situ microanalysis - Dias, Ágata; Qiu, W; Barriga, F; Tao, C (InterRidge Workshop on Hydrothermal Ore-forming Processes, 2019)

Sulfide Sites in the Arctic Ocean: Jan Mayen and Loki’s Castle, Mineralogical Magazine - Cruz, M I; Marques, A F; Dias, Ágata; Pedersen, R; Relvas, J M R S; Barriga, F J A S (Goldschmidt, 2013)

Sulphide mineralization in Arctic seafloor hydrothermal fields: extending the European exploration area to the Far North - Cruz, M I; Dias, Ágata; Pedersen, R B; Relvas, J M R S; Fonseca, R; Barriga, F J A S (ERA-MIN., 2013)

Surface sediment composition and distribution of hydrothermal derived elements at the Duanqiao-1 hydrothermal field, Southwest Indian Ridge - Dias, Ágata; Liao, Shili; Tao, Chunhui; Su, Xin; Yang, Zhen; Ni, Jianyu; Liang, Jin; Yang, Weifang; Liu, Jia; Li, Wei; Dong, Chuanwan (Marine Geology, 2019)

Sustainable Development of Macao Fishery - Un, Iok Sio (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Sustainable innovation in the face of globalization: a work report on the policy reform of the DSAJ and its subordinate department CRCBM - Chan, San San (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Syntactic and lexical typology of Macau Patuá and Malacca Creole Portuguese. - Baxter, Alan N. (University of Saint Joseph, 2018)

T4E fitness - Maung, Aung Kyaw Soe (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Talent management in the office of infrastructure development: a work report - Lau, Ariann Paula (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Teachers' perceptions of professional development: a case study of two schools in Macau - Wong, Fong Lei (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Teaching and learning with MOOCs: computing academics' perspectives and engagement - Eckerdal, Anna; Kinnunen, Päivi; Thota, Neena; Nylén, Aletta; Sheard, Judy; Malmi, Lauri (Association for Computing Machinery, 2014)
During the past two years, Massive Open Online Courses (MOOCs) have created wide interest in the academic world raising both enthusiasm for new opportunities for universities and many concerns for the future of university education. The discussion has mainly appeared in non-scientific forums, such as magazine articles, columns and blogs, making it difficult to judge wider opinions within academia. To collect more rigorous data we surveyed teachers, researchers, and academic managers on their opinions and experiences of MOOCs. In this paper, we present our analysis of responses from the computer science academic community (n=137). Their feelings about MOOCs are highly mixed. Content analysis of open-ended questions revealed that the most often mentioned positive aspects included affordances of MOOCs, freedom of time and location for studying, and the possibility to experience teaching from top-level international teachers/experts. The most common negative aspects included concerns about pedagogical designs of MOOCs, assessment practices, and lack of interaction with the teacher. About half the respondents claimed they had not changed their teaching as a result of MOOCs, a small number used MOOCs as learning resources and very few were engaging with MOOCs in any significant way.
Keywords: computing academics; distance learning; e-learning; moocs massive open online courses; open learning; pedagogy

Temperament and motive disposition as predictors of academic emotions - Choi, Lik Hang (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Temporal variation in brain transcriptome is associated with the expression of female mimicry as a sequen-tial male alternative reproductive tactic in fish. - Cardoso, S.D., Gonçalves, D., Goesmann, A., Canário, A.V.M., & Oliveira, R.F. (Molecular Ecology, 2017)

Temporal variation in brain transcriptome is associated with the expression of female mimicry as a sequential male alternative reproductive tactic in fish - Cardoso, Sara D.; Gonçalves, David; Goesmann, Alexander; Canário, Adelino V. M.; Oliveira, Rui F. (Molecular Ecology, 2018)
Distinct patterns of gene expression often underlie intra- and intersexual differences, and the study of this set of coregulated genes is essential to understand the emergence of complex behavioural phenotypes. Here, we describe the development of a de novo transcriptome and brain gene expression profiles of wild-caught peacock blenny, Salaria pavo, an intertidal fish with sex-role reversal in courtship behaviour (i.e., females are the courting sex) and sequential alternative reproductive tactics in males (i.e., larger and older nest-holder males and smaller and younger sneaker males occur). Sneakers mimic both female's courtship behaviour and nuptial coloration to get access to nests and sneak fertilizations, and later in life transition into nest-holder males. Thus, this species offers the unique opportunity to study how the regulation of gene expression can contribute to intersex phenotypes and to the sequential expression of male and female behavioural phenotypes by the same individual. We found that at the whole brain level, expression of the sneaker tactic was paralleled by broader and divergent gene expression when compared to either females or nest-holder males, which were more similar between themselves. When looking at sex-biased transcripts, sneaker males are intersex rather than being either nest-holder or female-like, and their transcriptome is simultaneously demasculinized for nest-holder-biased transcripts and feminized for female-biased transcripts. These results indicate that evolutionary changes in reproductive plasticity can be achieved through regulation of gene expression, and in particular by varying the magnitude of expression of sex-biased genes, throughout the lifetime of the same individual.
Keywords: RNA-seq; Salaria pavo; alternative reproductive tactics; behavioural plasticity; neurogenomic state; sex-biased gene expression

Ten Spatial Problems with myGeoffice© for Teaching Purposes - Negreiros, Joao; Diakite, Ansoumane (Open Journal of Social Sciences, 2019)
For a long time, Geography did not hold a specific mathematical approach for any interpretation of space and this was the key reason why Geography degrees covered a wide variety of subjects such as demography, geology or topography to fulfill its curriculum. Yet from the 90’s, Geography finally created its own research agenda to meet four vital questions of any true geographer: “Where is …?”, “Is there a general spatial pattern?”, “What are the anomalies?” and “Why do these phenomena pursue certain spatial distribution?” The present review article addresses ten different spatial (point, regression and event) issues for learning and teaching aim where statistics play a major background role on the outcomes of myGeoffice© free Web GIS platform. These include cluster analysis, geographically weighted regression (GWR), ordinary least squares (OLS) regression, path analysis, minimum spanning tree, linear regression, space-time clustering and point patterns, for instance. Although the technical viewpoint of the algorithms is not explained at fully, this review paper makes a rather strong emphasis on the result’s interpretation, their respective meaning and when these techniques should be applied in a learning/teaching context.

The academic and intellectual life of Macau - Morrison, Keith (Review of Culture (Revista de Cultura), 2014)

The antecedents of In-service teachers’ burnout in a casino dominant economy - Kuok, A. C. H.; Lam, S. M. I (KEDI Journal of Educational Policy, 2018)

The attitude of Macao’s Chinese young people towards Religion and factors influencing their Religious attitude - Cheang, Un I. (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Religious Studies (MRS); University of Saint Joseph

The BRICS and the global order in the early XXI century - Kern, Rafaela Chemale (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The Canton Conference (1667-1668): its content and sinificance - Ip, Ka Kei (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Religious Studies (MRS); University of Saint Joseph

The challenges of ethnic foodservices business in Macau: an Indian restaurant case study - Khan, Muhammad Imran (2016)
Keywords: Food service management; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The change of UK business management style - Lai, Chi Leng (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Colonization of Lifeworlds of Education by Work: Restoration and Recoupling of Lifeworld and System in the Inner Self - Morrison, Keith (Horizons of Education, 2015)
The argument is raised that, in an age of the networked, connected society in an information-rich environment with communication possibilities as never before experienced or made possible, the displacement of educational virtues of morality, ethics and the development of all-round human beings, by those of money, labour, power and work are speeding apace, and the disconnect between system and lifeworld is increasing. Drawing initially on the work of Habermas, in which the colonization of the lifeworld occurs by system imperatives of rationalization, labour, money and power, the paper argues that such moves are manifested starkly in discourses of the relation between education and work, and five areas are introduced in which the links operate. The marketization and commodification of education, together with its incorporation into the service of capital and labour, are attested through a short worked example of one small territory within the larger context of China. Then, taking a lead from Sertillanges and Habermas’s later work, the paper argues for: (a) a reaffirmation of the importance of moral, ethical and spiritual dimensions of education; (b) the breaking of a narrowly instrumental, capital-acquisitive view of education as serving the jobs market and social control and towards a liberating view of education as communicative action and the development of being rather than simply behaving; (c) the importance of transcendence and immanence; and, thereby, (d) moves towards the re-integration of system and lifeworld in participating subjects.

The concept of humanity in the encius and the communist manifesto: a comparative philosophical approach - Vong, Iok Ip; Alabanza, Ian Shelley Sasha Pugal (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Philosophy; University of Saint Joseph

The contribution of female directors in the cinema of China's Special Administrative Regions - Souza, Ravane da Costa (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

The cost benefit analysis of transition to electric vehicle: in Macao and Hong Kong geographical region - Nnaemeka, Ezeka Franklin Amarachukwu (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The creative industries as an integrated factor in a sustainable model for Macao's economic development - Azevedo, Margarida; Barbosa, Álvaro (Creative Industries Journal, 2014)
This article presents an insight into one of the regions with the fastest-growing economy, heavily based on an entertainment, gaming and tourism industry, and that is urgently looking for a sustainable model that articulates with complementary sectors within the cultural and creative industries – Macao. Macao is facing a major economic and social challenge; it has grown as a vulnerable economy relying almost exclusively on gaming revenues. Alternative activities to diversify the economy are urgently required to answer the competition risks haunting this industry. The cultural and creative industries could be a complementary activity – a vehicle for economic diversification. However, current public and private stakeholders for the cultural and creative sector might have been neglecting the unique cultural and heritage ecosystem of the territory, focusing on isolate opportunities and overlooking an inclusive and robust strategy. A sustainable model that attends to the local conditions and its people is required for alternative activities to become a meaningful sector for the social and economic development of Macao.

The Criminalization of Verbal Sexual Harassment in Amending Macao's Criminal Code - Yang, Vincent (Socioeconomic Development Research, 2016)

The Cultivation of Research Labor in Pacific Asia with Special Reference to Singapore - Ge, Yun; Ho, K. C. (Asia Pacific Education Review, 2018)
This paper adopts a political economy perspective in understanding how the country context frames the development of higher education doctoral science, technology, engineering, and mathematics (STEM) programs. We argue that a country's commitment to research and development spending as a strategy to maintain its economic competitiveness creates the market for research labor. This embeddedness of STEM doctoral training programs in the country's science and technology system enlarges differences between STEM and non-STEM doctoral programs. This argument is validated from a survey of doctoral students in leading Pacific Asian universities which shows that STEM doctoral programs have stronger research networks, are better financed, use better facilities, and incorporate a variety of research placements. The embeddedness of STEM programs is further illustrated from the case of Singapore. Singapore-based STEM doctoral students mention enjoying better financial support and receiving better career advice from their supervisors. They depend on collaborative peer learning and cite more varied employment options when asked about their career plans.
Keywords: Career Counseling; Cooperative Learning; Doctoral Programs; Educational Facilities; Employment Opportunities; Financial Support; Foreign Countries; Graduate Students; Networks; STEM Education; Student Attitudes; Student Placement; Student Research; Student Surveys; Supervisor Supervisee Relationship; Universities

The current situation of Macau secondary multi-media teaching in physics - Ao, Wai Chi (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The development of Jack Ma's e-commerce strategy into the Pearl River Delta Regions - Wong, Cheng (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The development of social media marketing in Macau - Chan, Io Pang (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The development of street dance in Macau: its effect on business and society - Tang, Si Ian (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Development of the Gaming Industry and Its Impact on Land Use - Wan, Yim King Penny; Pinheiro, Francisco (Gaming, Governance and Public Policy in Macao, 2011)
Over the past few years, the gaming industry has changed the face of Macao and the lives of its citizens. The liberalisation of casino licensing in 2002 and the implementation of the Chinese government's new visa regulations in 2003, which permitted many mainland Chinese to travel to Hong Kong and Macao on an individual basis, triggered an economic boom. Foreign investment increased dramatically as international companies began to build casinos and hotels. By 2006, gaming revenues had reached a record annual high of US$10.33 billion, far exceeding the US$6.6 billion made on the Las Vegas strip (Gaming Inspection and Coordination Bureau, 2008). Tourist numbers more than doubled from 11 million in 2002 to 21.7 million in 2009 (Statistics and Census Service, 2009a). Rapid economic growth has come at a price, however. There have been many social dislocations and challenges for public policy that can be attributed to the expansion of the gaming industry. A particular issue is land, a fundamental factor of production and an essential component of the gaming industry's success but in short supply in Macao. The tension between casino requirements for land and public needs spills over into debates on matters as diverse as building height restrictions, heritage protection, green space, the opaqueness of government decisions and its lack of consultative mechanisms. © 2011 by The Hong Kong University Press, HKU. All rights reserved.

The effect of family and personal factors on marital attitudes and expectations in Macau - Chan, Cheng Nga (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The effect of managers' cultural and educational background on management style: a study of middle level managers in Macao - Tam, Hoi Iong (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

The effectiveness of a Macau drug prevention program: a comparative Study - Cheung, Claudia (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

The effectiveness of active learning for lower motivated students in a Macao school - Ao, Chi Seng (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The effectiveness of Management Trainee (MT) programs in Macau's Hotel Sector - Ma, Cheok Mei (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The effects of instagram application on the world of photography - Coteriano, Mónica dos Santos (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

The efficacy of an empathy training program for young offenders in the Macao youth correctional - Wong, Pak Kei (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The efficacy of self-control training in the Macao youth correctional institute: changes in the impulsiveness and emotion stability of young offenders - Lei, Joana (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The etiology of mental disorders: public endorsement of traditional Chinese beliefs in Macau - Found, Andrew; Duarte, Carlos (The International Journal of Social Psychiatry, 2013)
BACKGROUND: Public beliefs concerning the causes of mental disorders are important in their effective treatment. The relative importance of public beliefs related to the etiology of mental disorders among Chinese populations and their relationship to other attitudes to mental disorders are poorly understood. AIMS: To investigate the endorsement of beliefs related to the etiology of mental disorders in Macau, in particular, traditional Chinese beliefs, and to explore their relationship to general attitudes towards mental disorders. METHODS: A survey of 361 members of the public measured attitudes towards 32 possible causes of mental disorders as well as contact with and social distance from individuals with a mental disorder. RESULTS: The results indicated that traditional Chinese beliefs were ranked with relatively low importance compared with psychosocial causes. Traditional beliefs related to two underlying factors and were significantly higher in participants with lower education levels. There was a significant negative correlation between endorsement of traditional beliefs and contact with individuals with a mental disorder and a significant positive correlation between endorsement of traditional beliefs and desired social distance from individuals with a mental disorder. CONCLUSION: Factors underlying traditional Chinese beliefs concerning the causes of mental disorders are associated with more negative attitudes towards individuals with a mental disorder, with such beliefs more strongly endorsed by those with relatively lower education levels.
Keywords: Adolescent; Adult; Aged; Attitude to Health; Chinese; Female; Health Knowledge, Attitudes, Practice; Humans; Macau; Male; Medicine, Chinese Traditional; Mental Disorders; Mental disorder; Middle Aged; Surveys and Questionnaires; Young Adult; etiology; lay theories

The evaluation of Microsoft Corporation - Mendonça, César (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The evolution and SWOT analysis of Macao's social security system - Chiang, Lidia (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The evolution of gaming legalization and junket regulation: a comparative study of Macao's and Nevada's gaming industry - Cheong, Weng Lam (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The fiction of Fernanda Dias and Senna Fernandes: Revisiting colonial Macau through the lens of ethnicity, gender and patriarchy - Correia, Ana; Borges, Vera (Proceedings of The European Conference on Cultural Studies 2014, 2014)

The financial feasibility study of redevelopment project at Rua da Caldeira Number 22 - Cheong, Tat Hong (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The financial valuation study of McDonald's, Inc - Ng, Wai Lon (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Foundation of Soundscape-Lab in Macau. - Cordeiro, Joao; Barbosa, Alvaro; Martins, Luis; Gomes, Jose (2014)

The Future of Macau Aviation Industry: A Long-Term Plan & Development Strategies - Xia, Harry (University of Saint Joseph, 2015)

The gender gap in science, engineering, technology & mathematics: unfolding traditional mindsets - Correia, Ana; Marques, Ana (Proceedings of Fifth International Conference of Education, Research and Innovation, 2012)

The generics pharmaceutical industry: the present and future of antibiotics - Ng, Kin Wa (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The green consumer target market and its most effective marketing mix - Guy, Wendy Danielle (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The health related quality of life of coronary heart disease patients with and without percutaneous coronary intervention - Chu, Mei I. (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The impact of declining gaming revenue in the hospitality industry in Macao - Choi, Mei Chan (University of Saint Joseph, 2016)
Keywords: Hospitality industry; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The impact of government policy on the tourism industry: a work report on strategic management of the Macao government tourist office - Sio, Ka Pek (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The Impact of Illegal Contributions on Social Security Scheme and Governance: A Work report on Strategic Management of the Social Security Fund - Cheang, Sin I. (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The impact of multimodal digital games in children’s learning environments - Martins de Abreu, F.; Barbosa, Alvaro (MRI INTERNATIONAL CONFERENCE - Common Good and Education, 2017)

The impact of retail industry of luxury fashion products in Macau's economy - Zhong, Shao Ling (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The impact of social support on the mental health of the visually impaired in Macao = 社會支援對於澳門視障人士的心理影響 - Loi, Wai Cheng (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The impacts of cultural diversity on organization in Macau - Chan, In Choi (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The influence of bilateral trade agreements on mode of market entry choice of resources seeking Chinese firms operating in Nigeria - Olukayode, Iwaloye Ojo (University of Saint Joseph, 2014)
In the past three decades there have being an increase in the number of Bilateral Trade Agreements (BTAs) globally. These agreements involve huge human and financial movements and are essentially based on trade and investment. This phenomenon has brought new dimension to global business environment by changing the landscape in whichfirms from emerging markets operate in another emerging market. In the light of this, this dissertation is to examine how bilateral trade agreementsprovisions influence choice of foreign market entry mode of resource seeking Chinese Multinational Enterprises operating in Nigeria. This study adopts a qualitative design, collecting data using semi-structured interviews. The data are analyzed with content analysis and explanation building to identify themes through application of replication logic. The data obtained from the interviews regarding the research questions are presented and discussed as major findings and adoptedfor the creation of the new model for the study of resources seeking firm’s choice of market entry modes in emerging markets The model developed in this dissertation makes a contribution to theory for the study of market entry modes of MNEs from developing countries entering another developing country. In this case, Chinese resources seeking multinational firms entering Nigeria. Elements of Dunning’s OLI theory, Resources Dependency Theory, and Institution theory extended for the purpose for the theory development process. This investigation also provides important information to assist state policy actors in their development of bilateral trade agreements between China and Nigeria. Implications for firms and their involvement in developing countries and with framework where bilateral trade agreements exist are also provided
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph

The influence of culture on psychological help-seeking behavior: a study with the Filipino community in Macao - Zancan, Madalena (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The influence of job satisfaction and coping strategy on turnover intention of employees in Macao - Kong, Wan Si (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The influence of parental expectations on the psychological distress of Chinese college students in Macao - Sam, David (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The influence of SAR government performance on people’s trust toward Central government: Implications for Hong Kong and Macau civic education - Chris Cheung, Hin Wah; So, Man Yum Larry; Choi, Chi U. Francis; Chow, Chin Fung Philip (Asian Education and Development Studies, 2018)
Purpose The purpose of this paper is to explore the influence of Special Administrative Region (SAR) performance on the “trust” of Hong Kong and Macau people, who “live” under similar context of “one country, two systems,” toward Beijing Central Government. The different perceptions, relating to the abovementioned issue, of the young peoples’ are also investigated. Implication for civic education in these two societies will be brought to light. Design/methodology/approach This study adopts secondary data analysis on the captioned topic. To further illustrate the said issue, this study reviews and analyzes data from protest campaigns in both societies. Findings This paper finds that the performance of Hong Kong and Macau SAR Governments has different impacts on the peoples’ “trust” toward Central Government. It may attribute to the different perceptions about the role of Central Government and levels of democratization in these societies. Civic education emphasizing the “core spirit” of “One country, two systems,” roles of SAR and Central Governments could enable young people better comprehend their relationship with Mainland China and their role as SAR–Chinese citizens. Originality/value This paper is an exploratory study for providing implications for further research on this topic.
Keywords: Civic education; Political trust

The influence of social companions on affect and life satisfaction - Chao, Hang In (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The influence of socialiration tactics and causality orientations on eross-evltuaal adjustment - Bilugan, Marifi Lagan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Inner Harbour - Background Document on the Revitalization of Macau’s Vernacular Heritage - Soares, Nuno (CURB-Center for Architecture and Urbanism, 2014)

The Inner Harbour – Policy Recommendations on the Revitalization of Macau’s Vernacular Heritage - Soares, Nuno (CURB-Center for Architecture and Urbanism, 2014)

The Inner Harbour Vernacular Heritage - Soares, Nuno (CURB-Center for Architecture and Urbanism, 2018)

The Inquisition in Goa and Macao in the 16th Century ; The Untold Story of Leonor da Fonseca, A Macanese New Christian (1593-1595) - Morais, Isabel (澳门学引论, 2010)

The Internet in China’s state–society relations: Will Goliath prevail in the chiaroscuro? - Sautedé, Eric (China Information, 2013)
This article explores how state and society relations have been affected by the development of information technology in China over the past 20 years. It argues that despite all the transformative changes that such technology has helped bring about, ?benefits? have to be weighed in terms of both empowerment of society and strengthening of state capacity. Ultimately, the digital challenge has not translated into a weakening of the authoritarian state, and this can be explained by the very nature of the party-state in China and how it has managed to make use of communication tools that prove to be both constructive and divisive.

The interplay between a Confucian-heritage culture and teachers’ sentiments and attitudes towards inclusion in Macao - Correia, Ana; Monteiro, Elisa; Kuok, Angus; Forlin, Christine; Teixeira, Vitor (European Journal of Special Education Research, 2019)

THE INTERPLAY BETWEEN A CONFUCIAN-HERITAGE CULTURE AND TEACHERS' SENTIMENTS AND ATTITUDES TOWARDS INCLUSION IN MACAU - Correia, Ana; Forlin, Chris; Teixeira, Vitor Manuel dos Santos; Kuok, A. C. H.; Monteiro, Elisa (2019)
Macau Special Administration Region (Macau SAR) is in the process of revising legislation concerning special and inclusive education. While the institutional discourse revolves around establishing inclusive education, it is unclear as to how the proposed changes will enable or depress this from occurring. This research, therefore, examined teachers’ attitudes towards inclusion as an indication of how well the new legislation may be received. Specifically, it investigated the interplay between 508 teachers working in private schools in Macau, that identified themselves as being inclusive schools, and teachers’ sentiments and attitudes towards the acceptance of inclusion and the role that Confucian values might play in shaping these attitudes. Discussion focusses on four key outcomes that need to be addressed if a significant improvement in including all children in regular schools in Macau is to be achieved. These include the need (1) to clarify the concept of inclusion at government, school, and teacher levels as it currently has ambiguous meaning; (2) to provide teachers with more opportunities to have systematic contacts with students with SEN, as this is crucial to improving their sentiments and attitudes toward people with disability; (3) to provide professional learning about inclusive education with better partnerships between teacher education institutions and schools to bridge theory and practice; and (4) to review the hidden influence of the subtle levels of time-honoured Confucian beliefs in Macau, which are not manifest nor easily detected but possibly have a deep impact on day-to-day practices.

The investigation and measures on overtime work in Macau casino and hotel industry: an example of a Macau casino-hotel - Tang, Si Man (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The labor inspection system in Macau: a work report of the strategic management of macau labor affairs bureau - Chan, Weng Sam (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The labor market for casino dealers in Macau: future scenarios and implications for the city of dream - Lam, Ka Fai (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The legal service of the Identification Services Bureau of Macao SAR: reforms and way ahead - Leong, Pui Man (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The local contemporary art of Macao in a state of ambivalence - Mendes, Carla de Utra; Simões, José Manuel (Behind the Façade: Interdisciplinary perspectives on Macao, 2014)

The lodging sector in Macau: uncompetitive budget accommodation - Iong, Kuok Un (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Long March toward Moral Leadership in Business - Rothlin, Stephan; McCann, D (Silliman Journal, 2018)

The Macau Forum and China's Soft Power in the Making: Training the Elite of the Development Portuguese Speaking Countries" - Tran, Émilie; Matias, José Carlos (China - An International Journal, 2015)

The Macau lodging sector: current needs and opportunities for budget hotels - Lei, Kuong Chon (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The management styles in transitions in South Korea - Chiu, Ien Lon (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The meaning of faith: an inquiry of the perceptions of evangelical Christians in Macau - Lei, Ut Neng (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The meeting of John C.H Wu With St. Therese of Lisieux in the Context of China Mission - Tang, Ee Chen (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Religious Studies (MRS); University of Saint Joseph

The mission, values and the principles of Catholic Schools: the case of Macau from the teachers's perspective - Lemos, Avelino (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The multidimensional impact of foreign direct investment on host country economic development: a case analysis of Mozal Aluminum Smelter in Mozambique - Manhiça, Laura Antuérpia Francisco (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The musical meaning of Josquin's Motets - Chan, Pak Hung (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Choral Conducting (MCC); University of Saint Joseph

The neglected heritage of the religious resources in Macao SAR: a feasibility study on developing religious tourism - Wong, Ka Lai (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The OBOR geopolitical drive: the Chinese access security Strategy - Leandro, Francisco J. B. S. (The Belt and Road Initiative Law, Economics, and Politics, 2018)

The OBOR Global Geopolitical Drive: The Chinese Access Security Strategy - - Leandro, F. J (Law, Economics, and Politics, 2018)

The other side of creative industries in Hong Kong and Macau - Mendes, Carla de Utra; Simoes, José Manuel (International Journal of Cultural and Creative Industries, 2014)

The other side of creative industries in Hong Kong and Macau - Mendes, Carla de Utra; Simoes, José Manuel (2014 International Conference of Culture and Creativity (ICCC 2014), 2014)

The outcome of mind over old-age depression program on order people with depression in one Macao elderly day center - Yang, Liu (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The parenting style and quality of attachment in Portuguese vs. Chinese families - Kuoc, Lai Sam (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The path to corporate social responsibility at Coca Cola Macau ltd - Lou, Chi Kin (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The pay structure reform of Macau civil service: the civil servants' perspective - Leong, Vengian (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The perception of psychological counseling services in Macau: the influence of the Chinese culture of "face" - Lai, Chi Shan (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Post-Colonial Imaginary & Politics of Representation in the Macao SAR: The TEATRAU (Theatre showcase from Portuguese-speaking countries) & the (Re) emergence of 'Lusofonia' under Chinese stars - Morais, Isabel (Theatre 15 China, India & the Eastern World, 2016)

The psychological factors related to the usage of electronic devices among adolescents in Macau - Chan, Ka Pou (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The relationship between children's attachment with parents and general self-efficacy during young adulthood in Macau - U, Lei Fong (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The relationship between effort/reward imbalance and happiness: a study of Macau residents - Lam, Hoi Man (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The relationship between music preference, relaxation and personality: a study of Macau residents - Pun, Nga Si (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The relationship between personality, locus of control and driving anger - Fok, Celia Machado (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The relationship between time perspective and study motivation on decision making of student in Macau - Tong, I Wan (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

The relationship between traditional Chinese beliefs and help seeking intention: a survey of elderly people in Macau - Wong, Ka Lok (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The relationship between work engagement, meaning in life, satisfaction with life and happiness - Lau, Kin Hong (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The relevance of philosophy, spirituality and religion in counselling & psychotherapy within Asia - kazmi, Sayed Shajaat Hussain (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The role of economic diplomacy as economic statecraft strategy, for limited sovereign states - Vicente, Mário do Rosário Almeida Barbosa (University of Saint Joseph, 2017)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Role of Mangroves on the Bioaccumulation and Citogenotoxic Effects of Metals and Pesticides on the Food Web of a Coastal System - Chan, S. K; Tagulao, Karen (University of Saint Joseph, 2016)

The role of mangroves on the bioaccumulation and citogenotoxic effects of metals and pesticides on the food web of a sub-tropical coastal system - Chan, Shek Kiu; Tagulao, Karen (University of Saint Joseph, 2018)

The role of mangroves on the bioaccumulation and citogenotoxic effects of metals and pesticides on the food web of a tropical coastal system - Chan, Shek Kiu; Tagulao, Karen (University of Saint Joseph, 2016)

The role of spirituality and religion in counseling and pyschotherapy of christian clients - Tse, Chau Hung (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Sai Van Lake square integrated tourism project: issues and reflections - Lei, Lai Leng (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The seminars of the Macao forum: An illustration of China’s soft-power diplomacy towards the Portuguese-speaking countries - Tran, Emilie; Dos Santos, Jose Carlos Matias (China: An International Journal, 2015)
This article reviews the role that the Macao Special Administrative Region (SAR) plays in China’s cultural and public diplomacy through training programmes organised by the Macao Forum and tailored for the elite of the world’s Portuguese-speaking countries (PSCs). It begins with a review of China’s approach to key instruments of its soft-power offensive and strategy towards the developing world, followed by an overview of Beijing’s linkages with each PSC. Formulated as an expression of China’s cultural diplomacy towards the PSCs, the seminars of the Macao Forum serve as a kind of cooperation in which the provider party—rather than delivering tangible goods and services such as food, money, loans or infrastructure—actually offers grey matter in the form of ideas for initiatives in public policies and reforms, in order to foster further economic development and administrative rationalisation. Adding to an intense debate and substantial literature that discuss quantitatively and qualitatively China’s role in and aid provision to Africa, the authors argue that China, through the Macao Forum’s training programmes, courts the developing PSCs by building the capacity of their human capital, targeting in particular those in the public and private sectors who are in a position to implement their ideas.

The social security system in Macao: a work report on the social security fund - Cheang, Ka Lei (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The study of financial valuation of Marriott International, Inc - Ao, Ka Ian (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The study of psychic distance influence on a manager's choice of transnational marketing: a dissertation - Chukwudi, Romanus (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The supply chain analysis of Kuong Kei Logistics - Sou, Tak Keong (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The tortuous route of the street hawkers in Macao: tales of persistence from the 1950’s to 2015 - Kam, Pui Han (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The urban system of the “Portuguese” city of Macau: inventory of the parish model and heritage patterns - Lao, Fong I. (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The Urge to End It All: A Closer Look into Suicidal Thoughts & Behaviors - Linyu, Khriesizou; Lau, Christine (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The use of cognitive behavior child-centered play therapy: a case study - Cheong, Tania Guilherme (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The valuation of Costco Wholesale Corporation (COSTCO) - Enomoto, Hiromi (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Venetian gaming competitiveness in Macau: a comparison with Galaxy - Chan, Hang Ieng (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Vital Signs of Roman Catholic Liturgical Music among the Cantonese-Portuguese-English Speaking Communities in Macau 羅馬天主教禮儀聖樂在澳門粵葡英三語群體間之生命力’ - Law, Cyril Jerome (2019)

The vocal brain of fish: development of auditory processing and vocal motor control - Vasconcelos, Raquel (University of Saint Joseph, 2016)

The Walt Disney Company valuation "If you can dream it, you can do it" - Walt Disney - Pereira, Filipe Manuel Peixoto (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

"The will and the way of inclusive education in Macao", - Correia, Ana; Teixeira, Vitor (Asian Education and Development Studies, 2017)

The work stress and well-being of casino hotel executives in Macau - Ong, Irene (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Third culture kids: their search for cultural identity - Oliveira, Deborah Christina de (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Three Essays on Foreign Trade, Offshoring and International Rivalry - Lei, Weng Chi (University of Washington, 2018)
This dissertation consists of three essays, covering the topics of foreign trade, offshoring and international rivalry. In particular, Chapter 1 analyzes the strategic capacity allocation of an international oligopoly. Because a line of products shares specific inputs that are fixed in the short run, a multiproduct oligopolist faces a capacity constraint in the production. Not being able to produce the desirable quantities to meet demand, an oligopolist strategically allocates its capacity among different products against its rival. If the market were monopolistic, a firm would mainly concern the effective profitability of a product when allocating its capacity and when responding to a capacity expansion. Identical duopolists that compete in a Cournot fashion should have identical capacity allocation. However, in a sequential game, while the Stackelberg leader allocates all its scarce capacity towards the more profitable product, the follower should still allocate some capacity towards the unprofitable product. This matches the observation that Boeing, the incumbent in the large commercial aircrafts (LCA) industry, specializes in smaller planes, while Airbus allocates resources more evenly towards both superjumbo planes and smaller planes. Chapter 2 provides an explanation to the observation that international oligopolists, which are similar in many ways (subject to the same state of technology, have equal market shares, etc.), may engage in significantly different degrees of offshoring. Different from previous studies, which considered fragmentation to be affected by global exogenous factors only, this essay sees fragmentation as an endogenous variable. A firm can invest on R&D of its own fragmentation technology to enable certain degrees of fragmentation, so that offshoring of those fragmented subparts can be achieved. An important implication of endogenous fragmentation is that the government now has a policy alternative to export subsidy. Very often, when export subsidy is prohibited under an FTA, a government has incentive to subsidize fragmentation of a firm, which can stimulate both export and offshoring. Chapter 3 investigates Macao's and Singapore's questionable goal to diversify among two tourism services—gambling and convention. Macao has a cost advantage in gambling while Singapore has a cost advantage in convention. When a city operates as a regional monopoly, the simple multiproduct model shows that it is optimal for a city to diversify in response to an expansion in the markets of the tourism services. If the two cities operate as a Cournot duopoly instead, there will be a higher degree of product differentiation between the cities. Yet, both cities diversify more when there is a market expansion. On the other hand, Osaka is a potential entrant. The three-city model shows that if Osaka's relative cost of producing convention is even lower than Singapore’s, both Macao and Singapore will produce greater proportions of gambling compared to the two-city case. In general, Macao and Singapore respond to Osaka’s rivalry by strategizing their product mixes to avoid head-on competition with Osaka.
Keywords: 0501:Economics; Economics; Foreign trade; International rivalry; Offshoring; Social sciences; Strategic capacity allocation

To what extent social media plays a role in Macao emergency public communication? the Macao case study during Typhoon Hato (2017) - Ng, Ka Man (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Top-down vs. Bottom-up Strategies in Macau Banking Sector - Ieong, Mei Sio (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Towards a canonically configured episcopal conference of the Catholic Church in the People's Republic of China - Cheng, Xiu Guo (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Religious Studies (MRS); University of Saint Joseph

Towards A New Professionalism For English Language Teachers In China : Changes In Beliefs And Attitudes, And Classroom Practice - Sansom, David William. (University of Saint Joseph, 2015)
This doctoral dissertation focuses on teacher education in the context of experienced tertiary English language teachers in mainland China. It investigates the changes in teachers’ beliefs and attitudes, and in their classroom practice, that result from an external inservice education and training (INSET) course. It follows up subsequent change in teachers’ classroom practice, and in their beliefs and attitudes, in their teaching contexts one year after the INSET course. This dissertation presents a review of the literature in the field of second language teacher education, shifts in research paradigms in the field, and the characterisation of inservice teacher professional development. The nature of teachers’ beliefs and attitudes, and of teachers’ classroom practice, are synthesised from the literature, and are related to research on stages of innovations. Models of change (from beliefs and attitudes to classroom practice, as well as alternative pathways) are discussed, and a conceptualisation of the processes of teacher change in the context of innovations for experienced inservice teachers is proposed. The research presents a case study of one group of teachers attending an INSET course, and uses qualitative data collection, analysis and interpretation. Findings are discussed which provide insight and guidance for INSET provision in the context of experienced teachers, and which add to the research in the field of teacher education in the context of China. The findings suggest that in the complexity of INSET among individual teachers any one model of the process of teacher change may not be applicable, but rather that multiple possible models of change exist for each teacher—in beliefs and attitudes, and in classroom practice—and for each innovation. It is likely that each individual teacher experiences different change models for different innovations during the same INSET course. The significance and implications of the findings are discussed in relation to INSET provision, teacher change, and theories of teacher education and development, as well as the limits of the study, and future research areas suggested
Keywords: Attitudes; Beliefs; China; Classroom Practice; English Teachers; PhD in Education (D-SE); Professionalism; Thesis and Dissertations; University of Saint Joseph

Towards an architecture center in Macau: vision and feasibility - Simões, Ana Filipa Brito da Cruz Rodrigues (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Towards the Creation of a New Sustainable Urban Environment: Improvement and Revitalization of Public Spaces in the Historical Centre of Macao - Zhu, Rong; Pinheiro, Francisco Vizeu (2010 International Conference on E-Product E-Service and E-Entertainment, 2010)
Contemporary urban environment is facing big changes caused by a series of synthetic factors on politics, economy, technology, society and culture. Its goals and design concepts have shifted from the fulfillment of the basic function of life into the improvement of whole qualities of cities. Forming the key part of city fabric, urban historical centre helps link scattered individual historical buildings, and retrieve urban fabric. It also takes important roles in preserving history and tradition, keeping social meanings of a place and city's sustainability. This paper briefly analyzed the historic background and current issues in Macao Historic Centre. Meanwhile, strategies and principles are proposed to improve and revitalize public spaces located in dilapidated or misused historical centre so as to provide new scientific and holistic ideas for the creation of a new sustainable environment in China.
Keywords: Asia; Cities and towns; Fabrics; Green products; History; Publishing; Urban areas

Traditional Chinese medicine versus allopathic treatments: an economic feasiblity study - Videira, Mafalda Raquel da Silva (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Traffic Pollution & Urban Design, Alternatives for Developing Healthy Historical Centers: The Case of Macao - Pinheiro, Francisco Vizeu (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Training and development at the grand LapA hotel in Macau: a qualitative study - Ng, Choi Teng (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Training busy middle-level managers: an exploratory study in Macao hotel industry - Leng, Chiang (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Trajetórias e identidades profissionais na educação: uma história de vida - Rosa, Sandra Moreira Gaspar (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Transformational leadership in a cross cultural context - Shimeobi, Reginald Isiguzo (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Transgenerational Entrepreneurship In Chinese Family Businesses: Proposal For A Model Of Work-Life Synergy - Phillips, Jenny O. L.; Osorio, Arturo E.; Alves, José (2018)
Family business are the dominant form of business in the world, and Chinese family business (CFB) is a unique type of family business that relies on collective action to survive. This paper argues that in CFBs, entrepreneurial actions are transgenerational collective endeavors, and successors are groomed as stewards of the family legacy. Work-life relationship in CFBs is about synergy and not balance because the family identity is the business identity, and vice-versa. Using five in-depth case studies, this research introduces an alternative understanding of CFBs and proposes a model of work-life synergy in transgenerational entrepreneurship based on discussion of five theory-based propositions. This model explains that through emphasizing on the business family's shared value and entrepreneurial legacy, elements of trust, shared identity and stewardship of family members are enhanced which leads to collective action and goal of the business family, resulting in transgenerational entrepreneurship. Limitations and future research are presented.
Keywords: Chinese family business; family legacy; stewardship; transgenerational entrepreneurship; work-life synergy.

Translation into Portuguese of the work Macau Days - a tri-lingual book (English, Portuguese, Chinese) that includes a series of poetic texts by Brian Castro and artworks by John Young, 2017 in collaboration with the J.M. Coetzee Centre for Creative Practice and the EU Centre for Global Affairs, University of Adelaide, Australia. - Morais, I. (A-A-Publishing, 2018)

Transparency: A Necessary First Step Toward an Ethic of Finance - Rothlin, Stephan; McCann, D; Myers, T (Silliman Journal, 2017)

Treanch model of reciprocaion: relating,achiement goals, engagement and academic emotions - Vong, Ka Iu (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Tremores - Simões, José Manuel (Aspectus. Revista de Arte & Ciência, 2019)

Trust gap between government and citizens in the context of social development in Macau - Iong, Chi Long (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Uma leitura de Monção,de Vimala Devi: O puzzle da identidade - Coutinho, Marilia Gomes Coelho (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Lusophone Studies in Linguistics and Literature (MLLS); University of Saint Joseph

Understanding Employee Turnover in Multi-Cultural High Demand Situations: The Hotel Service Industry in Macau (2008-2012) - Lo, Ka In (University of Saint Joseph, 2013)
Keywords: 2008-2012; Hotel Service Industry; Macau

Uptake and depuration kinetics of dicofol metabolite 4,4′-dichlorobenzophenone, in the edible Asiatic clam Meretrix meretrix - Ivorra, Lucia; Cruzeiro, Catarina; Chan, Shek Kiu; Tagulao, Karen Araño; Cardoso, Patricia G. (Chemosphere, 2019)
Uptake and depuration kinetics of 4,4′-dichlorobenzophenone (main metabolite of dicofol) in the edible clam Meretrix meretrix were evaluated through a mesocosm experiment. M. meretrix was exposed to different dicofol concentrations (environmental concentration, D1 = 50 ng/L; supra-environmental concentration, D2 = 500 ng/L) for 15 days, followed by the same depuration period. To accomplish this goal, an analytical method was successfully optimized for 4,4′-DCBP using QuEChERS as extraction method with a range of concentrations 0.3–76.8 ng/g ww quantified by gas chromatography coupled to tandem mass spectrometry. Our results demonstrated different kinetics of accumulation depending on the two dicofol treatments. For D1, the uptake kinetic was best fitted using a plateau followed by one phase association kinetic model, while for D2 a one phase association kinetic model suited better. Similar bioconcentration factors were obtained for both concentrations but only animals exposed to D2, showed 4,4′-DCBP levels above the limits of quantification after 24 h exposure. These animals also showed lower uptake rate (ku) than organisms exposed to D1. During the depuration period, only organisms exposed to D1 successfully depurated after 24 h. On the other hand, although animals exposed to D2 presented higher elimination factor, they did not reach the original levels after depuration. Moreover, values detected in these clams were higher than the Maximum Residue Level (10 ng/g) established by the European legislation. This indicates that longer periods of depuration time than the ones used in this study, may be needed in order to reach safe levels for human consumption. This work also demonstrated that studies on metabolite kinetics during uptake/depuration experiments, could be a new alternative to understand the impact and metabolism of pesticides in the marine environment.
Keywords: Bivalves; GC-MS/MS; Organochlorine pesticides; QuEChERS bioconcentration; Seafood

Use of apparatuses in science laboratory: developmental characteristics of didactical interactions. (The International Education & Learning Review, 2018)

Use of stable isotopes to understand food webs in Macao wetlands - Chen, Qian; Liu, Yang; Ho, Wei-Tim; Chan, Shek Kiu; Li, Qiu-hua; Huang, Jian-Rong (Wetlands Ecology and Management, 2017)
In this study, components of the food-web in Macao wetlands were quantified using stable isotope ratio techniques based on carbon and nitrogen values. The δ13C and δ15N values of particulate organic matter (δ13CPOM and δ15NPOM, respectively) ranged from −30.64 ± 1.0 to −28.1 ± 0.7 ‰, and from −1.11 ± 0.8 to 3.98 ± 0.7 ‰, respectively. The δ13C values of consumer species ranged from −33.94 to −16.92 ‰, showing a wide range from lower values in a freshwater lake and inner bay to higher values in a mangrove forest. The distinct dietary habits of consumer species and the location-specific food source composition were the main factors affecting the δ13C values. The consumer 15N-isotope enrichment values suggested that there were three trophic levels; primary, secondary, and tertiary. The primary consumer trophic level was represented by freshwater herbivorous gastropods, filter-feeding bivalves, and plankton-feeding fish, with a mean δ15N value of 5.052 ‰. The secondary consumer level included four deposit-feeding fish species distributed in Fai Chi Kei Bay and deposit-feeding gastropods in the Lotus Flower Bridge flat, with a mean δ15N value of 6.794 ‰. The tertiary consumers group consisted of four crab species, one shrimp species, and four fish species in the Lotus Flower Bridge Flat, with a mean δ15N value of 13.473 ‰. Their diet mainly comprised organic debris, bottom fauna, and rotten animal tissues. This study confirms the applicability of the isotopic approach in food web studies.

User intention to adopt mobile payment services in Macau - Lam, Ka Wai (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

User Preference on Artificial Reverberation and Delay Time Parameters - Pestana, Pedro Duarte; Reiss, Joshua; Barbosa, Álvaro (Journal of the Audio Engineering Society, 2017)

Using Collaborative learning and blended learning with Macau undergraduate students inside and outside university classroom - Monteiro, Elisa Pack Jon Fong Rendall (University of Saint Joseph, 2015)
This thesis reports a mixed methods empirical research which included a university-wide survey and action research in form of a quasi-experiment in collaborative blended learning (CBL) with Macau undergraduate students. The intervention embodied the principles of social constructivism and investigated the putative benefits and challenges of CBL. The purpose of the study was to identify how to promote effective CBL in undergraduate students and to increase effective learning, motivation, autonomy, empowerment, and communication. It found that only small improvements to students’ CBL took place over time, and found that the students needed specific instruction, practice and development in how to collaborate, both with and without online learning. Despite being in a world-leading, enriched digital environment, the students were new to collaboration and online learning. Students discovered and appreciated the benefits and challenges to collaboration and CBL largely by doing it. The thesis shows that CBL does not release teachers from their instructional and pedagogical roles; rather they place teachers at the heart of effective practice and improvements. The study underpins the need for explicit training of students in CBL. It identifies several strategies and tools which can be useful to promote effective genuine CBL
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

Using cooperative learning in an English language classroom - Leong, Cheng In (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Using digital reading platforms to develop Chinese elementary students' English reading - Correia, Ana; Norte, Patrícia; Garrot, João (International Symposium on Education and Psychology (ISEP), 2017)

Using smartphones as personal monitoring tools for the acoustic environment - Cordeiro, Joao; Barbosa, Alvaro (2014)

Valuation of discovery communications - Wong, Mei Wan (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Ebay INC - Pong, Pou I. (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Expedia, Inc - Lei, Lou Man (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Foot Locker, INC - Lam, Weng Ip (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of GAP Inc - Cheong, Im Seong (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Las Vegas Sands - Ho, Chi Wa (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Shun Tak Holdings - Cheang, Wai Kei (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Starwood hotels and resorts worldwide, Inc - Fong, Pok Hin (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Wal-Mart Stores, Inc - Ng, Mei Wa (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Wynn resorts, limited - Leong, Teng Hon (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuing Walt Disney Co - Neves, Júlio Alexandre Dias (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Variation in students' conceptions of classroom management - Correia, Ana (International Symposium on Education and Psychology (ISEP), 2017)

Vatican II - Gomez, Fausto (Orientis Aura: Macau Perspectives In Religious Studies, 2016)
From a reason-faith perspective, I reflect on “Vatican II: Gaudium et Spes Fifty Years Later.” In the introduction, I speak briefly on the Second Vatican Council, and on its Pastoral Constitution Gaudium et Spes (“Joy and Hope”) and its ethical and social teachings.

Vcall - Wong, Io Leong (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Viability of recycling ventures in Macau - Okorocha, Anthony Ifeanyi (University of Saint Joseph, 2016)
Keywords: Macau; Recycling industry; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Video Content Marketing in the Retail Sector: Implementation for Macau - Lourenço, Joana (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Visions for Education among Chinese and Non-Chinese Student Teachers: Exploring Cultural Differences - Correia, Ana (The International Journal of Diversity in Education, 2015)
Using Habermas’s theory of communicative action, this study explores the educational visions held by a multi-cultural class of students enrolled in a teacher preparation programme set in a culturally and linguistic diverse urban environment with a recent history of colonialism. The purpose of the study was to analyse the educational and teaching visions put forward by student teachers in an essay during the course “Principles of Education,” which took place in the 2013–2014 academic year and to determine whether the variation in respondents’ vision statements was related to the students’ cultural backgrounds. The students’ awareness of the instructor’s grading role may have influenced the content of their vision statements, and thus Habermas’s theory of communicative action was selected as it allows one to focus on both the content and the process of communicative interaction. The current qualitative research presents data from twenty Macau-Chinese and twenty non-Chinese overseas students. Their visions for education and teaching were examined along the lines of culture. The findings revealed that the idealised representations of what education and teaching is, does and symbolise, varies along culture lines. Since urban educational environments are growing culturally diverse, it is recommended that additional attention be given to cultural awareness in teacher education programmes.

Visitor and operator perceptions on destination image and destination brand personality of Macao - Lam, Iok Keng (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Visual media in Macau hospitality industries: analysis of the existing creative process in hospitality and casino companies in Macau - Azevedo, Nuno Jorge Veloso do Carmo (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Vocal differentiation parallels development of auditory saccular sensitivity in a highly soniferous fish - Vasconcelos, Raquel O.; Alderks, Peter W.; Ramos, Andreia; Fonseca, Paulo J.; Amorim, M. Clara P.; Sisneros, Joseph A. (Journal of Experimental Biology, 2015)
Vocal differentiation is widely documented in birds and mammals but has been poorly investigated in other vertebrates, including fish, which represent the oldest extant vertebrate group. Neural circuitry controlling vocal behaviour is thought to have evolved from conserved brain areas that originated in fish, making this taxon key to understanding the evolution and development of the vertebrate vocal-auditory systems. This study examines ontogenetic changes in the vocal repertoire and whether vocal differentiation parallels auditory development in the Lusitanian toadfish Halobatrachus didactylus (Batrachoididae). This species exhibits a complex acoustic repertoire and is vocally active during early development. Vocalisations were recorded during social interactions for four size groups (fry: <2 cm; small juveniles: 2–4 cm; large juveniles: 5–7 cm; adults >25 cm, standard length). Auditory sensitivity of juveniles and adults was determined based on evoked potentials recorded from the inner ear saccule in response to pure tones of 75–945 Hz. We show an ontogenetic increment in the vocal repertoire from simple broadband-pulsed ‘grunts’ that later differentiate into four distinct vocalisations, including low-frequency amplitude-modulated ‘boatwhistles’. Whereas fry emitted mostly single grunts, large juveniles exhibited vocalisations similar to the adult vocal repertoire. Saccular sensitivity revealed a three-fold enhancement at most frequencies tested from small to large juveniles; however, large juveniles were similar in sensitivity to adults. We provide the first clear evidence of ontogenetic vocal differentiation in fish, as previously described for higher vertebrates. Our results suggest a parallel development between the vocal motor pathway and the peripheral auditory system for acoustic social communication in fish.

Web 2.0 Tool Recommendations for Teachers - Negreiros, Joao Garrott Marques; Lei, Weng Chi (International Journal of Innovation and Research in Educational Sciences, 2019)

Web portals in Macau: qoos.com versus cyberctm.com - Cheang, Melody (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Western Educated Young Entrepreneurs of Macao: An Exploratory Study - Chan, Weng Si (University of Saint Joseph, 2015)
Keywords: Entrepreneurship; Religious aspects; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

What Kinds of Comparison Are Most Useful in the Study of World Philosophies? - Sivin, Nathan; Akasoy, Anna; Anderson, Warwick; Colas, Gérard; Eh, Edmond (Journal of World Philosophies, 2018)
Keywords: comparative history; connected history; cultural manifolds; diachronic; intellectual history; inter-cultural comparison; intra-cultural comparison; mutual pollination; postcolonial history; synchronic; transnational history

What Motivates Generation Y Employees in Macau: An Exploratory Study - Organo, Olen Royce Riesgo (University of Saint Joseph, 2013)
Keywords: Employee motivation; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

What students are saying on Facebook about their schools? - Kio, Su Iong (Webology, 2015)

When the Gospel meets the China Dream: Religious Freedom and the Golden Rule - Chiaretto Yan, Kin Sheung (International Bulletin of Mission Research, 2018)
The issue of religious freedom affects Sino-Vatican relations, but the Roman Catholic Church shares values with Confucianism, which provides common ground for dialogue. Pope Francis is focusing the church outward by promoting a culture of encounter and by working unceasingly for a fraternal dialogue of peace. Chinese president Xi Jinping urges his people to fulfill the China dream, emphasizing the core values of harmony, friendship, and civilization. Many have believed that the Gospel can contribute to China?s spiritual civilization; normalization of relations between China and the Holy See would benefit China and the Catholic Church and contribute to world peace and harmony.

“Wisdom in Aristotle and Aquinas,” Existenz - Eh, E. (International Journal in Philosophy, Religion, Politics and the Arts, 2017)

Wisdom in Aristotle and Aquinas: From Metaphysics to Mysticism - Eh, Edmond (Existenz: An International Journal in Philosophy, Religion, Politics, and the Arts, 2017)
This essay contains an attempt to trace the evolution of the concept of wisdom as found in the thought of Aristotle and Aquinas in terms of how the philosophical concept of wisdom as an intellectual virtue is understood and used to express the theological concept of wisdom as a gift of the Holy Spirit. The main aim is to understand how Aquinas derived the concept of wisdom from Aristotle's metaphysics and developed it in his mysticism. This research is based on a close study of Book Six of Aristotle's Nichomachean Ethics, the corresponding sections of Aquinas' Sententia libri Ethicorum and question forty-five of the second part of the second part of Aquinas' Summa Theologiae. The insights gained from the study are then used to decipher the theoretical meaning of Augustine's famous saying: "love and do what thou wilt" and to expound on the practical value of wisdom for religious leaders.

Work engagement: Evolution of the concept and a new inventory. Psychological Thought, - Kuok, A.C.H.; Taormina, R.J. (2017)

Work in the visual and performing arts - Rocco, Ron (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Work report - Chan, Kai Iong (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Work Report: the Venetian Macao resort hotel - Lei, Iok Kei (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Workplace community development empowering employees in a public service a field research - Tong, Ka Io (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Wrestling with God - Flores, Randolf (Orientis Aura: Macau Perspectives In Religious Studies, 2016)
This study will discuss the following Old Testament texts: Gen 32:23-32; Jon 1:17; Tob 6:1-9; and Exod 4:24-26 and will argue that these are about the initiation of a person to do a divine mission. Some parallels from Asia—Epic Gilgamesh, texts from Tibetan Buddhism, Hinduism, and the Philippine epic, Biag ni Lam-ang will also be taken into consideration to shed light on them. It will also present their interpretation as typoi of the sacraments of initiations found in early Christian literature and art.

Zechariah Goh Toh Chai's reminiscences of Hai Nan and in the bamboo forest: a conductor's perspective - Lee, Pei Khoon (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Choral Conducting (MCC); University of Saint Joseph

⼆⼗世紀澳⾨錯位的記憶——《神州在望》作品簡析. - Zhou, L. (Journal of Macau Studies, 2017)

優質睡眠與工作壓力對澳門博彩員工之相關性研究 = Quality of sleep and work-related stress among casino employees in Macau - Ng, Kuan Fun (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

加拿大網絡安全戰略及法律問題 - , - Yang, Vincent (中國法學- 2013年網絡資訊安全法特刊, 2013)

廣州會議（1667-1668）四十二條條文的意義 - Ip, Ka Kei (道風：基督教文化評論, 2012)
Canton Conference (1667-1668) is regarded as an important event in the history of Christianity in China. The Conference was held by missionaries from three religious orders, namely, the Jesuits, Dominicans and Franciscans. Together they tried to achieve something common to strive for the prosperity of the China mission. It is true that the background and atmosphere of the Conference was influenced and overwhelmed by the Rites controversy. However, another significant part that the conference covered, in a large portion, dealt with wide pastoral issues in the context of Chinese society. The forty two articles in this Conference demonstrate the open-mindedness and a fairly positive knowledge of an approach to Chinese custom. In addition, some recommendations remain open to further inquires, in the sense that they were still finding a better way to cope with the indigenous affairs. Analysis of the articles as a whole gives light to various aspects of missionary work at that time beyond the controversial article forty-first.
Keywords: Canton Conference; Christianity in China; Missionary Activity; 中國基督宗教史; 傳教士活動; 廣州會議

從即興戲劇體驗討論香港幼兒美感教育環境 - 何嘉莉 (亞洲戲劇教育學刊, 2018)

提升澳門文化遺產保護與管理的水平 - Pinheiro, Francisco Vizeu (澳門研究, 2015)

教育治理背景下的本科訊息公開:基於政策証據視覺的分析教育發展研究 (CSSCI) - 孟瀏今 (2015)

教育輿情中的教育政策目標, 議題關注與價值表達: 以兩份十大教育新聞榜單的話語分析為例 - 陳霜葉; 孟瀏今 (北京大學教育評論, 2014)

澳門《新城區總體規劃方案》之建議 - Pinheiro, Francisco Vizeu (澳門研究, 2017)

澳門天主教教理培育委員會《天主教教理》卷二「基督奧跡的慶典」課程 - Law, Cyril Jerome (2019)

澳門幼稚園老師對幼兒偏差行為的態度及輔導策略 - Cheong, Wai Fan (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

《澳門旅遊業發展總體規劃》文本建議 - Pinheiro, Francisco Vizeu (澳門研究, 2017)

澳門非特教專業小學教師對融合教育態度之研究 - Lei, Oi Meng (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門高小學生偏差行為現況、成因及處理方法的個案研究 - Wong, Kin Wai (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

馬相伯研究的點線面 – 生命、史料、信仰(On Ma Xiangbo Studies) - Law, Cyril Jerome (2019)